SYNTHESIS, CAPPING, AND DISPERSION OF TiO2 NANOCRYSTALS

By preparing and dispersing individual, uniformly sized TiO2 nanocrystals, the scattering and transparency reduction caused by nanocrystal aggregation are solved, and a nanocomposite with high transparency and low scattering is achieved.

JP2025062602APending Publication Date: 2025-04-14US BANK TRUST CO NAT ASSOC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024232133
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-08-28
Filing Date
2024-12-27
Publication Date
2025-04-14

AI Technical Summary

Technical Problem

The prior art is easy to form aggregates when preparing TiO2 nanocrystals, resulting in a decrease in scattering and transparency of nanocrystals in nanocomposite.

Method used

A single, uniformly sized TiO2 nanocrystals were prepared by a method and mixed with the solvent. Through heat treatment and pressure control, the uniform dispersion and stability of the nanocrystals in the solvent were ensured.

Benefits of technology

The high transparency and low scattering of TiO2 nanocrystals in nanocomposite are achieved, and the stable combination of nanocrystals and matrix materials is improved, improving the optical performance of nanocomposite.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062602000001_ABST
    Figure 2025062602000001_ABST
Patent Text Reader

Abstract

To provide a method of preparing monodispersed TiO2 nanocrystals with nanocrystal size between 1 to 30 nm, and the prepared TiO2 nanocrystals.SOLUTION: A method of preparing TiO2 nanocrystals comprises converting a precursor of titanium dioxide into TiO2 nanocrystals in a solvent. The majority of the solvent is not water, and the converting comprises 1) mixing the precursor of titanium dioxide in the solvent to provide a reaction mixture, and 2) heating the reaction mixture at a reaction temperature, e.g., about 180°C to about 250°C, about 200°C to about 210°C, for a period of time to provide the TiO2 nanocrystals. Dispersions of nanocrystals can be formed in various solvents at high loading, high transmittance, and low viscosity. Formulations incorporating these nanocrystals and a matrix material are highly stable, where the resulting nanocomposites have high refractive index and are optically transparent in the visible wavelengths, with very little or no scattering.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS: This application claims priority to U.S. Provisional Application No. 62 / 769,703, filed November 20, 2018, and U.S. Provisional Application No. 62 / 892,625, filed August 28, 2019, the contents of which are incorporated by reference in their entireties.

[0002] Capped colloidal TiO 2 Described herein is the preparation of nanocrystals and their dispersions in solvents, monomers, oligomers, and polymers, as well as the resulting nanocomposite films. 2 The nanocrystals are highly monodisperse with nanocrystal sizes between 1-50 nm. These nanocrystals may be used to form nanocomposites incorporating high loadings of uniformly dispersed capped nanocrystals therein. Dispersions of nanocrystals may be formed in a variety of solvents, and these dispersions have high loadings, high transmittance, and low viscosity. The resulting formulations incorporating these nanocrystals and matrix materials are highly stable, and the resulting nanocomposites are optically transparent at visible wavelengths with high refractive index and little or no scattering. Additionally, TiO synthesized by the disclosed method has been shown to be highly stable and highly transparent at visible wavelengths with low or no scattering. 2 Nanocrystals were synthesized in a similar manner. 2 It can be mixed with nanocrystals to form nanocomposites with unique properties. [Background technology]

[0003] Titanium dioxide (TiO2), or titania, is one of the most widely used multifunctional ceramic materials due to its unique physical and chemical properties combined with its abundance and non-toxicity. TiO 2Titania is commercially produced on a multi-million ton scale due to its bulk properties, including high refractive index and (UV) light absorption, and is commonly found in pigments, paints, sunscreens, and coatings. These applications utilize a wide range of sizes of titania, from a few nanometers to a few micrometers. In addition to traditional applications, titania is also being investigated for use in many other emerging applications, including optoelectronics, photovoltaics, catalysis, fuel cells, batteries, smart windows, sensors, CMOS sensors, LEDs, mini-LEDs, micro-LEDs, organic LEDs (OLEDs), quantum LEDs (QLEDs), touch screens, displays, flexible electronics, printed electronics, and self-cleaning surfaces. TiO 2 One of the applications of nanoparticles that is gaining attention is in augmented reality (AR), mixed reality (MR), and virtual reality (VR) applications as high refractive index materials for use in waveguides, light extraction, and 3D sensors. 2 The high refractive index of titania is beneficial for enhancing the viewing angle in AR applications, which is a key feature in AR applications. Titania has also been heavily explored as a wide band gap semiconductor material for photocatalytic processes. Titania nanocrystals with small particle and shape sizes (<100 nm) have shown high UV light absorption along with high visible light transmittance. When combined with monomers into films, these nanocomposites show high transparency. Titania nanocrystals have also attracted great interest in the fields of plasmonics and metamaterials due to their diverse applications in energy storage, sub-diffraction imaging, structural color, sensing, light harvesting, cloaking, negative refraction, and optical information recording.

[0004] More specifically, TiO with particle size less than 50 nm 2Nanocrystals are considered for use in optical layers due to their inherent high transparency, high refractive index, and UV light absorption. Applications include internal light extraction layers, optical adhesives, microlens arrays, optical coatings, waveguides, and diffraction gratings. In addition, these materials are highly dispersible due to their small size and the functionality of the organic ligands, with loadings reaching 80% in dispersions, and can be easily applied by spin coating, spray coating, dispensing, slot die, inkjet printing, screen printing, nanoinjection, and other methods. They can be easily deposited / fabricated using existing techniques such as imprinting, photopatterning, roll-to-roll, or imprint deposition.

[0005] A nanocrystal is a single crystal of a material with at least one dimension of the crystal less than one micron in size. Nanocrystals may retain the optical, mechanical, and physical properties of their bulk crystals or may exhibit completely different properties. Nanocrystals can be produced by a variety of methods, including liquid synthesis, solvothermal synthesis, gas-phase synthesis, aerosol synthesis, pyrolysis, flame pyrolysis, laser pyrolysis, ball milling, and laser ablation.

[0006] Common routes to produce nanocrystals often result in agglomerates that cause scattering and poor transmission in the resulting nanocomposite. One key to producing well-dispersed nanocomposites is to use nanocrystals that do not agglomerate before mixing with the matrix or vehicle begins. Summary of the Invention

[0007] The present disclosure provides monodisperse TiO nanoparticles having nanocrystal sizes between 1 and 50 nm. 2 Methods for preparing nanocrystals and TiO prepared according to these methods 2 The present disclosure also provides TiO nanocrystals. 2 Methods for capping nanocrystals and capped TiO prepared according to these methods 2 The nanocrystals prepared according to these methods are provided. 2Also provided herein are formulation dispersions, nanocomposite compositions, substrates, coatings, and devices of monomers, oligomers, and polymers containing nanocrystals. The nanocrystals provided can be formed in a variety of solvents at high loadings, high transmittance, and low viscosity. Formulations incorporating these nanocrystals and matrix materials are highly stable, and the resulting nanocomposites have a high refractive index, and are optionally optically transparent at visible wavelengths with little or no scattering.

[0008] In some embodiments, the present disclosure provides: [1] Titanium dioxide precursor is dissolved in a solvent and TiO 2 Converting TiO into nanocrystals 2 A method of preparing nanocrystals, wherein the solvent is not predominantly water; [2] The conversion may include 1) mixing a titanium dioxide precursor in a solvent, optionally with water, to provide a reaction mixture; and 2) heating the reaction mixture at a reaction temperature, e.g., from about 180° C. to about 250° C., from about 200° C. to about 210° C., for a period of time to form TiO. 2 providing a nanocrystal; [3] The conversion may include: 1) adding a titanium dioxide precursor and, optionally, water to a solvent to provide a reaction mixture; and 2) heating the reaction mixture at a reaction temperature of about 180°C to about 250°C (e.g., about 200°C to about 210°C, or about 203°C to about 207°C) for about 10 minutes to 5 hours (e.g., 20 minutes to 1 hour, or 1-5 hours) to produce TiO. 2 obtaining nanocrystals according to [1]; [4] The method according to [2] or [3], wherein heating the reaction mixture at the reaction temperature is carried out under a pressure in the range of about 40 psi to about 500 psi, for example about 40 psi to about 150 psi; [5] The method according to any one of [2] to [4], wherein the reaction mixture is heated to the reaction temperature at a heating rate of about 0.1° C. to 5° C. per minute, for example about 0.5° C. to about 3° C. per minute; [6] The molar ratio of titanium dioxide precursor to water, if applicable, is from about 1:0 to about 1:10, e.g., from about 1:0 to 1:0.1, 1:0.1 to 1:0.5, 1:0.5 to 1:1, 1:1 to 1:1.5, 1:1.5 to 1:2, 1:2 to 1:2.5, 1:2.5 to 1:3, 1:3 to 1:3.5, 1:3.5 to 1:4, [1]-[5] in the range of 1:4–1:4.5, 1:4.5–1:5, 1:5–1:5.5, 1:5.5–1:6, 1:6–1:6.5, 1:6.5–1:7, 1:7–1:7.5, 1:7.5–1:8, 1:8–1:8.5, 1:8.5–1:9, 1:9–1:9.5, or 1:9.5–1:10. 5. A method according to any one of the preceding claims; [7] The molar ratio of the titanium dioxide precursor to the solvent is from about 1:1 to about 1:150, e.g., from about 1:1 to 1:5, 1:5 to 1:10, 1:10 to 1:15, 1:15 to 1:20, 1:20 to 1:25, 1:25 to 1:30, 1:30 to 1:35, 1:35 to 1:40, 1:40 to 1:45, 1:45 to 1:50, 1:50 to 1: 55, 1:55 to 1:60, 1:60 to 1:65, 1:65 to 1:70, 1:70 to 1:75, 1:75 to 1:80, 1:80 to 1:85, 1:85 to 1:90, 1:90 to 1:95, 1:95 to 1:100, or 1:100 to 1:150; [8] The method of any one of [1]-[7], wherein the titanium dioxide precursor is a titanium alkoxide, e.g., a titanium alkoxide having a formula of Ti(OR)4, a compound having a formula of Ti(OR)xGy, or a combination thereof, each R group can independently be an alkyl group (e.g., a C1-C6 alkyl group), or a substituted alkyl group, each occurrence of G group is independently a halogen (e.g., Cl), x is an integer from 0 to 4, and y is an integer from 0 to 4, with the proviso that x+y is 4; [9] The precursor of titanium dioxide is titanium methoxide (Ti(OCH 3 ) 4 ), titanium ethoxide (Ti(OCH 2 CH 3 ) 4 ), titanium n-propoxide (Ti(OCH2 CH 2 CH 3 ) 4 ), titanium isopropoxide (Ti(OCH(CH 3 ) 2 ) 4 ), titanium n-butoxide (Ti(OCH 2 CH 2 CH 2 CH 3 ) 4 ), titanium oxyacetylacetonate (TiO(CH 3 COCHCOCH 3 ) 2 ), titanium chloride (TiCl 4 ), titanium chlorotriisopropoxytitanium (TiCl(OCH(CH 3 ) 2 ) 3 ), titanium chlorotributoxide (TiCl(OCH 2 CH 2 CH 2 CH 3 ) 3 ), titanium dichloride diethoxide (TiCl 2 (OCH 2 CH 3 ) 2 ), and combinations thereof;

[10] The method according to any one of [1] to [7], wherein the precursor of titanium dioxide is titanium methoxide, titanium ethoxide, titanium n-propoxide, titanium isopropoxide, titanium n-butoxide, or a combination thereof;

[11] The method according to any one of [1] to

[10] , wherein the solvent is an alcohol-based solvent, an ether-based solvent, a glycol-based solvent, a ketone-based solvent, an ester-based solvent, an aromatic solvent, water, or a combination thereof;

[12] The solvent is benzyl alcohol, phenol, oleyl alcohol, butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, 2-(isopentyloxy)ethanol, 2-propoxy-propanol (PnP), 2-(hexyloxy)ethanol, tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ... the method of any one of [1] to

[10] , comprising one or more solvents selected from ethyl ether, diethylene glycol, dipropylene glycol, acetone, propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), methyl acetates, ethyl acetates, butyl acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, butoxyethyl acetate, ethyl acetate, 2-(2-butoxyethoxy)ethyl acetate, benzene, toluene, and water;

[13] The method according to any one of [1] to

[10] , wherein the solvent comprises benzyl alcohol, phenol, butanol, oleyl alcohol, dodecyl alcohol, and / or octadecanol;

[14] The method according to any one of [1] to

[13] , further comprising: 2 The method wherein the nanocrystals have an anatase crystal structure;

[15] The method according to any one of [1] to

[14] , further comprising: 2a method in which the nanocrystals have an average particle size of less than 50 nm (e.g., less than about 50 nm, less than about 40 nm, less than about 30 nm, less than about 20 nm, less than about 10 nm, or less than about 5 nm, e.g., about 1 nm, about 4 nm, about 5 nm, about 10 nm, about 15 nm, about 20 nm, about 35 nm, about 30 nm, about 40 nm, about 50 nm, or any range between the recited values, e.g., about 1 nm to about 5 nm, about 1 nm to about 10 nm, about 40 nm to about 50 nm, about 20 nm to about 30 nm, about 10 nm to about 20 nm, about 30 nm to about 40 nm, about 4 nm to about 50 nm, about 4 nm to about 20 nm, about 15 nm to about 20 nm, or about 10 nm to about 25 nm), as measured by TEM;

[16] The method according to any one of [1] to

[15] , further comprising: 2 a method wherein the nanocrystals have an average particle size of about 4 nm to about 50 nm, e.g., about 4 nm to about 20 nm, or about 15 nm to about 20 nm, as measured by TEM;

[17] The method according to

[16] , further comprising the step of: 2 a method wherein the nanocrystals have an average particle size of about 10 nm to about 25 nm as measured by TEM;

[18] TiO having an average particle size of less than 10 nm (e.g., less than 5 nm, e.g., from about 1 nm to about 5 nm, or from about 1 nm to about 10 nm) as measured by TEM. 2 A method of preparing nanocrystals includes: 1) adding a titanium dioxide precursor and water to a solvent to provide a reaction mixture; and 2) heating the reaction mixture at a reaction temperature of about 180° C. to about 250° C. (e.g., about 200° C. to about 210° C., about 203° C. to about 207° C.) for about 10 minutes to 5 hours (e.g., about 20 minutes to 1 hour, or 1-5 hours) to form a TiO nanocrystal. 2 and providing nanocrystals of the formula:

[19] The method according to

[18] , wherein heating the reaction mixture at the reaction temperature is carried out under a pressure in the range of about 40 psi to about 500 psi, for example about 40 psi to about 150 psi;

[20] The method according to any one of

[18] to

[19] , wherein the reaction mixture is heated to the reaction temperature at a heating rate of about 0.1° C. to 5° C. per minute, for example about 0.5° C. to about 3° C. per minute;

[21] The molar ratio of titanium dioxide precursor to the solvent is from about 1:1 to about 1:150, e.g., 1:1-1:5, 1:5-1:10, 1:10-1:15, 1:15-1:20, 1:20-1:25, 1:25-1:30, 1:30-1:35, 1:35-1:40, 1:40-1:45, 1:45-1:50, 1:50-1: 55, 1:55-1:60, 1:60-1:65, 1:65-1:70, 1:70-1:75, 1:75-1:80, 1:80-1:85, 1:85-1:90, 1:90-1:95, 1:95-1:100, 1:100-1:150;

[22] TiO having an average particle size of greater than 4 nm but less than 50 nm (e.g., from about 10 nm to about 25 nm, or from about 4 nm to about 20 nm) as measured by TEM. 2 A method of preparing nanocrystals includes: 1) adding a titanium dioxide precursor and water to a solvent to provide a reaction mixture; and 2) heating the reaction mixture at a reaction temperature of about 180° C. to about 250° C. (e.g., about 200° C. to about 210° C.) for about 10 minutes to 5 hours (e.g., 20 minutes to 1 hour, or 1-5 hours) to form TiO nanocrystals. 2 wherein the molar ratio of titanium dioxide precursor to water is in the range of from about 1:0.3 to about 1:3, e.g., from about 1:0.5 to about 1:2.5, from about 1:0.5 to about 1:1, from about 1:1 to about 1:1.5, from about 1:1.5 to about 1:2, from about 1:2 to about 1:2.5, or less than 1, e.g., less than 0.5, less than about 0.1, less than about 0.2, less than about 0.3, less than about 0.4, less than about 0.45, or from about 0.2 to about 0.5, or from about 0.3 to about 0.45;

[23] The method according to

[22] , wherein heating the reaction mixture at the reaction temperature is carried out under a pressure in the range of about 40 psi to about 500 psi, for example about 40 psi to about 150 psi;

[24] The method according to any one of

[22] to

[23] , wherein the reaction mixture is heated to the reaction temperature at a heating rate of about 0.1° C. to 5° C. per minute, for example about 0.5° C. to about 3° C. per minute;

[25] The molar ratio of titanium dioxide precursor to the solvent is from about 1:1 to about 1:150, e.g., 1:1-1:5, 1:5-1:10, 1:10-1:15, 1:15-1:20, 1:20-1:25, 1:25-1:30, 1:30-1:35, 1:35-1:40, 1:40-1:45, 1:45-1:50, 1:50-1: 55, 1:55-1:60, 1:60-1:65, 1:65-1:70, 1:70-1:75, 1:75-1:80, 1:80-1:85, 1:85-1:90, 1:90-1:95, 1:95-1:100, 1:100-1:150;

[26] The precursor of titanium dioxide is titanium alkoxide, e.g., Ti(OR) 4 Titanium alkoxide, Ti(OR) x G y or a combination thereof, wherein each R group can be independently an alkyl group or a substituted alkyl group, and each occurrence of G group is independently a halogen (e.g., Cl), x is an integer from 0 to 4, and y is an integer from 0 to 4, with the proviso that x+y is 4;

[27] The precursor of titanium dioxide is titanium methoxide (Ti(OCH 3 ) 4 ), titanium ethoxide (Ti(OCH 2 CH 3 ) 4 ), titanium n-propoxide (Ti(OCH 2 CH 2 CH 3 ) 4 ), titanium isopropoxide (Ti(OCH(CH 3 ) 2 ) 4), titanium n-butoxide (Ti(OCH 2 CH 2 CH 2 CH 3 ) 4 ), titanium oxyacetylacetonate (TiO(CH 3 COCHCOCH 3 ) 2 ), titanium chloride (TiCl 4 ), titanium chlorotriisopropoxytitanium (TiCl(OCH(CH 3 ) 2 ) 3 ), titanium chlorotributoxide (TiCl(OCH 2 CH 2 CH 2 CH 3 ) 3 ), titanium dichloride diethoxide (TiCl 2 (OCH 2 CH 3 ) 2 ), and combinations thereof;

[28] The method according to any one of

[18] to

[25] , wherein the precursor of titanium dioxide is titanium methoxide, titanium ethoxide, titanium n-propoxide, titanium isopropoxide, titanium n-butoxide, or a combination thereof;

[29] The method according to any one of

[18] to

[28] , wherein the solvent is an alcohol-based solvent, an ether-based solvent, a glycol-based solvent, a ketone-based solvent, an ester-based solvent, an aromatic solvent, water, or a combination thereof;

[30] The solvent is benzyl alcohol, phenol, oleyl alcohol, butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, 2-(isopentyloxy)ethanol, 2-propoxy-propanol (PnP), 2-(hexyloxy)ethanol, tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ... the method according to any one of

[18] to

[28] , comprising one or more solvents selected from ethyl ether, diethylene glycol, dipropylene glycol, acetone, propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), methyl acetates, ethyl acetates, butyl acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, butoxyethyl acetate, ethyl acetate, 2-(2-butoxyethoxy)ethyl acetate, benzene, toluene, and water;

[31] The method according to any one of

[18] to

[28] , wherein the solvent comprises benzyl alcohol, phenol, butanol, oleyl alcohol, dodecyl alcohol, and / or octadecanol.

[32] TiO prepared according to the above method 2 The method according to any one of

[18] to

[31] , wherein the nanocrystals have an anatase crystal structure;

[33] The method according to any one of [1] to

[32] , further comprising: 2a method in which the nanocrystals have a narrow particle size distribution, the particle size distribution being characterized by: 1) a ratio of D90:D10 less than 5, preferably less than 3, or less than 2, e.g., from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.8, from about 1.2 to about 3, or from about 1.5 to about 3; 2) a ratio of D90:D50 less than 3, preferably less than 2, or less than 1.5, e.g., from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.5; and / or 3) a ratio of D50:D10 less than 3, preferably less than 2, or less than 1.5, e.g., from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.5;

[34] The method according to any one of [1] to

[32] , further comprising: 2 a method in which the nanocrystals have a narrow particle size distribution, characterized by a standard deviation (σ) of the particle size distribution of 15% or less (e.g., 10% or less, or 5% or less, e.g., about 1% to about 15%, about 5% to about 10%, or about 10% to about 15%) of the median particle size of the nanocrystals, as measured by TEM;

[35] The method according to any one of [1] to

[32] , further comprising: 2 a method in which the nanocrystals have a narrow particle size distribution, characterized by a standard deviation (σ) of the particle size distribution of 5 nm or less (e.g., 3 nm or less, or about 1 nm or less, e.g., about 1 nm, about 3 nm, about 5 nm, or any range between the recited values, e.g., about 1-3 nm, about 1-5 nm, about 3-5 nm, etc.), as measured by TEM;

[36] The method according to any one of [1] to

[32] , further comprising: 2 a method wherein the nanocrystals have a narrow particle size distribution, characterized in that greater than about 90% (e.g., greater than about 95%, or greater than about 99%, e.g., about 91%, about 95%, about 98%, about 99%, about 99.5%, or any range between the recited values, e.g., 90-99%, 90-95%, or 95-99%) of the nanoparticles have a particle size within 5 nm of the average particle size, as measured by TEM;

[37] TiO2 Separating the solvent from the nanocrystals to obtain wet TiO 2 The method according to any one of [1] to

[36] , further comprising providing a nanocrystal;

[38] Wet TiO 2 The method of

[37] , further comprising suspending the nanocrystals in a second solvent, e.g., a capping solvent;

[39] A TiO prepared by the method described in any one of [1] to

[38] . 2 Nanocrystals;

[40] A TiO having an average particle size of less than 50 nm (e.g., less than about 50 nm, less than about 40 nm, less than about 30 nm, less than about 20 nm, less than about 10 nm, or less than about 5 nm, e.g., about 1 nm, about 4 nm, about 5 nm, about 10 nm, about 15 nm, about 20 nm, about 35 nm, about 30 nm, about 40 nm, about 50 nm, or any range between the recited values), as measured by TEM, e.g., a TiO having an average particle size of about 1 nm to about 5 nm, about 1 nm to about 10 nm, about 40 nm to about 50 nm, about 20 nm to about 30 nm, about 10 nm to about 20 nm, about 30 nm to about 40 nm, about 4 nm to about 50 nm, about 4 nm to about 20 nm, about 15 nm to about 20 nm, or about 10 nm to about 25 nm, as measured by TEM. 2 Nanocrystals;

[41] 1) a ratio of D90:D10 of less than 5, preferably less than 3, or less than 2, e.g., from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.8, from about 1.2 to about 3, or from about 1.5 to about 3; 2) a ratio of D90:D50 of less than 3, preferably less than 2, or less than 1.5, e.g., from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.5; and and / or 3) a TiO as described in

[40] , having a narrow particle size distribution characterized by a D50:D10 ratio of less than 3, preferably less than 2, or less than 1.5, for example from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.5. 2 Nanocrystals;

[42] A TiO nanoparticle as described in

[40] having a narrow particle size distribution characterized by a standard deviation (σ) of the particle size distribution of 15% or less (e.g., 10% or less, or 5% or less, e.g., from about 1% to about 15%, from about 5% to about 10%, or from about 10% to about 15%) of the median particle size of the nanocrystals, as measured by TEM. 2 Nanocrystals;

[43] A TiO powder as described in

[40] , having a narrow particle size distribution characterized by a standard deviation (σ) of the particle size distribution of 5 nm or less (e.g., 3 nm or less, or about 1 nm or less, e.g., about 1 nm, about 3 nm, about 5 nm, or any range between the recited values, e.g., about 1-3 nm, about 1-5 nm, about 3-5 nm, etc.), as measured by TEM. 2 Nanocrystals;

[44] A TiO nanocrystal as described in

[40] having a narrow particle size distribution characterized by greater than about 90% (e.g., greater than about 95%, or greater than about 99%, e.g., about 91%, about 95%, about 98%, about 99%, about 99.5%, or any range between the recited values, e.g., 90-99%, 90-95%, or 95-99%, etc.) of the nanocrystals having a particle size within 5 nm of the average particle size, as measured by TEM. 2 Nanocrystals;

[45] The TiO according to any one of

[40] to

[44] , which has an anatase crystal structure. 2 Nanocrystals;

[46] The TiO according to any one of

[39] to

[45] . 2 The nanocrystals are reacted with a first capping agent in a first capping solvent to form a first at least partially capped TiO 2 Manufacture of nanocrystals of TiO 2 Methods for capping nanocrystals;

[47] The reaction is carried out by 1) reacting the at least partially capped TiO 22) mixing the nanocrystals with a first capping agent in a first capping solvent to provide a first reaction mixture; and 3) heating the first reaction mixture, for example, at the reflux temperature of the first capping solvent for a period of time (e.g., about 10 minutes to about 120 minutes) to produce a first at least partially capped TiO. 2

[46] , further comprising producing the nanocrystals;

[48] ​​1) A first at least partially capped TiO 2 2) mixing the nanocrystals with a second capping agent in a second capping solvent to provide a second reaction mixture; and 2) heating the second reaction mixture, for example, at the reflux temperature of the second capping solvent, for a period of time (e.g., from about 10 minutes to about 120 minutes) to produce a second at least partially capped TiO. 2 The method of

[46] or

[47] , further comprising producing the nanocrystals;

[49] The method of any one of

[45] to

[48] , further comprising: a) adding water to the first or second reaction mixture after each heating step 2); and b) heating the first or second reaction mixture for an additional period of time (e.g., from about 10 minutes to about 120 minutes);

[50] A first or second at least partially capped TiO 2 The method according to any one of

[45] to

[49] , further comprising isolating, purifying and / or drying the nanocrystals;

[51] The method of any one of

[45] to

[50] , wherein the first or second capping agent is independently selected from a silane, an alcohol, a carboxylic acid, a thiol, a sulfonate, a phosphonate, a phosphate, and combinations thereof;

[52] The first or second capping agent is selected from the group consisting of methyltrimethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, phenyltrimethoxysilane, dodecyltrimethoxysilane, m,p-ethylphenethyltrimethoxysilane, 2-[methoxy(polyethyleneoxy)propyl]trimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercapto ... Pyrtrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-isocyanatopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 1-hexenyltrimethoxysilane, 1-octenyltrimethoxysilane, phenylaminomethyl)methyldimethoxysilane, N-phenylaminopropyltrimethoxysilane, 3-(4-pyridyl)propyltrimethoxysilane, 2-(3-trimethoxysilylpropylthio)trimethoxysilane, N-(3-trimethoxysilylpropyl)pyrrole, 2-(3-trimethoxysilylpropylthio)thiophene, (3-trimethoxysilylpropyl)diethylenetriamine, 11-mercaptoundecyltrimethoxysilane, (2-diphenylphosphino)ethyldimethylethoxysilane, 2-(diphenylphosphino)ethyltriethoxysilane, 3-(diphenylphosphino)propyltriethoxysilane, heptanol, hexanol, octanol, benzyl alcohol, phenol, ethylene Alcohol, propanol, butanol, oleyl alcohol, dodecyl alcohol, octadecanol, triethylene glycol monomethyl ether, octanoic acid, acetic acid, propionic acid, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, benzoic acid, stearic acid, trifluoroacetic acid, biphenyl-4-carboxylic acid, 2-(2-methoxyethoxy)acetic acid, methacrylic acid, mono-2-(methacryloyloxy)ethyl succinate, 2-mercaptoethanol, 2-{2-(2-mercaptoethoxy)ethoxy}ethanol, 2-(2-

[50] , wherein the 2-(2-methoxyethoxy)ethanethiol, 1-octanethiol, sodium 2,3-dimercaptopropanesulfonate monohydrate, sodium dodecyl sulfate, dodecylphosphonic acid, octylphosphonic acid, (11-mercaptoundecyl)phosphonic acid, (11-(acryloyloxy)undecyl)phosphonic acid, 11-methacryloyloxyundecylphosphonic acid, [2-[2-(2-methoxyethoxy)ethoxy]ethyl]phosphonic acid ethyl ester, and combinations thereof;

[53] The method of any one of

[45] to

[50] , wherein the first or second capping agent is independently selected from methyltrimethoxysilane, n-octyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, and combinations thereof, e.g., the first or second capping agent is independently selected from methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and combinations thereof;

[54] The method according to any one of

[45] to

[53] , wherein the first or second capping solvent is independently selected from alcohol-based solvents, ether-based solvents, glycol-based solvents, ketone-based solvents, ester-based solvents, aromatic solvents, water, and combinations thereof;

[55] The first or second capping solvent is selected from the group consisting of benzyl alcohol, phenol, oleyl alcohol, butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, 2-(isopentyloxy)ethanol, 2-propoxy-propanol (PnP), 2-(hexyloxy)ethanol, tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol, dipropylene glycol, acetone, propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), methyl acetates, ethyl acetates, butyl carbitol acetate (BCA), butyl acetate, ethylene glycol monobutyl ether ... the method according to any one of

[45] to

[53] , wherein the alkyl group is independently selected from butyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, butoxyethyl acetate, ethyl acetate, 2-(2-butoxyethoxy)ethyl acetate, benzene, toluene, water, and combinations thereof;

[56] The method of any one of

[45] -

[53] , wherein the first or second capping solvent is independently selected from benzyl alcohol, butyl carbitol acetate (BCA), propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), ethyl acetate, toluene, and combinations thereof, e.g., the first or second capping solvent is independently selected from benzyl alcohol, butyl carbitol acetate (BCA), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl acetate, and combinations thereof;

[57] An at least partially capped TiO2 prepared by the method according to any one of

[45] to

[56] . 2 Nanocrystals;

[58] The TiO according to any one of

[39] to

[45] , which is at least partially capped with at least one capping agent selected from silanes, alcohols, carboxylic acids, thiols, sulfonates, phosphonates, phosphates, and combinations thereof. 2 At least partially capped TiO containing nanocrystals 2 Nanocrystals;

[59] At least one capping agent is selected from the group consisting of methyltrimethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, phenyltrimethoxysilane, dodecyltrimethoxysilane, m,p-Ethylphenethyltrimethoxysilane, 2-[methoxy(polyethyleneoxy)propyl]trimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-isocyanatopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 1-hexenyltrimethoxysilane, 1-octenyltrimethoxysilane, phenylaminomethyl)methyldimethoxysilane, N-phenylaminopropyltrimethoxysilane, 3-(4-pyridylethyl)thiopropyltrimethoxysilane, N-(3-trimethoxysilylpropyl)pyrrole, 2-(3-trimethoxysilylpropylthio)thiophene, (3-trimethoxysilylpropylthio)pyrrole, (2-(diphenylphosphino)ethyldimethylethoxysilane, 2-(diphenylphosphino)ethyltriethoxysilane, 3-(diphenylphosphino)propyltriethoxysilane, heptanol, hexanol, octanol, benzyl alcohol, phenol, ethanol, propanol, butanol, oleyl alcohol, dodecyl alcohol, octadecanol, triethylene glycol Monomethyl ether, octanoic acid, acetic acid, propionic acid, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, benzoic acid, stearic acid, trifluoroacetic acid, biphenyl-4-carboxylic acid, 2-(2-methoxyethoxy)acetic acid, methacrylic acid, mono-2-(methacryloyloxy)ethyl succinate, 2-mercaptoethanol, 2-{2-(2-mercaptoethoxy)ethoxy}ethanol, 2-(2-methoxyethoxy)ethanethiol, 1-octanethiol, 2,3-Dimercaptopropanesulfonic acid sodium monohydrate, sodium dodecyl sulfate, dodecylphosphonic acid, octylphosphonic acid, (11-mercaptoundecyl)phosphonic acid, (11-(acryloyloxy)undecyl)phosphonic acid, 11-methacryloyloxyundecylphosphonic acid, [2-[2-(2-methoxyethoxy)ethoxy,

[58] , wherein the at least partially capped nano-TiO is independently selected from: 2 crystal;

[60] The at least partially capped TiO of

[58] or

[59] , wherein the at least one capping agent is selected from methyltrimethoxysilane, n-octyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, and combinations thereof, e.g., the at least one capping agent is selected from methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and combinations thereof. 2 Nanocrystals;

[61] In dry and / or substantially pure form, e.g., TiO 2 The capping agent used to cap the nanocrystals, and / or TiO 2

[57] -

[60] , wherein the at least partially capped TiO is free or substantially free of by-products resulting from capping the nanocrystals. 2 Nanocrystals;

[62] The at least partially capped TiO according to any one of

[57] to

[61] . 2 Nanocrystals;

[63] The at least partially capped TiO nanoparticles according to any one of

[57] to

[62] , characterized in that the capped titanium dioxide nanocrystals have an average particle size, measured by volume, of less than 130 nm (e.g., less than 120 nm, less than 100 nm, less than 80 nm, less than 50 nm, less than 20 nm, or less than 10 nm, e.g., about 10 nm, about 20 nm, about 50 nm, about 80 nm, about 100 nm, about 120 nm, or any range between the recited values, e.g., about 10 to about 50 nm, about 50 nm to about 100 nm, etc.), as measured by Dynamic Light Scattering (DLS). 2 Nanocrystals;

[64] The at least partially capped TiO of

[63] , further characterized in that the D9999 is less than 500 nm (e.g., less than 200 nm, less than 100 nm, or less than 50 nm, e.g., about 10 nm, about 20 nm, about 50 nm, about 100 nm, about 200 nm, about 500 nm, or any range between the recited values, e.g., about 20 nm to about 50 nm, about 50 nm to about 100 nm, about 20 nm to about 200 nm, about 100 nm to about 200 nm, etc.) as measured by dynamic light scattering (DLS) on the volume of the capped titanium dioxide nanocrystals dispersed in a solvent at 5 wt. 2 Nanocrystals;

[65] The at least partially capped TiO according to any one of

[57] to

[64] , characterized by an organic content of about 5% to about 35%, preferably about 5% to about 15%, about 10% to about 25%, or about 15% to about 30%, as measured by TGA. 2 Nanocrystals;

[66] At least partially capped TiO 2 At least partially capped TiO nanocrystals are present in an amount greater than 30%, e.g., greater than 40%, greater than 50%, greater than 60%, or greater than 70%, by weight of the dispersion, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, or any range between the recited values, e.g., about 40-70%, about 30-80%, about 50-80%, etc.2 a nanocrystal dispersion comprising nanocrystals and a solvent;

[67] The at least partially capped TiO according to any one of

[57] to

[65] . 2 Nanocrystals, such as methyltrimethoxysilane, n-octyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, and at least partially capped TiO with a capping agent selected from silane, allyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, and combinations thereof. 2 The nanocrystal dispersion according to

[66] , comprising nanocrystals, preferably wherein the capping agent is selected from methyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and combinations thereof, more preferably wherein the capping agent is selected from methoxy(triethyleneoxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, and combinations thereof, for example wherein the capping agent is methoxy(triethyleneoxy)propyltrimethoxysilane;

[68] The nanocrystal dispersion of

[66] or

[67] , wherein the solvent is independently selected from alcohol-based solvents, ether-based solvents, glycol-based solvents, ketone-based solvents, ester-based solvents, aromatic solvents, water, and combinations thereof;

[69] The solvent may be benzyl alcohol, phenol, oleyl alcohol, butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, 2-(isopentyloxy)ethanol, 2-propoxy-propanol (PnP), 2-(hexyloxy)ethanol, tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol, dipropylene glycol, acetone, propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), methyl acetates, ethyl acetates, butyl carbitol acetate (BCA), butyl acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate. tart, butoxyethyl acetate, ethyl acetate, 2-(2-butoxyethoxy)ethyl acetate, benzene, toluene, water, and combinations thereof, preferably wherein the solvent is selected from benzyl alcohol, butyl carbitol acetate (BCA), butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, tetrahydrofuran, diethyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol, dipropylene glycol, acetone, propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), ethyl acetate, butyl acetate, diethylene glycol monoethyl ether acetate, toluene, and combinations thereof;

[70] The nanocrystal dispersion according to

[66] or

[67] , wherein the solvent is selected from benzyl alcohol, butyl carbitol acetate (BCA), isopropanol, tetrahydrofuran, propylene glycol monomethyl ether (PGME), dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), ethyl acetate, toluene, and combinations thereof, preferably, the solvent is selected from butyl carbitol acetate (BCA), propylene glycol monomethyl ether (PGME), dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl acetate, and combinations thereof, for example, the solvent is propylene glycol methyl ether acetate (PGMEA). dispersion;

[71] At least partially capped TiO 2 A nanocrystal dispersion comprising nanocrystals and a dispersing agent (e.g., a nonionic dispersing agent, an anionic dispersing agent, or a combination thereof), the nanocrystal dispersion comprising at least a partially capped TiO 2 A nanocrystal dispersion, wherein the nanocrystals are present in an amount greater than 30%, e.g., greater than 40%, greater than 50%, greater than 60%, greater than 70%, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, or any range between the recited values, by weight of the dispersion;

[72] The nanocrystal dispersion of

[71] , wherein the dispersing agent is selected from polyalkylene glycols and esters thereof, polyoxyalkylenes, polyhydric alcohol ester alkylene oxide adducts, alcohol alkylene oxide adducts, sulfonic acid esters, sulfonic acid salts, carboxylic acid esters, carboxylic acid salts, alkylamide alkylene oxide adducts, alkylamines, and combinations thereof;

[73] TiO in dispersion 2The nanocrystal dispersion according to any one of

[66] to

[72] , wherein the average particle size of the nanocrystals is in the range of 1 to 50 nm, e.g. 4 to 20 nm, or 15 to 20 nm, as measured by TEM;

[74] TiO in dispersion 2 The nanocrystal dispersion according to any one of

[66] to

[73] , wherein the D9999 of the nanocrystals, as determined by DLS, is in the range of 20 to 500 nm, preferably less than 200 nm;

[75] At least partially capped TiO in a dispersion 2 A nanocrystal dispersion according to any one of

[66] to

[74] , wherein the nanocrystals are uniformly dispersed without aggregation or sedimentation of the nanocrystals as observed by TGA;

[76] The nanocrystal dispersion of any one of

[66] -

[75] , wherein the dispersion is stable for more than 2 weeks, e.g., for 3 or 4 weeks, or for more than 3 weeks or more than 4 weeks, and exhibits a change in transmittance at 400 nm of less than 5% (e.g., less than 3%, less than 2%, or less than 1%, e.g., about 0.1%, about 0.5%, about 1%, about 2%, about 3%, or any range between the recited values, e.g., about 0.01-1%, about 0.1-1%, about 0.1-5%, about 0.5-2%, about 0.5-3%, about 0.5-1%, etc.) when stored in the dark at room temperature;

[77] At least partially capped TiO 2 A nanocrystal dispersion according to any one of

[66] to

[76] , prepared by a process comprising mixing nanocrystals with a solvent to form a dispersion;

[78] At least partially capped TiO 2 The nanocrystals are in substantially pure form, e.g., TiO 2 The capping agent used to cap the nanocrystals, and / or TiO 2 A nanocrystal dispersion according to

[77] , which is free or substantially free of by-products resulting from capping the nanocrystals;

[79] The method further comprises the step of: 2The nanocrystal dispersion of

[77] or

[78] , comprising mixing the nanocrystals with a solvent to form a dispersion;

[80] A nanocomposite formulation comprising the nanocrystal dispersion according to any one of

[66] to

[79] and a monomer, oligomer, and / or polymer;

[81] A nanocomposite formulation prepared by a process comprising mixing the nanocrystal dispersion according to any one of

[66] to

[79] with a monomer, an oligomer, and / or a polymer;

[82] 1) At least partially capped TiO 2 2) a nanocomposite formulation comprising a nanocrystal and a monomer, oligomer, and / or polymer;

[83] 1) At least partially capped TiO 2 a nanocomposite formulation comprising: nanocrystals; 2) monomers, oligomers, and / or polymers; and 3) a solvent;

[84] 1) At least partially capped TiO 2 1) a nanocomposite comprising: nanocrystals; 2) a monomer, oligomer, and / or polymer; and 3) a curing agent. Agent;

[85] 1) At least partially capped TiO 2 2) a monomer, oligomer, and / or polymer; 3) a solvent; and 4) a curing agent;

[86] The nanocomposite formulation according to any one of

[80] to

[85] , further comprising one or more components selected from a curing agent, an adhesion promoter, a wetting agent, a leveling agent, a dispersant, a viscosity modifier, and an antioxidant;

[87] The at least partially capped TiO according to any one of

[57] to

[65] . 2nanocrystals, such as TiO that are at least partially capped with a capping agent selected from methyltrimethoxysilane, n-octyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, and combinations thereof; 2 A nanocomposite formulation according to any one of

[80] to

[86] , which contains nanocrystals, preferably, the capping agent is selected from methyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and combinations thereof, more preferably, the capping agent is selected from methoxy(triethyleneoxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, and combinations thereof, for example, the capping agent is methoxy(triethyleneoxy)propyltrimethoxysilane;

[88] At least partially capped TiO 2 The nanocrystals are in substantially pure form, e.g., TiO 2 The capping agent used to cap the nanocrystals, and / or TiO 2 A nanocomposite formulation according to any one of

[80] to

[87] , which is free or substantially free of by-products resulting from capping nanocrystals;

[89] At least partially capped TiO 2The nanocomposite formulation according to any one of

[80] to

[88] , wherein the nanocrystals are present in an amount of greater than 30% by weight relative to the monomer, oligomer, and / or polymer, e.g., greater than 40%, greater than 50%, greater than 60%, greater than 70%, greater than 80%, or greater than 90%, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, about 90%, or any range between the recited values, e.g., about 50-90%, about 40-80%, about 60-90%, etc.;

[90] The monomers, oligomers, and / or polymers may be, for example, bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), bisphenol A ethoxylate diacrylates, bisphenol A propoxylate diacrylate, bisphenol F ethoxylate (2 EO / phenol) diacrylate, bisphenol A glycerolate diacrylates, bisphenol A ethoxylate dimethacrylate, ethoxylated (4) bisphenol A diacrylate (SR-601), bisphenol A ethoxylate diacrylate (SR-349), tris(2-acryloyloxy)ethyl}isocyanurate, tricyclodecane dimethanol diacrylate, tris(2-hydroxyethyl)isocyanurate triacrylate, cresol novolac epoxy acrylate (CN112C60), benzyl methacrylate (BMA), benzyl acrylate, trimethylolpropane triacrylate (TMPTA), trimethylolpropane ethoxylate (1 EO / OH) methyl ether diacrylate, 1,6-hexanediol diacrylate (HDDA, SR238B), tri(ethylene glycol) diacrylate, ethylene glycol diacrylate, poly(ethylene The nanocomposite formulation according to any one of

[80] to

[89] , wherein the compound is an acrylate, an epoxy, or an isocyanurate selected from di(ethylene glycol) diacrylate, glycerol 1,3-diglycerolate diacrylate, di(ethylene glycol) diacrylate, and combinations thereof;

[91] The monomers, oligomers, and / or polymers are selected from the group consisting of bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), bisphenol A ethoxylate diacrylates, bisphenol A propoxylate diacrylate, bisphenol F ethoxylate (2 EO / phenol) diacrylate, bisphenol A glycerolate diacrylates, bisphenol A ethoxylate dimethacrylate, ethoxylated (4) bisphenol A diacrylate. (SR-601), biphenol A ethoxylate diacrylate (SR-349), cresol novolac epoxy acrylate (CN112C60), and combinations thereof, preferably the monomer, oligomer, and / or polymer is selected from bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), ethoxylated (4) bisphenol A diacrylate (SR-601), biphenol A ethoxylate diacrylate (SR-349), cresol novolac epoxy acrylate (CN112C60), and combinations thereof, for example, the monomer, oligomer, and / or polymer is bisphenol A glycerolate dimethacrylate;

[92] The solvent, if present, is selected from benzyl alcohol, butyl carbitol acetate (BCA), butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, tetrahydrofuran, diethyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol, dipropylene glycol, acetone, propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), ethyl acetate, butyl acetate, diethylene glycol monoethyl ether acetate, toluene, and combinations thereof, preferably the solvent is selected from benzyl alcohol, butyl carbitol acetate (BCA), butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, tetrahydrofuran, diethyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol, dipropylene glycol, acetone, propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), ethyl acetate, butyl acetate, diethylene glycol monoethyl ether acetate, toluene, and combinations thereof. ), propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), ethyl acetate, toluene, and combinations thereof, more preferably the solvent is selected from benzyl alcohol, butyl carbitol acetate (BCA), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl acetate, and combinations thereof, for example, the solvent is dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), or a combination thereof. The nanocomposite formulation according to any one of

[80] to

[91] ;

[93] The nanocomposite formulation according to any one of

[80] to

[92] , wherein the curing agent, if present, is a photopolymerization initiator and / or a thermal free radical initiator;

[94] The curing agent may be Ebecryl Pl 15, Ebecryl P39, benzophenone, SpeedCure BEM, 4,4'-bis(diethylamino)benzophenone, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, Irgacure 184, 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), ethyl(2,4,6-trimethylbenzoyl)phenylphosphinate, 4-(dimethylamino)benzophenone, 2-isopropylthoxanthone, Darocure 4265, The nanocomposite formulation according to

[93] , comprising one or more agents selected from SpeedCure Xkm, methylbenzoylformate, thioxanthen-9-one, dicumyl peroxide, t-butyl perbenzoate, benzoyl peroxide, t-butyl peracetate, 1,1-di(t-butylperoxy)3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne, 2,2'-azobisisobutyronitrile, and combinations thereof;

[95] The nanocomposite formulation according to

[93] , wherein the curing agent comprises one or more agents selected from Ebecryl® Pl 15, Ebecryl® P39, benzophenone, diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide, Irgacure® 184, benzoyl peroxoside, and 2,2'-azobisisobutyronitrile;

[96] The nanocomposite formulation according to any one of

[80] to

[95] , further comprising at least one adhesion promoter selected from 3-aminopropyltriethoxysilane, 3-[(methacryloyloxy)propyl]trimethoxysilane, ureidopropyltrimethoxysilane, trimethoxy[3-(methylamino)propyl]silane, CN820, CN146, and combinations thereof;

[97] The nanocomposite formulation according to any one of

[80] to

[96] , further comprising at least one wetting agent selected from BYK-307, BYK-330, Novec 4430, Novec 4432, Novec 4434, and combinations thereof;

[98] The nanocomposite formulation according to any one of

[80] to

[97] , further comprising at least one leveling agent selected from BYK-352, BYK-353, BYK-356, BYK-361N, BYK-322, BYK-323, BYK-350, and combinations thereof;

[99] DISPERBYK-101, DISPERBYK-130, DISPERBYK-140, DISPERBYK-160, DISPERBYK-161, DISPERBYK-162, DISPERBYK-163, DISPERBYK-164, DISPERBYK-165, DISPERBYK-166, DISPERBYK-170, DISPERBYK-171, DISPERBYK-182, DISPERBYK-2000, DISPERBYK-2001, Solsperse 32000 32000), Solsperse 36000, Solsperse 28000, Solsperse 20000, Solsperse 41000, and Solsperse 45000, FC-4430, FC-4432, FC-4434 (3M), Capstone FS-3100, and combinations thereof;

[0100] The nanocomposite formulation according to any one of

[80] to

[99] , further comprising at least one antioxidant selected from Irganox 1010, Irganox 1076, SongNox® 1076, SongNox® 2450, SongNox® 1680, Irgaphos 168, SongLight® 6220, and combinations thereof;

[0101] TiO in the formulation 2 The nanocomposite formulation according to any one of

[80] to

[0100] , wherein the average particle size of the nanocrystals is in the range of 1 to 50 nm, for example, 4 to 20 nm, or 10 to 20 nm, as measured by TEM;

[0102] TiO in the formulation 2 The nanocomposite formulation according to any one of

[80] to

[0101] , wherein the D9999 of the nanocrystals is in the range of 20 to 500 nm, preferably less than 200 nm, as determined by DLS;

[0103] At least partially capped TiO in the formulation 2 Nanocrystals, TG A nanocomposite preparation according to any one of

[80] to

[0102] , in which the nanocrystals are uniformly dispersed without aggregation or precipitation as observed by A;

[0104] A nanocomposite formulation according to any one of

[80] to

[0103] , wherein the formulation is stable for more than 2 weeks, e.g., for 3 or 4 weeks, or for more than 3 weeks or more than 4 weeks, and exhibits a change in transmittance at 400 nm of less than 5% (e.g., less than 3%, less than 2%, or less than 1%, e.g., about 0.1%, about 0.5%, about 1%, about 2%, about 3%, or any range between the recited values, e.g., about 0.01-1%, about 0.1-1%, about 0.1-5%, about 0.5-2%, about 0.5-3%, about 0.5-1%, etc.) when stored in the dark at room temperature;

[0105] Brookfield RVDV II+ II+) The nanocomposite formulation according to any one of

[80] to

[0104] , having an adjustable viscosity in the range of about 1 cp to about 1000 cp, for example, about 1 cP to 2 cP, about 2 cP to 5 cP, about 5 cP to 10 cP, about 10 cP to 15 cP, about 15 cP to 20 cP, about 20 cP to 25 cP, about 25 cP to about 30 cP, about 30 cP to about 40 cP, about 40 cP to about 50 cP, about 50 cP to about 60 cP, about 60 cP to about 75 cP, about 75 cP to about 100 cP, about 100 cP to about 200 cP, about 200 cP to about 500 cP, or about 500 cP to about 1,000 cP, when measured at 25°C using a cone-and-plate viscometer;

[0106] Titania particles, polymer beads, silica particles, or ZrO 2 A nanocomposite formulation according to any one of

[80] to

[0105] , further comprising at least one scatterer particle, such as a controlled aggregate of nanocrystals;

[0107] 106. The nanocomposite formulation according to claim 105, wherein at least one scatterer has a particle size in the range of about 50 nm to about 2 μm, e.g., 50-100 nm, 100-200 nm, 200-300 nm, 300-400 nm, 400-500 nm, 500-600 nm, 600-700 nm, 700-800 nm, 800-900 nm, 900 nm to 1 μm, 1-1.5 μm, or 1.5-2 μm;

[0108] The nanocomposite formulation according to

[0106] or

[0107] , wherein the at least one scatterer particle is present in an amount of 0.1 to 40% by weight based on the total weight of the formulation;

[0109] The nanocomposite formulation according to any one of

[0106] to

[0108] , wherein the formulation has a viscosity of less than 5 cPs, or 5 cPs to 50 cPs, or 50 cPs to 200 cPs, or 200 cPs to 400 cPs, or 400 cPs to 650 cPs, or 650 cPs to 1000 cPs, when measured at 25°C using a Brookfield RVDV II+ cone and plate viscometer;

[0110]

[80] to

[0109] , comprising attaching the nanocomposite preparation to the surface of the substrate;

[0111] The method according to claim 1, wherein the substrate is a glass substrate, a ceramic substrate, a metal substrate, and / or a plastic substrate;

[0112] The method according to

[0110] or

[0111] , wherein the nanocomposite formulation is applied to the surface of the substrate by spin coating, spraying, dipping, screen printing, rolling, painting, printing, inkjet printing, dispensing, roll-to-roll coating, deposition by evaporation and / or vapor deposition, preferably by spin coating, inkjet printing, imprinting, nanoimprinting, photopatterning, roll-to-roll coating, slot-die coating, and / or screen printing;

[0113] The method according to any one of

[0110] to

[0112] , further comprising curing the nanocomposite formulation by light, e.g., UV light, or by heat treatment;

[0114]

[0110] -

[0113] A coated substrate prepared by the method according to any one of the above.

[0115]

[0114] A device comprising a coated substrate according to the invention;

[0116] Optoelectronic devices, photovoltaic devices, catalytic devices, fuel cells, batteries, smart windows, sensors, CMOS sensors, LEDs, mini LEDs, micro LE D. The device of

[0115] , which is an organic light emitting diode (OLED), a quantum light emitting diode (QLED), a touch screen, a display, a flexible electronics device, a printed electronics device, an augmented reality, a virtual reality, a mixed reality, a waveguide, a diffraction grating, or a solar cell device;

[0117] A device according to claim 115, comprising a lens structure as an internal light extraction layer, e.g. a light emitting diode device, wherein the internal light extraction layer comprises a coated substrate according to claim 114;

[0118] At least partially capped TiO nanocrystals are present in an amount greater than 50%, e.g., greater than 60%, greater than 70%, greater than 80%, or greater than 90%, e.g., about 55%, about 60%, about 70%, about 80%, about 90%, or any range between the recited values, e.g., about 55-90%, about 60-90%, about 70-90%, by weight of the nanocomposite. 2 a nanocomposite film comprising nanocrystals and at least one monomer, oligomer, and / or polymer;

[0119]

[57] to

[65] , wherein the at least partially capped TiO 2 nanocrystals, such as TiO that are at least partially capped with a capping agent selected from methyltrimethoxysilane, n-octyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, and combinations thereof; 2 A nanocomposite film according to

[0118] , comprising nanocrystals, wherein preferably the capping agent is selected from methyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and combinations thereof, more preferably the capping agent is selected from methoxy(triethyleneoxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, and combinations thereof, for example, the capping agent is methoxy(triethyleneoxy)propyltrimethoxysilane;

[0120] At least partially capped TiO 2 The nanocrystals are in substantially pure form, e.g., TiO 2 The capping agent used to cap the nanocrystals, and TiO 2 A nanocomposite film according to any one of claims 1 to 4, which is free or substantially free of by-products resulting from capping the nanocrystals;

[0121] The monomers, oligomers and / or polymers may be, for example, bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), bisphenol A ethoxylate diacrylates, bisphenol A propoxylate diacrylate, bisphenol F ethoxylate (2 EO / phenol) diacrylate, bisphenol A glycerolate diacrylates, bisphenol A ethoxylate dimethacrylate, ethoxylated (4) bisphenol A diacrylate (SR-601), bisphenol A ethoxylate diacrylate (SR-349), tris(2-acryloyloxy)ethyl}isocyanurate, tricyclodecane dimethanol diacrylate, tris(2-hydroxyethyl)isocyanurate triacrylate, cresol novolac epoxy acrylate (CN112C60), benzyl methacrylate (BMA), benzyl acrylate, trimethylolpropane triacrylate (TMPTA), trimethylolpropane ethoxylate (1 EO / OH) methyl ether diacrylate, 1,6-hexanediol diacrylate (HDDA, SR238B), tri(ethylene glycol) diacrylate, ethylene glycol diacrylate, poly(ethylene glycol) diacrylate, glycerol 1,3-diglycerolate diacrylate The nanocomposite film according to any one of

[0118] to

[0120] , wherein the compound is an acrylate, an epoxy, or an isocyanurate selected from the group consisting of acrylate, epoxy, di(ethylene glycol) diacrylate, and combinations thereof;

[0122] The monomers, oligomers, and / or polymers may be selected from the group consisting of bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), bisphenol A ethoxylate diacrylates, bisphenol A propoxylate diacrylate, bisphenol F ethoxylate (2 EO / phenol) diacrylate, bisphenol A glycerolate diacrylates, bisphenol A ethoxylate dimethacrylate, ethoxylated (4) bisphenol A diacrylate. (SR-601), biphenol A ethoxylate diacrylate (SR-349), cresol novolac epoxy acrylate (CN112C60), and combinations thereof, preferably, the monomer, oligomer, and / or polymer is selected from bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), ethoxylated (4) bisphenol A diacrylate (SR-601), biphenol A ethoxylate diacrylate (SR-349), cresol novolac epoxy acrylate (CN112C60), and combinations thereof, for example, the monomer, oligomer, and / or polymer is bisphenol A glycerolate dimethacrylate;

[0123] TiO as measured by DLS as a 5% nanocrystal dispersion in PGMEA 2 The nanocomposite film according to any one of

[0118] to

[0122] , wherein the average particle size of the nanocrystals is in the range of 1 to 5 nm, 5 to 10 nm, 10 to 15 nm, 15 to 20 nm, 20 to 30 nm, 30 to 40 nm, or 40 to 50 nm, and D9999 is less than 100 nm;

[0124] A nanocomposite film according to any one of

[0118] to

[0123] , wherein the % transmittance of the film having a thickness of 1 micron is greater than 80%, e.g., greater than 85%, greater than 90%, greater than 95%, greater than 97%, greater than 98%, greater than 99%, e.g., about 85%, about 90%, about 95%, about 97%, about 98%, about 99%, about 99.5%, or any range between the recited values, e.g., about 90-99%, at a wavelength of 400 nm;

[0125] When measured using a Prism Coupler for films having a thickness of <5 um, at 448 nm, it is about 1.70 to about 2.10, e.g., 1.70-1.72, or 1.72-1.74, or 1.74-1.76, or 1.76-1.78, or 1.78-1.80, or 1.80-1.82, or 1.82-1.84, or 1.84-1.86, or 1.86-1.88, or has a refractive index of 1.88 to 1.90, or 1.90 to 1.92, or 1.92 to 1.94, or 1.94 to 1.96, or 1.96 to 1.98, or 1.98 to 2.00, or 2.00 to 2.02, or 2.02 to 2.04, or 2.04 to 2.06, or 2.06 to 2.08, or 2.08 to 2.10, and / or at 635 nm; from about 1.70 to about 2.10, for example, 1.70 to 1.72, or 1.72 to 1.74, or 1.74 to 1.76, or 1.76 to 1.78, or 1.78 to 1.80, or 1.80 to 1.82, or 1.82 to 1.84, or 1.84 to 1.86, or 1.86 to 1.88, or 1.88 to 1.90, or 1.90 to 1.92, or The nanocomposite film according to any one of

[0118] to

[0124] , having a refractive index of 1.92 to 1.94, or 1.94 to 1.96, or 1.96 to 1.98, or 1.98 to 2.00, or 2.00 to 2.02, or 2.02 to 2.04, or 2.04 to 2.06, or 2.06 to 2.08, or 2.08 to 2.10;

[0126] greater than 50 MPa, greater than 100 MPa, or greater than 200 MPa, or greater than 300 MPa, or greater than 400 MPa, e.g., about 55 MPa, about 100 MPa, about 200 MPa, about 300 MPa, about 400 MPa, about 500 MPa, or any value in between as measured by nanoindentation. The nanocomposite film according to any one of

[0118] to

[0125] , having a hardness in the range of, for example, about 50 to 500 MPa, or about 100 to 400 MPa;

[0127] A nanocomposite film according to any one of

[0118] to

[0126] , wherein the percent absorption of a film having a thickness of 1 micron is less than 0.1%, less than 0.05%, or less than 0.01% at a wavelength of 450 nm, as measured with an integrating sphere;

[0128] A nanocomposite film according to any one of

[0118] to

[0127] , having a surface roughness Ra of less than 1 nm as measured by AFM over an area of ​​5 microns x 5 microns;

[0129] The nanocomposite film according to any one of

[0118] to

[0128] , wherein the haze of the nanocomposite film is less than 0.1%, or less than 0.2%, or less than 0.3%, or less than 0.4%, or less than 0.5%, or less than 1% (e.g., about 0.01% to about 0.1%, about 0.1% to about 0.2%, about 0.1% to about 0.5%, about 0.2% to about 0.5%, or about 0.1% to about 1%) as measured by a haze meter, and b* is less than 1, or less than 0.5, or less than 0.1 (e.g., about 0.01 to about 0.1, about 0.1 to about 0.5, about 0.1 to about 0.2, or about 0.1 to about 1);

[0130] A nanocomposite film according to any one of

[0118] to

[0129] , wherein the haze of the nanocomposite film is less than 0.1%, or less than 0.2%, or less than 0.3%, or less than 0.4%, or less than 0.5%, or less than 1% (e.g., about 0.01% to about 0.1%, about 0.1% to about 0.2%, about 0.1% to about 0.5%, about 0.2% to about 0.5%, or about 0.1% to about 1%), and the at least partially capped nanocrystals are uniformly dispersed in the film without agglomeration to achieve a uniform RI distribution, as observed by uniform particle distribution by TEM, SEM, or EDX images;

[0131] At least partially capped TiO 2 A method for preparing a nanocomposite film according to any one of

[0118] to

[0130] , comprising mixing nanocrystals with at least one monomer, oligomer, and / or polymer to provide a nanocomposite formulation, and optionally curing the nanocomposite formulation to provide a nanocomposite film;

[0132] At least partially capped TiO in a solvent 2 A method for preparing a nanocomposite film according to any one of

[0118] to

[0130] , comprising mixing nanocrystals with at least one monomer, oligomer, and / or polymer to provide a nanocomposite formulation, and optionally curing the nanocomposite formulation to provide a nanocomposite film;

[0133] At least partially capped TiO 2 A method for preparing a nanocomposite film according to any one of

[0118] to

[0130] , comprising mixing nanocrystals, a curing agent, and at least one monomer, oligomer, and / or polymer to provide a nanocomposite formulation, and optionally curing the nanocomposite formulation to provide a nanocomposite film;

[0134] At least partially capped TiO in a solvent 2A method for preparing a nanocomposite film according to any one of

[0118] to

[0130] , comprising mixing nanocrystals, a curing agent, and at least one monomer, oligomer, and / or polymer to provide a nanocomposite formulation, and optionally curing the nanocomposite formulation to provide a nanocomposite film;

[0135] At least partially capped TiO 2 The method according to any one of

[0131] to

[0134] , wherein the nanocrystals are prepared according to any one of the methods according to

[46] to

[56] ;

[0136] At least partially capped TiO 2 The TiO nanocrystals were prepared according to one of the methods described in [1]–

[38] . 2 The method according to any one of

[0131] to

[0135] , which is prepared from nanocrystals;

[0137] A device comprising the nanocomposite film according to any one of

[0118] to

[0130] ;

[0138] or a device according to claim 0137, which is an optoelectronic device, a photovoltaic device, a catalytic device, a fuel cell, a battery, a smart window, a sensor, a CMOS sensor, an LED, a mini LED, a micro LED, an organic LED (OLED), a quantum LED (QLED), a touch screen, a display, a flexible electronics device, a printed electronics device, an augmented reality, a virtual reality, a mixed reality, a waveguide, a diffraction grating, or a solar cell device; or

[0139] A device according to

[0138] , for example a light-emitting diode device, comprising a lens structure as an internal light extraction layer, wherein the internal light extraction layer comprises the nanocomposite film according to any one of

[0118] to

[0130] ;

[0009] The aggregation of nanocrystals is controlled by the surface chemistry (or effective surface chemistry) of the nanocrystals. In dispersions, interparticle forces (electrostatic, van der Waals, entropic, etc.) arise between the surfaces of the nanocrystals, which tend to form aggregates. These interparticle forces are particularly important for nanocrystals, because of the large surface area to volume ratio for these particles. To avoid aggregation in dispersions, it is desirable to passivate (or stabilize) the surface of the nanocrystals. One method that may be used to passivate the surface of the nanocrystals involves the introduction of ligand ions or molecules. These ligands, also called capping agents, are added to the surface of the nanocrystal, thus creating a new effective surface of the nanocrystal. This effective surface is the surface of the shell created by the complete or partial surface coverage with the capping agent. The chemistry of this effective surface can be tailored to create a chemical environment that is significantly different from the actual or initial surface of the nanocrystal, which promotes dispersion while preventing or reducing aggregation.

[0010] Liquid synthesis of colloidal metal oxide nanocrystals is a method for producing nanocrystals that are at least partially surface passivated during synthesis. Liquid synthesis is carried out in a solvent with or without the presence of a capping agent. The nanocrystals are protected from aggregation, at least in part, during and after synthesis by the capping agent.

[0011] After the synthesis of nanocrystals by liquid synthesis, the as-prepared surface passivation can be modified by a process known as capping exchange, in which one ligand or capping agent is at least partially replaced by a different one. In this process, the nanocrystals are typically dispersed in a solvent with the desired capping agent. In some cases, the temperature of the suspension may be increased to further accelerate the exchange process. The result of the capping exchange is that a new capping agent is added to a portion of the nanocrystal surface, or a portion of the previous surface passivation agent is replaced with a new capping agent, or some combination thereof. The new capping agent may be selected to create a chemical compatibility between the effective nanocrystal surface and the solvent or other medium selected for the final dispersion or application.

[0012] To achieve higher quality nanocomposites, the nanocrystals are advantageously less than 50 nm in at least one dimension, preferably less than 30 nm in at least one dimension, preferably less than 20 nm in at least one dimension, preferably less than 10 nm in at least one dimension, with a narrow particle size distribution, as well as a specific particle shape (rod-like, spherical, etc.). In addition, the surface chemistry of the nanocrystals is advantageously sufficiently passivated to prevent or reduce agglomeration, and to increase or promote compatibility with solvents and / or matrix materials, thereby allowing or enhancing the dispersion of the nanocrystals in the nanocomposite or other substrate containing it.

[0013] Nanocrystals of the present disclosure also include, for example, nanoparticles, quantum dots, and colloidal particles. These will be recognized in the art as being crystalline and / or amorphous particles having sizes ranging from hundreds of nanometers down to 1 nm or less.

[0014] Functionalized silanes are a common class of organic compounds used to assemble onto the surface of nanocrystalline oxide materials as capping agents. These silanes are typically composed of a head and a tail component. The head of the functionalized silane is typically either a trialkoxysilane or trichlorosilane group, but di- and mono-substituted alkoxy and chlorosilanes are also possible. The head is anchored to the oxide surface via covalent bonding with hydroxyl groups (-OH) present on the surface or with -OR groups, where R is an alkyl or aryl group, to remove alcohols, alkyl chlorides, water, or HCl as by-products. The tail of the functionalized silane can contain one or more of alkyl chains of different lengths, aryl groups, ether groups, amines, thiols, acrylates, methacrylates, or carboxylic acids.

[0015] Other classes of organic compounds used as capping agents to passivate the surface of oxide materials include carboxylic acids and alcohols. The head of the carboxylic acid is a carboxyl (-COOH) group and the head of the alcohol is a -OH group. The head is anchored to the oxide surface by covalent bonding with a hydroxyl (-OH) group present on the surface or with a -OR group, where R is an alkyl or aryl group, eliminating alcohol or water as a by-product. The tails of the functionalized carboxylic acids and alcohols can consist of alkyl chains of various lengths, aryl groups, ether groups, amines, thiols, acrylates, methacrylates, or carboxylic acids.

[0016] Yet another class of organic compounds that can be used to passivate metal oxide surfaces has head groups including thiols, sulfonates, phosphates, and phosphonates, where the head of the molecule is anchored to the oxide surface by covalent bonding with hydroxyl (-OH) groups present on the surface or with -OR (R = alkyl or aryl) groups, removing alcohol or water as a by-product. The tails of these organic compounds can consist of alkyl chains of various lengths, aryl groups, ether groups, amines, thiols, acrylates, or methacrylates.

[0017] The present disclosure further includes methods of surface modifying nanocrystals with silanes, alcohols, thiols, sulfonates, phosphonates, phosphates, and / or carboxylic acids. The methods include depositing a capping agent during synthesis of the nanocrystals or depositing a capping agent after synthesis through ligand exchange of at least a portion of the capping agent originally present on the nanocrystal with a second one. These reactions can be carried out under ambient, heated, and / or elevated temperature / pressure conditions.

[0018] The present disclosure relates to capped TiO 2 Further included are dispersions and formulations of nanocrystals. These dispersions may be in solvents and the formulations may include monomers, oligomers, and polymers in addition to other additives.

[0019] The present disclosure further includes nanocomposite materials containing a matrix and nanocrystals, e.g., mixed, stirred, or dispersed therein. Nanocomposites according to the present disclosure may be made, for example, by UV curing, thermal curing, melt blending, in situ polymerization, and / or solvent mixing of the nanocrystals with the matrix material or precursors to the matrix. [Brief description of the drawings]

[0020] [Figure 1]FIG. 1 is an exemplary TEM image of titanium oxide nanocrystals described in Example 8, showing particle sizes of less than 10 nanometers. [Diagram 2] FIG. 2 is an exemplary DLS plot of intensity versus particle size for capped titanium dioxide nanocrystals as described in Example 8 at 5 wt % in PGMEA, showing particle sizes less than 20 nanometers due to aggregates with an average particle size of 11.260 nanometers. [Diagram 3] FIG. 3 is an exemplary volume vs. particle size DLS plot of capped titanium dioxide nanocrystals described in Example 8 at 5 wt % in PGMEA, showing a particle size of less than 25 nanometers due to aggregates with an average particle size of 9.462 nanometers. [Figure 4] Figure 4A is an exemplary optical density plot of the capped titanium dioxide nanocrystals described in Example 8 dispersed at 50% by weight in PGMEA, and Figure 4B is an exemplary optical transmittance plot of the capped titanium dioxide nanocrystals described in Example 8 dispersed at 50% by weight in PGMEA. [Diagram 5] FIG. 5 is an illustrative TGA plot of the capped titanium oxide nanocrystals described in Example 8 dispersed at 50 wt % in PGMEA. [Figure 6] FIG. 6 is an exemplary XRD pattern of the titanium oxide nanocrystals described in Example 8 consistent with the anatase phase. [Figure 7] FIG. 7 is an exemplary TEM image of titanium oxide nanocrystals described in Example 10 showing particle sizes less than 30 nanometers. [Figure 8] FIG. 8 is an exemplary XRD pattern of titanium oxide nanocrystals described in Example 10 consistent with the anatase phase. [Figure 9] FIG. 9 is an exemplary DLS plot of intensity versus particle size for capped titanium dioxide nanocrystals as described in Example 10 at 5 wt % in PGMEA, showing particle sizes less than 130 nanometers due to aggregates with an average particle size of 50.7 nanometers. [Figure 10]FIG. 10 is an exemplary volume vs. particle size DLS plot of capped titanium dioxide nanocrystals described in Example 10 at 5 wt % in PGMEA, showing particle sizes less than 100 nanometers due to aggregates with an average particle size of 15.7 nanometers. [Figure 11] FIG. 11 is an illustrative TGA plot of the capped titanium oxide nanocrystals described in Example 10 dispersed at 50 wt % in PGMEA. [Figure 12] FIG. 12 is an exemplary TGA plot of the formulation described in Example 12. [Figure 13] FIG. 13 is an exemplary light transmittance of the formulation described in Example 12. [Figure 14] FIG. 14 is an exemplary light transmittance plot of a 2 micron thick spin-coated nanocomposite film produced from the formulation described in Example 12. [Figure 15] FIG. 15 is an exemplary optical transmittance plot of a 1 micron thick spin-coated nanocomposite film produced from the formulation described in Example 14 in the as-prepared state (solid line) and after heat treatment at 150° C. under vacuum for 2 hours (dotted line). [Figure 16] FIG. 16 is an exemplary optical transmittance plot of a 1 micron thick spin-coated nanocomposite film made from the formulation described in Example 15 in the as-prepared state (solid line) and after heat treatment at 150° C. for 2 hours under vacuum (dotted line). [Figure 17] FIG. 17 is an exemplary TGA plot of the formulation described in Example 16. [Figure 18] FIG. 18 is an exemplary light transmittance plot of a 2 micron thick spin-coated nanocomposite film produced from the formulation described in Example 16. [Figure 19] FIG. 19 shows exemplary light transmittance of 2 micron thick spin-coated nanocomposite films produced using the formulation described in Example 17. [Figure 20]FIG. 20 is an exemplary TEM image of titanium oxide nanocrystals described in Example 18, showing an average particle size of less than 15 nanometers. [Figure 21] FIG. 21 is an exemplary XRD pattern of the titanium oxide nanocrystals described in Example 18, consistent with the anatase phase. [Figure 22] FIG. 22 is an exemplary DLS plot of intensity versus particle size for capped titanium oxide nanocrystals as described in Example 18 at 5 wt % in PGMEA, showing an average particle size of 21.85 nanometers. [Diagram 23] FIG. 23 is an exemplary volume vs. particle size DLS plot of capped titanium oxide nanocrystals as described in Example 18 at 5 wt % in PGMEA with an average particle size of 17.91 nanometers. [Figure 24] FIG. 24 is an illustrative TGA plot of the capped titanium dioxide nanocrystals described in Example 18 dispersed at 50 wt % in PGMEA. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Brief explanation of the table Table 1: TiO in a 2 gallon Parr reactor 2 Reaction conditions used to synthesize nanocrystals.

[0022] Table 2: Aging data containing methoxy(triethyleneoxy)propyltrimethoxysilane capped titanium dioxide nanocrystals as described in Example 8 dispersed at 50 wt% in PGMEA, showing initial, 1 week, and 1 month values ​​for TGA, DLS, and UV measurements.

[0023] Table 3: Data containing various ratios of capped titanium dioxide nanocrystals and capped zirconium dioxide nanocrystals dispersed at 50 wt % in PGMEA, showing TGA, DLS, and UV measurements as described in Example 17.

[0024] Table 4: Optical properties including % transmission, refractive index, b*, and % haze of 2 micron thick spin-coated nanocomposite films made from the formulations described in Example 17.

[0025] Table 5: Summary of properties of nanocrystal dispersions and formulations described in various examples.

[0026] Table 6: Summary of optical properties of the nanocomposite films described in the various examples.

[0027] In various embodiments, the present disclosure provides novel TiO 2 Nanocrystalline, capped TiO 2 The present disclosure provides nanocrystals, dispersions containing them, nanocomposites such as films containing them, and / or devices (e.g., coated substrates) containing them. In some embodiments, the present disclosure provides novel TiO 2 Nanocrystalline, capped TiO 2 Methods of preparing and using the nanocrystals, dispersions, nanocomposites, and / or devices are also provided.

[0028] In some embodiments, the present disclosure provides a TiO 2 A method for preparing nanocrystals is provided, which typically involves converting a titanium oxide precursor to TiO using a solvothermal process. 2 The conversion is not limited to any particular mechanism and can typically involve hydrolysis or solvolysis of a titanium oxide precursor. Although not required, the conversion is usually carried out under an inert atmosphere. For simplicity, the terms "titanium oxide" and "titanium dioxide" are used interchangeably herein.

[0029] In some embodiments, the synthesis methods for preparing titanium dioxide nanocrystals described herein include solvothermal methods in which titanium dioxide precursors are mixed or dissolved in at least one solvent and allowed to react for a period of time. In some cases, the use of pressure and / or heat may be required. In a typical solvothermal process, the majority of the solvent is not water. When water is used as the majority of the solvent, the synthesis method is referred to as a hydrothermal synthesis. TiO 2 In the solvothermal synthesis of nanocrystals, a small amount of water is used as a reactant rather than as a solvent. Its addition to the reaction mixture results in better control of particle size and distribution than reactions carried out without the addition of water.

[0030] In some embodiments, the TiO 2 The method for preparing the nanocrystals involves reacting a titanium oxide precursor with water in a solvent, such as a non-aqueous solvent, to produce TiO. 2 In some embodiments, the TiO nanocrystals described herein may be provided. 2 A method for preparing the nanocrystals includes mixing a titanium oxide precursor in a solvent to provide a reaction mixture and heating the reaction mixture to form TiO. 2 In some embodiments, the TiO nanocrystals described herein may be provided. 2 A method for preparing the nanocrystals includes adding a titanium oxide precursor and water to a solvent to provide a reaction mixture, and heating the reaction mixture to form TiO. 2 In some embodiments, the titanium oxide precursor can be dissolved in a solvent. In some embodiments, the reaction mixture can be heated under pressure to provide TiO nanocrystals. 2Nanocrystals can be provided. In some embodiments, the amount of water added to the solvent can range from about 0.01 to about 10 molar equivalents of the titanium oxide precursor. The molar ratio of titanium oxide precursor to water is in the range of about 1:0 to about 1:10, for example, about 1:0 to 1:0.1, 1:0.1 to 1:0.5, 1:0.5 to 1:1, 1:1 to 1:1.5, 1:1.5 to 1:2, 1:2 to 1:2.5, 1:2.5 to 1:3, 1:3 to 1:3.5, 1:3.5 to 1:4, 1:4 to 1:4.5, 1:4.5 to 1:5, 1:5 to 1:5.5, 1:5.5 to 1:6, 1:6 to 1:6.5, 1:6.5 to 1:7, 1:7 to 1:7.5, 1:7.5 to 1:8, 1:8 to 1:8.5, 1:8.5 to 1:9, 1:9 to 1:9.5, 1:9.5 to 1:10. The molar ratio of titanium oxide precursor to the solvent ranges from about 1:1 to about 1:150, e.g., 1:1-1:5, 1:5-1:10, 1:10-1:15, 1:15-1:20, 1:20-1:25, 1:25-1:30, 1:30-1:35, 1:35-1:40, 1:40-1:45, 1:45-1:50, 1:50-1:55, 1:55-1:60, 1:60-1:65, 1:65-1:70, 1:70-1:75, 1:75-1:80, 1:80-1:85, 1:85-1:90, 1:90-1:95, 1:95-1:100, or 1:100 to 1:150. In some embodiments, water is not added to the solvent. Commercially available solvents, such as reagent grade solvents, typically contain some level of moisture. The methods described herein do not require additional measures to be taken to remove moisture otherwise present in the solvents used herein. For the avoidance of doubt, unless otherwise clear from the context, amounts of water referred to herein should be understood as externally added water and do not include amounts of water that may be present in the solvent itself. Suitable precursors, solvents, amounts of water, heating temperatures, durations, and pressures include any of those described herein.

[0031] The titanium oxide precursors useful in the methods herein are not particularly limited, so long as they can be converted to TiO2, for example, by hydrolysis, decomposition, and / or other suitable reactions. In some embodiments, the titanium oxide precursor can be a hydrolyzable precursor. In some embodiments, the precursors of titanium oxide nanocrystals may be one or more alkoxides, such as titanium methoxide (Ti(OCH3)4), titanium ethoxide (Ti(OCH2CH3)4), titanium n-propoxide (Ti(OCH2CH2CH3)4), titanium isopropoxide (Ti(OCH(CH3)2)4), titanium n-butoxide (Ti(OCH2CH2CH2CH3)4); acetylacetonates, such as titanium oxyacetylacetonate (TiO(CH3COCHCOCH3)2); halides, such as titanium chloride (TiCl4); and mixed halides and alkoxides, such as titanium chlorotriisopropoxytitanium (TiCl(OCH(CH3)2)3), chlorotributoxytitanium (TiCl(OCH2CH2CH2CH3)3), or titanium dichlorodiethoxide (TiCl2(OCH2CH3)2), or other organometallic compounds.

[0032] For example, in some embodiments, the TiO 2The titanium oxide precursor for the method of preparing nanocrystals can be a titanium alkoxide. In some embodiments, the titanium alkoxide can have the formula Ti(OR)4, where each R group can independently be an alkyl group (e.g., C1-C6 alkyl) or a substituted alkyl group, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, benzyl, and the like. In some embodiments, all the R groups in Ti(OR)4 can be the same, such as titanium methoxide (Ti(OCH3)4), titanium ethoxide (Ti(OCH2CH3)4), titanium n-propoxide (Ti(OCH2CH2CH3)4), titanium isopropoxide (Ti(OCH(CH3)2)4), or titanium n-butoxide (Ti(OCH2CH2CH2CH3)4). In some embodiments, at least one of the R groups of Ti(OR)4 can be different from the remaining R groups.

[0033] In some embodiments, the TiO 2 The titanium oxide precursor for the method of preparing nanocrystals can have a formula of Ti(OR)xGy, where each occurrence of R group can be independently an alkyl group or a substituted alkyl group, e.g., methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, benzyl, etc., each occurrence of G group can be independently a halogen, e.g., Cl, x can be an integer from 0 to 4, and y can be an integer from 0 to 4, with the proviso that x+y is 4.

[0034] In some embodiments, the methods herein include 2 To prepare nanocrystals, one precursor of titanium oxide, such as titanium butoxide (Ti(OCH2CH2CH2CH3)4), or isopropoxide (Ti(OCH(CH3)2)4), can be used. However, in some embodiments, the methods herein can be used to prepare TiO 2It is also possible to use a mixture of two or more precursors of titanium oxide to prepare nanocrystals, for example titanium ethoxide (Ti(OCH2CH3)4) and titanium isopropoxide (Ti(OCH(CH3)2)4).

[0035] As used herein, TiO 2 A variety of solvents are useful in the method of preparing nanocrystals. Typically, the solvent is selected so that the titanium oxide precursor and optionally added water can dissolve in the solvent. In some preferred embodiments, the solvent can have a boiling point higher than that of water. Non-limiting solvents useful in the present disclosure include alcohols, such as: benzyl alcohol, phenol, oleyl alcohol, butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, 2-(isopentyloxy)ethanol, 2-propoxypropanol (PnP), 2-(hexyloxy)ethanol; ethers and cyclic ethers, such as: tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, dipropylene glycol monomethyl ether, diethylene glycol monoethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ... The solvent may be one or more of: glycols, such as diethylene glycol, dipropylene glycol; ketones and cyclic ketones, such as acetone; esters, such as propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), methyl acetates, ethyl acetates, butyl acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, butoxyethyl acetate, ethyl acetate, 2-(2-butoxyethoxy)ethyl acetate, and the like; aromatics, such as benzene, toluene; and water, as well as any combination or mixture thereof. Some specific examples are: In typical embodiments, the solvent may include an alcohol-based solvent, preferably an alcohol-based solvent having a boiling point higher than that of water. In some embodiments, the solvent may include benzyl alcohol. In some embodiments, the solvent may be a single alcohol-based solvent, such as benzyl alcohol. In some embodiments, the solvent may be a mixture of solvents, such as a mixture of benzyl alcohol and another solvent.

[0036] Without wishing to be bound by theory, the first TiO 2 The properties of the nanocrystals were determined by the capped TiO 2 It is believed that the properties of the nanocrystals, dispersions, nanocomposites, and / or devices may be affected. Thus, some embodiments of the present disclosure provide TiO 2 with certain desired properties (e.g., those described herein). 2 Methods for preparing the nanocrystals are also of interest.

[0037] In some embodiments, the present disclosure provides a TiO 2 A method of preparing nanocrystals is provided, the method comprising: 1) adding a titanium oxide precursor (e.g., as described herein) and water in a solvent (e.g., an alcohol-based solvent such as benzyl alcohol, or another solvent described herein) to provide a reaction mixture, the molar ratio of titanium oxide precursor to water being in the range of about 0.01 to about 10 (e.g., about 0.1 to about 1, about 1 to about 2.5, about 0.1 to about 0.5, about 0.5 to about 1, about 2.5 to about 5, etc.); and 2) heating the reaction mixture at a temperature of about 180° C. to about 250° C. (e.g., about 200° C. to about 210° C.) for about 10 minutes to 5 hours (e.g., 20 minutes to 1 hour, or 1-5 hours) to form a TiO nanocrystal. 2 and providing nanocrystals, such as TiO nanocrystals, as described in detail herein. 2 The particle size and particle size distribution of the nanocrystals can be controlled by the reaction conditions herein, including, for example, the reaction temperature, the amount of water added, and the heating time. Thus, in some embodiments, TiO 2The reaction conditions are controlled such that the nanocrystals can have an average particle size of less than 50 nm (e.g., less than about 50 nm, less than about 40 nm, less than about 30 nm, less than about 20 nm, less than about 10 nm, less than about 5 nm, e.g., about 1 nm, about 4 nm, about 5 nm, about 10 nm, about 15 nm, about 20 nm, about 35 nm, about 30 nm, about 40 nm, about 50 nm, or any range between the recited values, e.g., about 1 nm to about 5 nm, about 1 nm to about 10 nm, about 40 nm to about 50 nm, about 20 nm to about 30 nm, about 10 nm to about 20 nm, about 30 nm to about 40 nm, about 4 nm to about 50 nm, about 4 nm to about 20 nm, about 15 nm to about 20 nm, or about 10 nm to about 25 nm, etc.) as measured by TEM, preferably with a narrow particle size distribution. For example, in some embodiments, the TiO 2 The nanocrystals can have a narrow particle size distribution characterized by: 1) a D90:D10 ratio of less than 5, preferably less than 3, or less than 2, e.g., from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.8, from about 1.2 to about 3, or from about 1.5 to about 3; 2) a D90:D50 ratio of less than 3, preferably less than 2, or less than 1.5, e.g., from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.5; and / or 3) a D50:D10 ratio of less than 3, preferably less than 2, or less than 1.5, e.g., from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.5. In some embodiments, the TiO 2 The nanocrystals may also have a narrow particle size distribution characterized by a standard deviation (σ) of the particle size distribution of 15% or less (e.g., 10% or less, or 5% or less, e.g., about 1% to about 15%, about 5% to about 10%, or about 10% to about 15%) of the median particle size of the nanocrystals, as measured by TEM. 2The nanocrystals may also have a narrow particle size distribution, as measured by TEM, characterized by a standard deviation (σ) of the particle size distribution of 5 nm or less (e.g., 3 nm or less, or about 1 nm or less, e.g., about 1 nm, about 3 nm, about 5 nm, or any range between the recited values, e.g., about 1-3 nm, about 1-5 nm, about 3-5 nm, etc.). In some embodiments, the TiO 2 The nanocrystals are greater than about 90% (e.g., greater than about 95%, or greater than about 99%, e.g., about 91%, about 95%, about 9 The TiO nanocrystals prepared by the methods herein may also have a narrow particle size distribution characterized in that at least about 8%, about 99%, about 99.5%, or any range between the recited values, e.g., 90-99%, 90-95%, or 95-99%, etc., have a particle size within 5 nm of the average particle size. 2 It is important to note that nanocrystals and their particle size distribution are also novel aspects of the present disclosure. In any of the embodiments described herein, TiO 2 The nanocrystals can have an anatase crystal structure.

[0038] In some embodiments, the present disclosure provides a TiO 2 A method for preparing nanocrystals is provided, the method comprising: 1) adding a titanium oxide precursor (e.g., titanium methoxide, titanium ethoxide, titanium n-propoxide, titanium isopropoxide, or titanium n-butoxide, or as otherwise described herein) and water to a solvent (e.g., an alcohol-based solvent such as benzyl alcohol, phenol, butanol, oleyl alcohol, dodecyl alcohol, and octadecanol, or as otherwise described herein) to provide a reaction mixture having a molar ratio of titanium oxide precursor to water ranging from about 0.1 to about 5; and 2) heating the reaction mixture at a temperature of about 180° C. to about 250° C. (e.g., about 200° C. to about 210° C.) for about 10 minutes to about 5 hours (e.g., 20 minutes to 1 hour, or 1-5 hours) to form TiO nanocrystals. 2providing nanocrystals. In some embodiments, the molar ratio of water to titanium oxide precursor in the reaction mixture ranges from about 0.1 to about 5, from about 1 to about 2.5, or from about 0.1 to about 0.5, etc. In some embodiments, the reaction mixture is heated at about 200° C. to about 210° C. (e.g., from about 203° C. to about 207° C.) for about 10 minutes to 5 hours (e.g., from 20 minutes to 1 hour, or 1-5 hours). In some embodiments, TiO 2 The reaction conditions are controlled such that the nanocrystals can have an average particle size of less than 50 nm (e.g., less than about 50 nm, less than about 40 nm, less than about 30 nm, less than about 20 nm, less than about 10 nm, less than about 5 nm, e.g., about 1 nm, about 4 nm, about 5 nm, about 10 nm, about 15 nm, about 20 nm, about 35 nm, about 30 nm, about 40 nm, about 50 nm, or any range between the recited values, e.g., about 1 nm to about 5 nm, about 1 nm to about 10 nm, about 40 nm to about 50 nm, about 20 nm to about 30 nm, about 10 nm to about 20 nm, about 30 nm to 40 nm, about 4 nm to about 50 nm, about 4 nm to about 20 nm, about 15 nm to about 20 nm, or about 10 nm to about 25 nm), as measured by TEM, preferably with a narrow particle size distribution. In some embodiments, the TiO 2 The reaction conditions are controlled so that the nanocrystals have an average particle size of about 1 nm to about 5 nm, about 1 nm to about 10 nm, about 40 nm to about 50 nm, about 20 nm to about 30 nm, about 10 nm to about 20 nm, or about 30 nm to about 40 nm, as measured by TEM, and preferably have a narrow particle size distribution. For example, in some embodiments, TiO 2The reaction conditions are controlled such that the nanocrystals can have a narrow particle size distribution characterized by: 1) a D90:D10 ratio of less than 5, preferably less than 3, or less than 2, e.g., from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.8, from about 1.2 to about 3, or from about 1.5 to about 3; 2) a D90:D50 ratio of less than 3, preferably less than 2, or less than 1.5, e.g., from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.5; and / or 3) a D50:D10 ratio of less than 3, preferably less than 2, or less than 1.5, e.g., from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.5. In some embodiments, TiO 2 The reaction conditions are controlled such that the nanocrystals may have a narrow particle size distribution characterized by a standard deviation (σ) of the particle size distribution of 15% or less (e.g., 10% or less, or 5% or less, e.g., about 1% to about 15%, about 5% to about 10%, or about 10% to about 15%) of the median particle size of the nanocrystals, as measured by TEM. In some embodiments, the TiO 2 The nanocrystals are characterized by a narrow particle size distribution, as measured by TEM, characterized by a standard deviation (σ) of the particle size distribution of 5 nm or less (e.g., 3 nm or less, or about 1 nm or less, e.g., about 1 nm, about 3 nm, about 5 nm, or any range between the recited values, e.g., about 1-3 nm, about 1-5 nm, about 3-5 nm, etc.). In some embodiments, the TiO 2 The reaction conditions are controlled such that the nanocrystals can also have a narrow particle size distribution characterized by greater than about 90% (e.g., greater than about 95%, or greater than about 99%, e.g., about 91%, about 95%, about 98%, about 99%, about 99.5%, or any range between the recited values, e.g., 90-99%, 90-95%, or 95-99%, etc.) of the nanocrystals having a particle size within 5 nm of the average particle size, as measured by TEM.

[0039] In some embodiments, the heating rate and heating time are adjusted to TiO 2The particle size of the nanocrystals may be affected. Typically, longer heating times or faster heating rates may result in larger particle sizes and wider particle size distributions. In some preferred embodiments, the reaction mixture may be heated at about 200° C. to about 210° C. for about 10 minutes to 5 hours (e.g., 20 minutes to 1 hour, or 1-5 hours). In some embodiments, the heating rate may be controlled to bring the reaction temperature (e.g., from about 200° C. to about 210° C., or from about 203° C. to about 207° C.) to about 0.1° C. to about 5° C. / min, e.g., from about 0.5° C. to about 3° C. / min. In some embodiments, the reaction mixture may be heated under a pressure ranging from about 40 psi to about 500 psi, e.g., from about 40 psi to about 150 psi.

[0040] As described herein, the amount of water in the reaction mixture is determined by the amount of TiO 2 The particle size of the nanocrystals can also be influenced. For example, in some embodiments, the desired TiO 2 The nanocrystals have an average particle size of less than 10 nm (e.g., less than 5 nm, e.g., from about 1 nm to about 5 nm, or from about 1 nm to about 10 nm), and in such cases, the molar ratio of titanium oxide precursor to water can preferably range from about 1:0.3 to about 1:3, e.g., from about 1:0.5 to about 1:2.5, from about 1:0.5 to about 1:1, from about 1:1 to about 1:1.5, from about 1:1.5 to about 1:2, or from about 1:2 to about 1:2.5. In some embodiments, the molar ratio of titanium oxide precursor to solvent ranges from about 1:1 to 1:150, e.g., 1:1 to 1:5, 1:5 to 1:10, 1:10 to 1:15, 1:15 to 1:20, 1:20 to 1:25, 1:25 to 1:30, 1:30 to 1:35, 1:35 to 1:40, 1:40 to 1:45, 1:45 to 1:50, 1:50 to 1:55, 1:55 to 1:60, 1:60 to 1:65, 1:65 to 1:70, 1:70 to 1:75, 1:75 to 1:80, 1:80 to 1:85, 1:85 to 1:90, 1:90 to 1:95, 1:95 to 1:100, 1:100 to 1:150. 2The nanocrystals have an average particle size of greater than 4 nm but less than 50 nm (e.g., from about 10 nm to about 25 nm, or from about 4 nm to about 20 nm), and in such cases the molar ratio of titanium oxide precursor to water can range from about 1:0.3 to about 1:3, e.g., from about 1:0.5 to about 1:2.5, from about 1:0.5 to about 1:1, from about 1:1 to about 1:1.5, from about 1:1.5 to about 1:2, or from about 1:2 to about 1:2.5, preferably less than 1, e.g., less than 0.5, e.g., about 0.1, about 0.2, about 0.3, about 0.4, about 0.45, or from about 0.2 to about 0.5, or from about 0.3 to about 0.45.

[0041] TiO with detailed properties 2 Other suitable conditions and exemplary preparations of the nanocrystals are described herein. For example, in some embodiments, the precursor of titanium oxide is a titanium alkoxide, such as titanium (IV) butoxide. In some embodiments, the solvent can be an alcohol-based solvent, such as benzyl alcohol. Typically, the molar ratio of the precursor of titanium oxide (e.g., titanium (IV) butoxide) to the solvent (e.g., benzyl alcohol) can range from about 0.1:1 to about 50, preferably from about 1:5 to about 1:40, and preferably about 1:30.

[0042] In some embodiments, the TiO 2 Methods for preparing nanocrystals include, for example, Remove the solvent from the TiO 2 Separated from the nanocrystals, wet TiO 2 In some embodiments, the TiO nanocrystals described herein may further include providing nanocrystals. 2 The method for preparing nanocrystals was wet TiO 2 This can further include suspending the nanocrystals in a capping solvent (eg, as described herein, PGMEA, etc.).

[0043] In a further embodiment, the present disclosure provides an at least partially capped TiO 2A nanocrystal dispersion comprising nanocrystals and a solvent, the nanocrystal dispersion comprising at least a partially capped TiO 2 Provided are nanocrystal dispersions in which the nanocrystals are present in an amount greater than 30% by weight in the dispersion, e.g., greater than 40%, greater than 50%, greater than 60% by weight, or greater than 70%, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, or any range between the recited values, e.g., about 40-70%, about 30-80%, about 50-80%, etc. In some embodiments, the TiO of the dispersion is 2 The nanocrystals are at least partially capped with a capping agent such as a silane, an alcohol, a carboxylic acid, a thiol or sulfonate, or a phosphonate or phosphate. In some embodiments, TiO 2 The nanocrystals are at least partially capped with a capping agent as described herein. In some embodiments, the TiO 2 The size of the nanocrystals ranges from 1 to 50 nm, e.g., from 4 to 20 nm, or from 10 to 20 nm. In some embodiments, the at least partially capped TiO 2 The nanocrystals can typically have an organic content of about 5% to about 35%, preferably about 5% to about 15%, or about 10% to about 25%, or about 15% to about 30%, as measured by TGA. In some embodiments, the TiO 2 The nanocrystals were capped in the presence of water. In some embodiments, the at least partially capped TiO 2 The TiO nanocrystals are prepared by any of the methods described herein. 2 In a further embodiment, the at least partially capped TiO nanocrystals in the dispersion are 2The nanocrystals are uniformly dispersed without aggregation or settling of the nanocrystals as observed by TGA. In further embodiments, the dispersion is stable for greater than 2, 3, or 4 weeks and exhibits a change in transmittance at 400 nm of less than 1% (e.g., less than 3%, less than 2%, or less than 1%, e.g., less than 3%, less than 2%, or less than 1%, e.g., about 0.1%, about 0.5%, about 1%, about 2%, about 3%, or any range between the recited values, e.g., about 0.01-1%, about 0.1-1%, about 0.1-5%, about 0.5-2%, about 0.5-3%, about 0.5-1%, etc.) when stored in the dark at room temperature. As used herein, "capped TiO 2 The term "nanocrystals" is used to refer to at least partially capped TiO particles, unless otherwise specified by the context. 2 It is preferable to understand them as "nanocrystals."

[0044] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2 A nanocrystal dispersion comprising nanocrystals and a solvent, the nanocrystal dispersion comprising at least a partially capped TiO 2The nanocrystals are present in the dispersion in an amount greater than 30% by weight, e.g., greater than 40%, greater than 50%, greater than 60%, or greater than 70%, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, or any range between the recited values, e.g., about 40-70%, about 30-80%, about 50-80%, etc., and the nanocrystal dispersion is preferably in an aqueous medium such as benzyl alcohol, butyl carbitol acetate (BCA), butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, tetrahydrofuran, diethyl ether, ... The nanocrystal dispersion comprises a solvent selected from propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol, dipropylene glycol, acetone, propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), ethyl acetate, butyl acetate, diethylene glycol monoethyl ether acetate, and toluene. In the embodiment, the TiO 2 The nanocrystals are at least partially capped with a capping agent such as a silane, an alcohol, a carboxylic acid, a thiol or sulfonate, or a phosphonate or phosphate. In some embodiments, TiO 2 The nanocrystals are at least partially capped with a capping agent as described herein. In some embodiments, TiO 2The nanocrystals are at least partially capped with a capping agent selected from methyltrimethoxysilane, n-octyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, and combinations thereof. In some embodiments, the TiO in the dispersion is at least partially capped with a capping agent selected from methyltrimethoxysilane, n-octyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, and combinations thereof. 2 The average particle size of the nanocrystals ranges from 1 to 50 nm, e.g., from 4 to 20 nm, or from 10 to 20 nm. In some embodiments, the TiO 2 The D9999 of the nanocrystals is <200 nm. In some embodiments, the at least partially capped TiO 2 The nanocrystals can typically have an organic content of about 5% to about 35%, preferably about 5% to about 15%, or about 10% to about 25%, or about 15% to about 30%, as measured by TGA. In some embodiments, the TiO 2 The nanocrystals were capped in the presence of water. In some embodiments, the at least partially capped TiO 2 The TiO nanocrystals are prepared by any of the methods described herein. 2 In a further embodiment, the at least partially capped TiO nanocrystals in the dispersion are 2 The nanocrystals are uniformly dispersed without nanocrystal aggregation or settling as observed by TGA. In further embodiments, the dispersions are stable for greater than 2, 3, or 4 weeks and exhibit a change in transmittance at 400 nm of less than 5% (e.g., less than 3%, less than 2%, or less than 1%, e.g., about 0.1%, about 0.5%, about 1%, about 2%, about 3%, or any range between the recited values, e.g., about 0.01-1%, about 0.1-1%, about 0.1-5%, about 0.5-2%, about 0.5-3%, about 0.5-1%, etc.) when stored in the dark at room temperature.

[0045] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2 A nanocrystal dispersion comprising nanocrystals and a solvent, the nanocrystal dispersion comprising at least a partially capped TiO 2 The nanocrystal dispersion is provided, wherein the nanocrystals are present in an amount of greater than 30% by weight in the dispersion, e.g., greater than 40%, greater than 50%, greater than 60%, or greater than 70%, e.g., about 40, about 50%, about 60%, about 70%, about 80%, or any range between the recited values, e.g., about 40-70%, about 30-80%, about 50-80%, etc., and the nanocrystal dispersion comprises a solvent selected from benzyl alcohol, butyl carbitol acetate (BCA), isopropanol, tetrahydrofuran, propylene glycol monomethyl ether (PGME), dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), ethyl acetate, toluene, and combinations thereof. In some embodiments, the TiO of the dispersion is at least 100% by weight. 2 The nanocrystals are at least partially capped with a capping agent such as a silane, an alcohol, a carboxylic acid, a thiol or sulfonate, or a phosphonate or phosphate. In some embodiments, TiO 2 The nanocrystals are at least partially capped with a capping agent as described herein. In some embodiments, TiO 2 The nanocrystals are at least partially capped with a capping agent selected from methyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and combinations thereof. In some embodiments, the TiO in the dispersion 2 The average particle size of the nanocrystals ranges from 1 to 50 nm, e.g., from 4 to 20 nm, or from 15 to 20 nm. In some embodiments, the TiO 2 Nanocrystalline D99 In some embodiments, the at least partially capped TiO 99 of the present invention is in the range of 20-500 nm as determined by DLS. 2 The nanocrystals can typically have an organic content of about 5% to about 35%, preferably about 5% to about 15%, or about 10% to about 25%, or about 15% to about 30%, as measured by TGA. In some embodiments, the TiO 2 The nanocrystals were capped in the presence of water. In some embodiments, the at least partially capped TiO 2 The TiO nanocrystals are prepared by any of the methods described herein. 2 In a further embodiment, the at least partially capped TiO nanocrystals in the dispersion are 2 The nanocrystals are uniformly dispersed without nanocrystal aggregation or settling as observed by TGA. In further embodiments, the dispersion is stable for more than 2 weeks, e.g., for 3 or 4 weeks, or for more than 3 weeks or more than 4 weeks, and exhibits a change in transmittance at 400 nm of less than 5% (e.g., less than 3%, less than 2%, or less than 1%, e.g., about 0.1%, about 0.5%, about 1%, about 2%, about 3%, or any range between the recited values, e.g., about 0.01-1%, about 0.1-1%, about 0.1-5%, about 0.5-2%, about 0.5-3%, about 0.5-1%, etc.) when stored in the dark at room temperature.

[0046] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2 A nanocrystal dispersion comprising nanocrystals and a solvent, the nanocrystal dispersion comprising at least a partially capped TiO 2The nanocrystal dispersion is provided, wherein the nanocrystals are present in an amount greater than 30% by weight in the formulation, e.g., greater than 40%, greater than 50%, greater than 60%, or greater than 70%, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, or any range between the recited values, e.g., about 40-70%, about 30-80%, about 50-80%, etc., and the nanocrystal dispersion comprises a solvent selected from butyl carbitol acetate (BCA), propylene glycol monomethyl ether (PGME), dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl acetate, and combinations thereof. In some embodiments, the TiO of the dispersion is at least 100% by weight. 2 The nanocrystals are at least partially capped with a capping agent such as a silane, an alcohol, a carboxylic acid, a thiol or sulfonate, or a phosphonate or phosphate. In some embodiments, TiO 2 The nanocrystals are at least partially capped with a capping agent as described herein. In some embodiments, TiO 2 The nanocrystals are at least partially capped with a capping agent selected from methoxy(triethyleneoxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, and combinations thereof. In some embodiments, the TiO in the dispersion 2 The average particle size of the nanocrystals ranges from 1 to 50 nm, e.g., from 4 to 20 nm, or from 15 to 20 nm. In some embodiments, the TiO 2 The D9999 of the nanocrystals is in the range of 20-500 nm, as determined by DLS. In some embodiments, the at least partially capped TiO 2 The nanocrystals can typically have an organic content of about 5% to about 35%, preferably about 5% to about 15%, or about 10% to about 25%, or about 15% to about 30%, as measured by TGA. In some embodiments, the TiO 2The nanocrystals were capped in the presence of water. In some embodiments, the at least partially capped TiO 2 The TiO nanocrystals are prepared by any of the methods described herein. 2 In a further embodiment, the at least partially capped TiO nanocrystals in the dispersion are 2 The nanocrystals are uniformly dispersed without nanocrystal aggregation or settling as observed by TGA. In further embodiments, the dispersion is stable for more than 2 weeks, e.g., for 3 or 4 weeks, or for more than 3 weeks or more than 4 weeks, and has a 400 nm dispersibility of less than 5% (e.g., less than 3%, less than 2%, or less than 1%, e.g., about 0.1%, about 0.5%, about 1%, about 2%, about 3%, or any range between the recited values, e.g., about 0.01-1%, about 0.1-1%, about 0.1-5%, about 0.5-2%, about 0.5-3%, about 0.5-1%, etc.) when stored in the dark at room temperature. The change in transmittance at

[0047] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2 A nanocrystal dispersion comprising nanocrystals and a dispersing agent (e.g., a nonionic dispersing agent, an anionic dispersing agent, or a combination thereof), the nanocrystal dispersion comprising at least a partially capped TiO 2 Provided is a nanocrystal dispersion, wherein the nanocrystals are present in an amount by weight in the dispersion greater than 30%, e.g., greater than 40%, or greater than 50%, greater than 60%, or greater than 70%, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, or any range between the recited values, e.g., about 40-70%, about 30-80%, about 50-80%, etc., and the nanocrystal dispersion comprises a dispersing agent of propylene glycol methyl ether acetate (PGMEA). In some embodiments, the TiO of the dispersion is 2 The nanocrystals are at least partially capped with a capping agent such as a silane, an alcohol, a carboxylic acid, a thiol or sulfonate, or a phosphonate or phosphate. In some embodiments, TiO 2The nanocrystals are at least partially capped with a capping agent as described herein. In some embodiments, TiO 2 The nanocrystals are at least partially capped with a capping agent, methoxy(triethyleneoxy)propyltrimethoxysilane. In some embodiments, the TiO in the dispersion 2 The average particle size of the nanocrystals is in the range of 1 to 50 nm, for example 4 to 20 nm, or 15 to 20 nm, and preferably the TiO 2 The D9999 of the nanocrystals is in the range of 20-500 nm, e.g., D9999 is <200 nm, as determined by DLS. In some embodiments, the at least partially capped TiO 2 The nanocrystals can typically have an organic content of about 5% to about 35%, preferably about 5% to about 15%, or about 10% to about 25%, or about 15% to about 30%, as measured by TGA. In some embodiments, the TiO 2 The nanocrystals were capped in the presence of water. In some embodiments, the at least partially capped TiO 2 The TiO nanocrystals are prepared by any of the methods described herein. 2 In a further embodiment, the at least partially capped TiO nanocrystals in the dispersion are 2 The nanocrystals are uniformly dispersed without aggregation or settling of the nanocrystals as observed by TGA. In further embodiments, the dispersions are stable for greater than 2, 3, or 4 weeks and exhibit less than 1% change in transmittance at 400 nm when stored in the dark at room temperature.

[0048] In some embodiments, the nanocomposite formulations herein comprise at least a partially capped TiO 2 In some embodiments, the TiO 2 The nanocrystal nanocomposite formulation comprises preparing at least a partially capped TiO in the presence of at least one solvent. 2The nanocrystals may be suspended in at least one monomer, polymer, and / or oligomer. As used herein, the term "monomer, polymer, and / or oligomer" or similar expressions should be understood to include the recited monomer, its oligomer, its polymer, or any mixture thereof. In some embodiments, the TiO 2 The nanocrystal nanocomposite formulation may further comprise at least one hardening agent. In some embodiments, the TiO 2 The nanocrystal nanocomposite formulation may further comprise at least one adhesion promoter. In some embodiments, the TiO 2 The nanocrystal nanocomposite formulation may further comprise at least one wetting agent. In some embodiments, the TiO 2 The nanocrystal nanocomposite formulation may further comprise at least one leveling agent. In some embodiments, the TiO 2 The nanocrystal nanocomposite formulation may further comprise at least one dispersing agent. In some embodiments, the TiO 2 The nanocrystal nanocomposite formulation may further comprise at least one leveling agent. In some embodiments, the TiO 2 The nanocrystal nanocomposite formulation may further comprise at least one antioxidant. In some embodiments, the TiO 2 The nanocrystalline nanocomposite formulation may further comprise at least one scatterer particle.

[0049] In a further embodiment, the present disclosure provides a method for preparing an at least partially capped TiO film in the presence of a solvent. 2 A nanocomposite formulation comprising nanocrystals and at least one monomer, polymer and / or oligomer, the nanocomposite formulation comprising at least a partially capped TiO 2Provided are nanocomposite formulations in which the nanocrystals are present in an amount greater than 30% by weight relative to the monomers and / or oligomers described herein, e.g., greater than 40%, greater than 50%, greater than 60%, greater than 70%, greater than 80%, or greater than 90%, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, about 90%, or any range between the recited values, e.g., about 50-90%, about 40-80%, about 60-90%, etc. In some embodiments, the TiO of the formulation is 2 The nanocrystals are at least partially capped with a capping agent such as a silane, an alcohol, a carboxylic acid, a thiol or sulfonate, or a phosphonate or phosphate. 2 The nanocrystals may be capped in the presence of water. In some embodiments, TiO 2 The nanocrystals are at least partially capped with a capping agent as described herein. In some embodiments, the TiO 2 The average particle size of the nanocrystals ranges from 1 to 50 nm, e.g., from 4 to 20 nm, or from 10 to 20 nm. In some embodiments, the TiO 2 The D9999 of the nanocrystals is in the range of 20-500 nm, as determined by DLS. In some embodiments, the at least partially capped TiO 2 The nanocrystals can typically have an organic content of about 5% to about 35%, preferably about 5% to about 15%, or about 10% to about 25%, or about 15% to about 30%, as measured by TGA. In further embodiments, the at least partially capped TiO in the formulation 2The nanocrystals are uniformly dispersed without nanocrystal aggregation or settling as observed by TGA. In further embodiments, the formulations are stable for greater than 2, 3, or 4 weeks and exhibit a change in transmittance at 400 nm of less than 5% (e.g., less than 3%, less than 2%, or less than 1%, e.g., about 0.1%, about 0.5%, about 1%, about 2%, about 3%, or any range between the recited values, e.g., about 0.01-1%, about 0.1-1%, about 0.1-5%, about 0.5-2%, about 0.5-3%, about 0.5-1%, etc.) when stored in the dark at room temperature. In further embodiments, the TiO 2 The nanocrystalline nanocomposite formulations can have a tunable viscosity ranging from about 1 cP to about 1000 cP, e.g., from about 1 cP to 2 cP, from about 2 cP to 5 cP, from about 5 cP to 10 cP, from about 10 cP to 15 cP, from about 15 cP to 20 cP, from about 20 cP to 25 cP, from about 25 cP to 30 cP, from about 30 cP to 40 cP, from about 40 cP to 50 cP, from about 50 cP to 60 cP, from about 60 cP to 75 cP, from about 75 cP to 100 cP, from about 100 cP to 200 cP, from about 200 cP to 500 cP, or from 500 cP to 1,000 cP, as measured at 25° C. using a Brookfield RVDV II+ cone and plate viscometer. 2 The nanocomposite formulations are deposited on glass or plastic surfaces by spin coating, inkjet printing, nanoimprinting, photopatterning, imprinting, roll-to-roll coating, slot-die coating, and / or screen printing.

[0050] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2Nanocomposite formulations comprising nanocrystals and at least one monomer, polymer, and / or oligomer, the monomer, oligomer, and / or polymer being, for example, bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), bisphenol A ethoxylate diacrylates, bisphenol A propoxylate diacrylate, bisphenol F ethoxylate (2 EO / phenol) diacrylate, bisphenol A glycerolate diacrylates, bisphenol A ethoxylate dimethacrylate, ethoxylated (4) bisphenol A diacrylate. In one embodiment, the nanocomposite formulation is selected from the group consisting of dimethyl ether diacrylate (DMEA), ... In a further embodiment, the at least partially capped TiO 2The nanocrystals are present in an amount of greater than 30% by weight, e.g., greater than 40%, greater than 50%, greater than 60%, greater than 70%, greater than 80%, or greater than 90%, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, about 90%, or any range between the recited values, e.g., about 50-90%, about 40-80%, about 60-90%, etc., relative to the monomer and / or oligomer in the presence of a solvent, and the solvent is selected from the group consisting of benzyl alcohol, butyl carbitol acetate (BCA), butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, , methanol, tetrahydrofuran, diethyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol, dipropylene glycol, acetone, propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), ethyl acetate, butyl acetate, diethylene glycol monoethyl ether acetate, toluene, and combinations thereof. In some embodiments, the TiO 2 The nanocrystals are at least partially capped with a capping agent selected from methyltrimethoxysilane, n-octyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, and combinations thereof. In some embodiments, the TiO in the formulation is at least partially capped with a capping agent selected from methyltrimethoxysilane, n-octyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, and combinations thereof. 2 The average particle size of the nanocrystals ranges from 1 to 50 nm, e.g., from 4 to 20 nm, or from 10 to 20 nm. In some embodiments, the TiO 2The D9999 of the nanocrystals is in the range of 20-500 nm, as determined by DLS. In some embodiments, the at least partially capped TiO 2 The nanocrystals can typically have an organic content of about 5% to about 35%, preferably about 5% to about 15%, or about 10% to about 25%, or about 15% to about 30%, as measured by TGA. In some embodiments, the TiO 2 The nanocrystals may be capped in the presence of water. In some embodiments, the at least partially capped TiO 2 The TiO nanocrystals are prepared by any of the methods described herein. 2 In a further embodiment, the formulation is derived from at least partially capped TiO nanocrystals. 2 The nanocrystals are uniformly dispersed without aggregation or settling of the nanocrystals as observed by TGA. In further embodiments, the dispersion is stable for more than 2, 3, or 4 weeks and exhibits a change in transmittance at 400 nm of less than 5% (e.g., less than 3%, less than 2%, or less than 1%, e.g., about 0.1%, about 0.5%, about 1%, about 2%, about 3%, or any range between the recited values, e.g., about 0.01-1%, about 0.1-1%, about 0.1-5%, about 0.5-2%, about 0.5-3%, about 0.5-1%, etc.) when stored in the dark at room temperature. In further embodiments, the TiO 2 The nanocrystalline nanocomposite formulation exhibited a viscosity of approximately 1 cP to 1 MPa when measured at 25°C using a Brookfield RVDV II+ cone-plate viscometer. The TiO 200 may have a tunable viscosity in the range of 2 cP, about 2 cP to 5 cP, about 5 cP to 10 cP, about 10 cP to 15 cP, about 15 cP to 20 cP, about 20 cP to 25 cP, about 25 cP to 30 cP, about 30 cP to 40 cP, about 40 cP to 50 cP, about 50 cP to 60 cP, about 60 cP to 75 cP, about 75 cP to 100 cP, about 100 cP to 200 cP, about 200 cP to 500 cP, or 500 cP to 1,000 cP. 2The nanocomposite formulations are deposited on glass or plastic surfaces by spin coating, inkjet printing, nanoimprinting, photopatterning, imprinting, roll-to-roll coating, slot-die coating, and / or screen printing.

[0051] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2 A nanocomposite formulation is provided comprising nanocrystals and at least one monomer, polymer, and / or oligomer, the monomer, polymer, and / or oligomer being selected from bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), bisphenol A ethoxylate diacrylates, bisphenol A propoxylate diacrylate, bisphenol F ethoxylate (2 EO / phenol) diacrylate, bisphenol A glycerolate diacrylates, bisphenol A ethoxylate dimethacrylate, ethoxylated (4) bisphenol A diacrylate (SR-601), biphenol A ethoxylate diacrylate (SR-349), cresol novolac epoxy acrylate (CN112C60), and combinations thereof. In a further embodiment, the at least partially capped TiO 2The nanocrystals are present in an amount of greater than 30% by weight, e.g., greater than 40%, greater than 50%, greater than 60%, greater than 70%, greater than 80%, or greater than 90%, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, about 90%, or any range between the recited values, e.g., about 50-90%, about 40-80%, about 60-90%, etc., relative to the monomers and / or oligomers in the presence of a solvent, and the solvent is selected from benzyl alcohol, butyl carbitol acetate (BCA), propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), ethyl acetate, toluene, and combinations thereof. In some embodiments, the TiO 2 The nanocrystals are at least partially capped with a capping agent selected from methoxy(triethylneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and combinations thereof. In some embodiments, the TiO in the formulation 2 The average particle size of the nanocrystals ranges from 1 to 50 nm, e.g., from 4 to 20 nm, or from 10 to 20 nm. In some embodiments, the TiO 2 The D9999 of the nanocrystals is in the range of 20-500 nm, as determined by DLS. In some embodiments, the at least partially capped TiO 2 The nanocrystals can typically have an organic content of about 5% to about 35%, preferably about 5% to about 15%, or about 10% to about 25%, or about 15% to about 30%, as measured by TGA. In some embodiments, the TiO 2 The nanocrystals may be capped in the presence of water. In some embodiments, the at least partially capped TiO 2The TiO nanocrystals are prepared by any of the methods described herein. 2 In a further embodiment, the formulation is derived from at least partially capped TiO nanocrystals. 2 The nanocrystals are uniformly dispersed without aggregation or settling of the nanocrystals as observed by TGA. In further embodiments, the dispersion is stable for greater than 2, 3, or 4 weeks and has less than 5% (e.g., less than 3%, less than 2%, or less than 1%, e.g., about 0.1%, about 0.5%, about 1%, about 2%, about 3%, or any value in between the recited values) of nanocrystals when stored in the dark at room temperature. In further embodiments, the TiO 2 The nanocrystalline nanocomposite formulations can have a tunable viscosity in the range of about 1 cP to 2 cP, about 2 cP to 5 cP, about 5 cP to 10 cP, about 10 cP to 15 cP, about 15 cP to 20 cP, about 20 cP to 25 cP, about 25 cP to 30 cP, about 30 cP to 40 cP, about 40 cP to 50 cP, about 50 cP to 60 cP, about 60 cP to 75 cP, about 75 cP to 100 cP, about 100 cP to 200 cP, about 200 cP to 500 cP, or 500 cP to 1,000 cP, as measured at 25° C. using a Brookfield RVDV II+ cone and plate viscometer. 2 The nanocomposite formulations are deposited on glass or plastic surfaces by spin coating, inkjet printing, imprinting, nanoimprinting, photopatterning, roll-to-roll coating, slot-die coating, and / or screen printing.

[0052] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2 A nanocomposite formulation is provided comprising nanocrystals and at least one monomer, polymer, and / or oligomer of bisphenol A glycerolate dimethacrylate. In a further embodiment, the at least partially capped TiO 2The nanocrystals are present in an amount of greater than 30%, e.g., greater than 40%, greater than 50%, greater than 60%, greater than 70%, greater than 80%, or greater than 90%, by weight relative to the monomers and / or oligomers, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, about 90%, or any range between the recited values, e.g., about 50-90%, about 40-80%, about 60-90%, etc., in the presence of a solvent, and the solvent is selected from dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), and combinations thereof. In some embodiments, the TiO 2 The nanocrystals are at least partially capped with a capping agent, methoxy(triethyleneoxy)propyltrimethoxysilane. In some embodiments, the TiO in the formulation 2 The average particle size of the nanocrystals ranges from 1 to 50 nm, e.g., from 4 to 20 nm, or from 10 to 20 nm. In some embodiments, the TiO 2 The D9999 of the nanocrystals is in the range of 20-500 nm, as determined by DLS. In some embodiments, the at least partially capped TiO 2 The nanocrystals can typically have an organic content of about 5% to about 35%, preferably about 5% to about 15%, or about 10% to about 25%, or about 15% to about 30%, as measured by TGA. In some embodiments, the TiO 2 The nanocrystals may be capped in the presence of water. In some embodiments, the at least partially capped TiO 2 The TiO nanocrystals are prepared by any of the methods described herein. 2 In a further embodiment, the formulation is derived from at least partially capped TiO nanocrystals. 2The nanocrystals are uniformly dispersed without aggregation or settling of the nanocrystals as observed by TGA. In further embodiments, the dispersion is stable for more than 2, 3, or 4 weeks and exhibits a change in transmittance at 400 nm of less than 5% (e.g., less than 3%, less than 2%, or less than 1%, e.g., about 0.1%, about 0.5%, about 1%, about 2%, about 3%, or any range between the recited values, e.g., about 0.01-1%, about 0.1-1%, about 0.1-5%, about 0.5-2%, about 0.5-3%, about 0.5-1%, etc.) when stored in the dark at room temperature. In further embodiments, the TiO 2 The nanocrystalline nanocomposite formulations can have a tunable viscosity in the range of about 1 cP to 2 cP, about 2 cP to 5 cP, about 5 cP to 10 cP, about 10 cP to 15 cP, about 15 cP to 20 cP, about 20 cP to 25 cP, about 25 cP to 30 cP, about 30 cP to 40 cP, about 40 cP to 50 cP, about 50 cP to 60 cP, about 60 cP to 75 cP, about 75 cP to 100 cP, about 100 cP to 200 cP, about 200 cP to 500 cP, or 500 cP to 1,000 cP, as measured at 25° C. using a Brookfield RVDV II+ cone and plate viscometer. 2 Na The nanocomposite formulations are applied to glass or plastic surfaces by spin coating, inkjet printing, imprinting, nanoimprinting, photopatterning, roll-to-roll coating, slot-die coating, and / or screen printing.

[0053] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2A nanocomposite formulation is provided comprising nanocrystals and at least one monomer, polymer, and / or oligomer, the monomer, polymer, and / or oligomer being selected from bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), bisphenol A ethoxylate diacrylates, bisphenol A propoxylate diacrylate, bisphenol F ethoxylate (2 EO / phenol) diacrylate, bisphenol A glycerolate diacrylates, bisphenol A ethoxylate dimethacrylate, ethoxylated (4) bisphenol A diacrylate (SR-601), biphenol A ethoxylate diacrylate (SR-349), cresol novolac epoxy acrylate (CN112C60). In a further embodiment, the at least partially capped TiO 2 The nanocrystals are present in an amount of greater than 30% by weight, e.g., greater than 40%, greater than 50%, greater than 60%, greater than 70%, greater than 80%, or greater than 90%, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, about 90%, or any range between the recited values, e.g., about 50-90%, about 40-80%, about 60-90%, etc., relative to the monomers and / or oligomers in the presence of a solvent, and the solvent is selected from benzyl alcohol, butyl carbitol acetate (BCA), propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), ethyl acetate, toluene, and combinations thereof. In some embodiments, the TiO 2The nanocrystals are at least partially capped with a capping agent selected from methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and combinations thereof. In some embodiments, the TiO 2 in the formulation 2 The average particle size of the nanocrystals ranges from 1 to 50 nm, e.g., from 4 to 20 nm, or from 10 to 20 nm. In some embodiments, the TiO 2 The D9999 of the nanocrystals is in the range of 20-500 nm, as determined by DLS. In some embodiments, the at least partially capped TiO 2 The nanocrystals can typically have an organic content of about 5% to about 35%, preferably about 5% to about 15%, or about 10% to about 25%, or about 15% to about 30%, as measured by TGA. In some embodiments, the TiO 2 The nanocrystals may be capped in the presence of water. In some embodiments, the at least partially capped TiO 2 The TiO nanocrystals are prepared by any of the methods described herein. 2 In a further embodiment, the TiO 2The nanocrystal nanocomposite formulation may further include at least one curing agent, and the curing agent may be Ebecryl Pl 15, Ebecryl P39, benzophenone, Speed ​​Cure BEM, 4,4'-bis(diethylamino)benzophenone, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, Irgacure 184, 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), ethyl(2,4,6-trimethylbenzoyl)phenylphosphinate, 4-(dimethylamino)benzophenone, 2-isopropyl toxanthone, Darocur 4265, Speed ​​Cure Xkm, methyl benzoyl formate, thioxanthen-9-one, dicumyl peroxide, t-butyl perbenzoate, benzoyl peroxide, t-butyl peracetate, 1,1-di(t-butylperoxy)3,3,5- trimethylcyclohexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne, 2,2'-azobisisobutyronitrile, and combinations thereof.

[0054] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2 A nanocomposite formulation is provided comprising nanocrystals and at least one monomer, polymer, and / or oligomer, the monomer, polymer, and / or oligomer being selected from bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), ethoxylated (4) bisphenol A diacrylate (SR-601), biphenol A ethoxylate diacrylate (SR-349), cresol novolac epoxy acrylate (CN112C60). In a further embodiment, the at least partially capped TiO 2The nanocrystals are present in an amount of greater than 30% by weight, e.g., greater than 40%, greater than 50%, greater than 60%, greater than 70%, greater than 80%, or greater than 90%, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, about 90%, or any range between the recited values, e.g., about 50-90%, about 40-80%, about 60-90%, etc., relative to the monomers and / or oligomers in the presence of a solvent, and the solvent is selected from benzyl alcohol, butyl carbitol acetate (BCA), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl acetate, and combinations thereof. In some embodiments, the TiO 2 The nanocrystals are at least partially capped with a capping agent selected from methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and combinations thereof. In some embodiments, the TiO 2 in the formulation 2 The average particle size of the nanocrystals ranges from 1 to 50 nm, e.g., from 4 to 20 nm, or from 10 to 20 nm. In some embodiments, the TiO 2 The D9999 of the nanocrystals is in the range of 20-500 nm, as determined by DLS. In some embodiments, the at least partially capped TiO 2 The nanocrystals can typically have an organic content of about 5% to about 35%, preferably about 5% to about 15%, or about 10% to about 25%, or about 15% to about 30%, as measured by TGA. In some embodiments, the at least partially capped TiO 2 The TiO nanocrystals are prepared by any of the methods described herein. 2 In a further embodiment, the TiO 2The nanocrystal nanocomposite formulation may further comprise at least one hardening agent, the hardening agent being selected from Ebecryl® Pl 15, Ebecryl® P39, benzophenone, diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide, Irgacure® 184, benzoyl peroxoside, 2,2'-azobisisobutyronitrile, and combinations thereof. In further embodiments, the TiO 2 of the present invention may be used in combination with any of the above-mentioned compositions. 2 The nanocrystal nanocomposite formulation further comprises at least one adhesion promoter selected from 3-aminopropyltriethoxysilane, 3-[(methacryloyloxy)propyl]trimethoxysilane, ureidopropyltrimethoxysilane, trimethoxy[3-(methylamino)propyl]silane, CN820, CN146, and combinations thereof.

[0055] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2 A nanocomposite formulation comprising nanocrystals and at least one monomer, polymer, and / or oligomer, the monomer, polymer, and / or oligomer being selected from the group consisting of bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), ethoxylated (4) bisphenol A diacrylate (SR-601), biphenol A ethoxylate diacrylate (SR-349), cresol novolac epoxy a In a further embodiment, the at least partially capped TiO 2The nanocrystals are present in an amount of greater than 30% by weight, e.g., greater than 40%, greater than 50%, greater than 60%, greater than 70%, greater than 80%, or greater than 90%, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, about 90%, or any range between the recited values, e.g., about 50-90%, about 40-80%, about 60-90%, etc., relative to the monomers and / or oligomers in the presence of a solvent, and the solvent is selected from benzyl alcohol, butyl carbitol acetate (BCA), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl acetate, and combinations thereof. In some embodiments, the TiO 2 The nanocrystals are at least partially capped with a capping agent selected from methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and combinations thereof. In some embodiments, the TiO 2 in the formulation 2 The average particle size of the nanocrystals ranges from 1 to 50 nm, e.g., from 4 to 20 nm, or from 10 to 20 nm. In some embodiments, the TiO 2 The D9999 of the nanocrystals is in the range of 20-500 nm, as determined by DLS. In some embodiments, the at least partially capped TiO 2 The nanocrystals can typically have an organic content of about 5% to about 35%, preferably about 5% to about 15%, or about 10% to about 25%, or about 15% to about 30%, as measured by TGA. In some embodiments, the at least partially capped TiO 2 The TiO nanocrystals are prepared by any of the methods described herein. 2 In a further embodiment, the TiO 2The nanocrystal nanocomposite formulation may further comprise at least one hardening agent, the hardening agent being selected from Ebecryl® Pl 15, Ebecryl® P39, benzophenone, diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide, Irgacure® 184, benzoyl peroxoside, 2,2'-azobisisobutyronitrile, and combinations thereof. In further embodiments, the TiO 2 of the present invention may be used in combination with any of the above-mentioned compositions. 2 The nanocrystal nanocomposite formulation further comprises at least one adhesion promoter selected from 3-aminopropyltriethoxysilane, 3-[(methacryloyloxy)propyl]trimethoxysilane, ureidopropyltrimethoxysilane, trimethoxy[3-(methylamino)propyl]silane, CN820, CN146, and combinations thereof. In some embodiments, the TiO 2 The nanocrystalline nanocomposite formulation may further comprise at least one wetting agent selected from BYK-307, BYK-330, Novec 4430, Novec 4432, Novec 4434, and combinations thereof. In some embodiments, the TiO 2 The nanocrystal nanocomposite formulation may further comprise at least one leveling agent selected from BYK-352, BYK-353, BYK-356, BYK-361N, BYK-322, BYK-323, BYK-350, and combinations thereof. In some embodiments, the TiO 2Nanocrystal nanocomposite formulations include DisperBYK-101, DisperBYK-130, DisperBYK-140, DisperBYK-160, DisperBYK-161, DisperBYK-162, DisperBYK-163, DisperBYK-164, DisperBYK-165, DisperBYK-166, DisperBYK-170, DisperBYK-171, DisperBYK-182, DisperBYK-183, DisperBYK-184, DisperBYK-185, DisperBYK-186, DisperBYK-187, DisperBYK-188, DisperBYK-189, DisperBYK-200, DisperBYK-201, DisperBYK-202, DisperBYK-203, DisperBYK-204, DisperBYK-205, DisperBYK-206, DisperBYK-207, DisperBYK-208, DisperBYK-209, DisperBYK-300, DisperBYK-310, DisperBYK-311, DisperBYK-312, DisperBYK-313, DisperBYK-314, DisperBYK-315, DisperBYK-316, DisperBYK-317, DisperBYK-318, DisperBYK-319, DisperBYK-320, DisperBYK-321, DisperBYK-322, DisperBYK-323, DisperBYK-324, DisperBYK-325, DisperBYK-326, DisperBYK-327, DisperBYK-328, DisperBYK-329, DisperBYK-401, DisperBYK-410, DisperBYK-421, DisperBYK-422, DisperBYK-42 It may further comprise at least one dispersant selected from Spar BYK-2000, Dispar BYK-2001, Solsperse 32000, Solsperse 36000, Solsperse 28000, Solsperse 20000, Solsperse 41000, and Solsperse 45000, FC-4430, FC-4432, FC-4434 (3M), Capstone FS-3100, and combinations thereof.

[0056] In some embodiments, the TiO 2 The nanocrystalline nanocomposite formulation may further comprise at least one antioxidant selected from Irganox 1010, Irganox 1076, Songnox® 1076, Songnox® 2450, Songnox® 1680, Irgafos 168, Songlite® 6220. In some embodiments, the TiO 2 Nanocrystalline nanocomposite formulations consist of titania particles, polymer beads, silica particles, or ZrO 2 In a further embodiment, the TiO 2 The nanocrystalline nanocomposite formulation may include at least one scatterer particle in the range of 50-100 nm, or 100-200 nm, or 200-300 nm, or 300-400 nm, or 400-500 nm, or 500-600 nm, or 600-700 nm, or 700-800 nm, or 800-900 nm, or 900 nm to 1 μm, or 1-1.5 μm, or 1.5-2 μm. 2The nanocrystalline nanocomposite formulation may comprise at least one scatterer particle in an amount of 0.1-40% by weight, based on the total weight of the formulation. 2 The nanocrystalline nanocomposite formulation can include at least one scatterer particle, and the formulation can have a viscosity of less than 5 cPs, or between 5 cPs and 50 cPs, or between 50 cPs and 200 cPs, or between 200 cPs and 400 cPs, or between 400 cPs and 650 cPs, or between 650 cPs and 1000 cPs, as measured at 25° C. using a Brookfield RVDV II+ cone and plate viscometer.

[0057] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2A nanocomposite film comprising nanocrystals and at least one monomer, polymer, and / or oligomer, wherein the % transmission of the 1 micron film at wavelengths of 400 nm or greater is greater than 80%, e.g., greater than 85%, greater than 90%, greater than 95%, greater than 97%, greater than 98%, or greater than 99%, e.g., about 85%, about 90%, about 95%, about 97%, about 98%, about 99%, about 99.5%, or any range between the recited values. , e.g., 90-99%, and the nanocomposite film has a .alpha.-to-.alpha.-opaqueness at 448 nm, as measured by a prism coupler for films <5 um thick, of about 1.70 to about 2.10, e.g., 1.70-1.72, or 1.72-1.74, or 1.74-1.76, or 1.76-1.78, or 1.78-1.80, or 1.80-1.82, or 1.82-1.84, or 1.84-1.86, or 1.86-1.88, or 1.88-1.90, or 1.9 ... The refractive index may be from about 1.70 to about 2.10 at 635 nm, e.g., from 1.70 to 1.72, or from 1.72 to 1.94, or from 1.94 to 1.96, or from 1.96 to 1.98, or from 1.98 to 2.00, or from 2.00 to 2.02, or from 2.02 to 2.04, or from 2.04 to 2.06, or from 2.06 to 2.08, or from 2.08 to 2.10. or 1.80, or 1.80 to 1.82, or 1.82 to 1.84, or 1.84 to 1.86, or 1.86 to 1.88, or 1.88 to 1.90, or 1.90 to 1.92, or 1.92 to 1.94, or 1.94 to 1.96, or 1.96 to 1.98, or 1.98 to 2.00, or 2.00 to 2.02, or 2.02 to 2.04, or 2.04 to 2.06, or 2.06 to 2.08, or 2.08 to 2.10; 2The nanocrystals are at least partially capped with a capping agent, the capping agent being selected from the group consisting of methyltrimethoxysilane, n-octyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 2-[2-( 2-Methoxyethoxy)ethoxy]acetic acid, oleic acid, and combinations thereof, as measured by DLS as a 5% nanocrystal dispersion in PGMEA, exhibiting TiO 2 The nanocomposite film has an average particle size of the nanocrystals in the range of 1-5 nm, 5-10 nm, 10-15 nm, 15-20 nm, 20-30 nm, 30-40 nm, or 40-50 nm, and preferably has a D9999 of less than 100 nm.

[0058] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2A nanocomposite film comprising nanocrystals and at least one monomer, polymer, and / or oligomer, wherein the percent transmittance of the 1 micron film at wavelengths of 400 nm or greater is greater than 80%, e.g., greater than 785%, greater than 90%, greater than 95%, greater than 97%, greater than 98%, or greater than 99%, e.g., about 85%, about 90%, about 95%, about 97%, about 98%, about 99%, about 99.5%, or any value in between as recited. and the nanocomposite film has a .DELTA. of about 1.70 to about 2.10, e.g., 1.70 to 1.72, or 1.72 to 1.74, or 1.74 to 1.76, or 1.76 to 1.78, or 1.78 to 1.80, or 1.80 to 1.82, or 1.82 to 1.84, or 1.84 to 1.86, or 1.86 to 1.88, or 1.88 to 1.90, at 448 nm, as measured by a prism coupler for films <5 um thick. , or 1.90 to 1.92, or 1.92 to 1.94, or 1.94 to 1.96, or 1.96 to 1.98, or 1.98 to 2.00, or 2.00 to 2.02, or 2.02 to 2.04, or 2.04 to 2.06, or 2.06 to 2.08, or 2.08 to 2.10, and may have a refractive index of about 1.70 to about 2.10 at 635 nm, e.g., 1.70 to 1.72, or 1.72 to 1.74, or 1.74 to 1.76, or 1.76 to 1.78, or 1.78-1.80, or 1.80-1.82, or 1.82-1.84, or 1.84-1.86, or 1.86-1.88, or 1.88-1.90, or 1.90-1.92, or 1.92-1.94, or 1.94-1.96, or 1.96-1.98, or 1.98-2.00, or 2.00-2.02, or 2.02-2.04, or 2.04-2.06, or 2.06-2.08, or 2.08-2.10, and the nanocomposite film has a hardness, as measured by nanoindentation, of greater than 50 MPa, e.g., greater than 100 MPa, greater than 200 MPa, greater than 300 MPa, or greater than 400 MPa, e.g., about 55 MPa, about 100 MPa, about 200 MPa, about 300 MPa, about 400 MPa, about 500 MPa, or any range between the recited values, e.g., about 50-500 MPa, or about 100-400 MPa.

[0059] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2 A nanocomposite film comprising nanocrystals and at least one monomer, polymer, and / or oligomer, wherein the % transmission of the 1 micron film is greater than 80%, e.g., greater than 85%, greater than 90%, greater than 95%, greater than 97%, greater than 98%, or greater than 99%, e.g., about 85%, about 90%, about 95%, about 97%, about 98%, about 99%, about 99.5%, or any range between the recited values, e.g., 90-99%, at wavelengths of 400 nm or greater, and the nanocomposite film has a % transmission of about 1.70 to 1.80% at 448 nm, as measured by a prism coupler for a <5 um thick film. The optical fiber may have a refractive index of about 2.10, for example, 1.70 to 1.72, or 1.72 to 1.74, or 1.74 to 1.76, or 1.76 to 1.78, or 1.78 to 1.80, or 1.80 to 1.82, or 1.82 to 1.84, or 1.84 to 1.86, or 1.86 to 1.88, or 1.88 to 1.90, or 1.90 to 1.92, or 1.92 to 1.94, or 1.94 to 1.96, or 1.96 to 1.98, or 1.98 to 2.00, or 2.00 to 2.02, or 2.02 to 2.04, or 2.04 to 2.06, or 2.06 to 2.08, or 2.08 to 2.10. The optically active material may have a refractive index, at 1.70 to 2.10, e.g., from 1.70 to 1.72, or from 1.72 to 1.74, or from 1.74 to 1.76, or from 1.76 to 1.78, or from 1.78 to 1.80, or from 1.80 to 1.82, or from 1.82 to 1.84, or from 1.84 to 1.86, or from 1.86 to 1.88, or from 1.88 to 1.90, or from 1.90 to 1.92, or from 1.92 to 1.94, or from 1.94 to 1.96, or from 1.96 to 1.98, or from 1.98 to 2.00, or from 2.00 to 2.02, or from 2.02 to 2.04, or from 2.04 to 2.06, or from 2.06 to 2.08, or from 2.08 to 2.10. The nanocomposite film has a hardness, as measured by nanoindentation, of greater than 50 MPa, e.g., greater than 100 MPa, greater than 200 MPa, greater than 300 MPa, or greater than 400 MPa, e.g., about 55 MPa, about 100 MPa, about 200 MPa, about 300 MPa, about 400 MPa, about 500 MPa, or any range between the recited values, e.g., about 50-500 MPa, or about 100-400 MPa, and a % absorbance of 1 micron of the film, as measured by integrating sphere, at a wavelength of 450 nm, of less than 0.1%, less than 0.05%, or less than 0.01%.

[0060] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2A nanocomposite film comprising nanocrystals and at least one monomer, polymer, and / or oligomer, wherein the percent transmittance of the 1 micron film at wavelengths of 400 nm or greater is greater than 80%, e.g., greater than 85%, greater than 90%, greater than 95%, greater than 97%, greater than 98%, or greater than 99%, e.g., about 85%, about 90%, about 95%, about 97%, about 98%, about 99%, about 99.5%, or any range between the recited values, e.g., about 90-99%, and wherein the nanocomposite film and the zigzag film has a zigzag of about 1.70 to about 2.10 at 448 nm, e.g., 1.70-1.72, or 1.72-1.74, or 1.74-1.76, or 1.76-1.78, or 1.78-1.80, or 1.80-1.82, or 1.82-1.84, or 1.84-1.86, or 1.86-1.88, or 1.88-1.90, or 1.90-1.92, or 1.92-1.94, or 1.94-1.96, or 1.96 and may have a refractive index of about 1.70 to about 2.10 at 635 nm, e.g., 1.70 to 1.72, or 1.72 to 1.74, or 1.74 to 1.76, or 1.76 to 1.78, or 1.78 to 1.80, or 1.80 to 1.82, or 1.82 to 1.84, or 1.84 to 1.86, or 1.86 to 1.88; or 1.88 to 1.90, or 1.90 to 1.92, or 1.92 to 1.94, or 1.94 to 1.96, or 1.96 to 1.98, or 1.98 to 2.00, or 2.00 to 2.02, or 2.02 to 2.04, or 2.04 to 2.06, or 2.06 to 2.08, or 2.08 to 2.10, wherein the nanocomposite film has a surface roughness of less than 1 nm as measured by AFM over a 5 micron by 5 micron area.

[0061] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2 A nanocomposite film comprising nanocrystals and at least one monomer, polymer, and / or oligomer, wherein the capped nanocrystals are present in an amount greater than 50% by weight of the nanocomposite (e.g., about 55%, about 60%, about 70%, about 80%, about 90%, or any range between the recited values, e.g., about 55-90%, about 60-90%, about 70-90%), greater than 60% by weight of the nanocomposite, greater than 70% by weight of the nanocomposite, greater than 80% by weight of the nanocomposite, or greater than 90% by weight of the nanocomposite, and the capped nanocrystals are present in an amount greater than 50% by weight of the nanocomposite (e.g., about 55%, about 60%, about 70%, about 80% by weight of the nanocomposite, or greater than 90% by weight of the nanocomposite), and the capped nanocrystals are present in an amount greater than 50% by weight of the nanocomposite (e.g., about 55-90%, about 60-90%, about 70-90%), greater than 60% by weight of the nanocomposite, greater than 70% by weight of the nanocomposite, greater than 80% by weight of the nanocomposite, or greater than 90% by weight of the nanocomposite, ... at wavelengths of 400 nm or greater, the percent transmission is greater than 80%, e.g., greater than 85%, greater than 90%, greater than 95%, greater than 97%, greater than 98%, or greater than 99%, e.g., about 85%, about 90%, about 95%, about 97%, about 98%, about 99%, about 99.5%, or any range between the recited values, e.g., about 90-99%, as measured by a prism coupler for a film <5 um thick, wherein the nanocomposite film , at 448 nm, from about 1.70 to about 2.10, e.g., 1.70-1.72, or 1.72-1.74, or 1.74-1.76, or 1.76-1.78, or 1.78-1.80, or 1.80-1.82, or 1.82-1.84, or 1.84-1.86, or 1.86-1.88, or 1.88-1.90, or 1.90-1.92, or 1.92-1.94, or 1.94-1.96, or 1.96-1. 98, or 1.98 to 2.00, or 2.00 to 2.02, or 2.02 to 2.04, or 2.04 to 2.06, or 2.06 to 2.08, or 2.08 to 2.10, and at 635 nm may have a refractive index of about 1.70 to about 2.10, e.g., 1.70 to 1.72, or 1.72 to 1.74, or 1.74 to 1.76, or 1.76 to 1.78, or 1.78 to 1.80, or 1.80 to 1.82, or 1.82 to 1. 84, or 1.84 to 1.86, or 1.86 to 1.88, or 1.88 to 1.90, or 1.90 to 1.92, or 1.92 to 1.94, or 1.94 to 1.96, or 1.96 to 1.98, or 1.98 to 2.00, or 2.00 to 2.02, or 2.02 to 2.04, or 2.04 to 2.06, or 2.06 to 2.08, or 2.08 to 2.10.

[0062] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2A nanocomposite film comprising nanocrystals and at least one monomer, polymer, and / or oligomer, wherein the % transmittance of the film at 1 micron is greater than 80%, e.g., greater than 85%, greater than 90%, greater than 95%, greater than 97%, greater than 98%, or greater than 99%, e.g., about 85%, about 90%, about 95%, about 97%, about 98%, about 99%, about 99.5%, or any range between the recited values, e.g., about 90-99%, at wavelengths of 400 nm or greater; and wherein the nanocomposite film is less than 5 μm in thickness. from about 1.70 to about 2.10 at 448 nm, e.g., from 1.70 to 1.72, or from 1.72 to 1.74, or from 1.74 to 1.76, or from 1.76 to 1.78, or from 1.78 to 1.80, or from 1.80 to 1.82, or from 1.82 to 1.84, or from 1.84 to 1.86, or from 1.86 to 1.88, or from 1.88 to 1.90, or from 1.90 to 1.92, or from 1.92 to 1.94, or from 1.94 to 1.96, or from 1.96 to 1.98, or from 1.98 to 2.00, or from 2.00 2.02, or 2.02 to 2.04, or 2.04 to 2.06, or 2.06 to 2.08, or 2.08 to 2.10, and at 635 nm may have a refractive index of about 1.70 to about 2.10, for example, 1.70 to 1.72, or 1.72 to 1.74, or 1.74 to 1.76, or 1.76 to 1.78, or 1.78 to 1.80, or 1.80 to 1.82, or 1.82 to 1.84, or 1.84 to 1.86, or 1.86 to 1.88, or 1.88 to 1.90, or 1.90 to 1.92, or 1.92 to 1.94, or 1.94 to 1.96, or 1.96 to 1.98, or 1.98 to 2.00, or 2.00 to 2.02, or 2.02 to 2.04, or 2.04 to 2.06, or 2.06 to 2.08, or 2.08 to 2.10, and the haze of the nanocomposite is less than 0.1%, or less than 0.2%, or less than 0.3%, or less than 0.4%, or less than 0.5%, or less than 1% (e.g., from about 0.01% to about 0.1%, from about 0.1% to about 0.2%, from about 0.1% to about 0.5%, from about 0.2% to about 0.5%, to about 0.1% to about 1%), and b* is less than 1, or less than 0.5, or less than 0.1 (e.g., about 0.01 to about 0.1, about 0.1 to about 0.5, about 0.1 to about 0.2, or about 0.1 or less) as measured by a haze meter. The present invention provides a nanocomposite film having a molecular weight of about 1.0 or more.

[0063] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2A nanocomposite film comprising nanocrystals and at least one monomer, polymer, and / or oligomer, wherein the percent transmittance of the 1 micron film at wavelengths of 400 nm or greater is greater than 80%, e.g., greater than 85%, greater than 90%, greater than 95%, greater than 97%, greater than 98%, or greater than 99%, e.g., about 85%, about 90%, about 95%, about 97%, about 98%, about 99%, about 99.5%, or any range between the recited values, e.g., about 90-99%, , the nanocomposite film has an average optical transmittance (Omni) of about 1.70 to about 2.10, e.g., 1.70-1.72, or 1.72-1.74, or 1.74-1.76, or 1.76-1.78, or 1.78-1.80, or 1.80-1.82, or 1.82-1.84, or 1.84-1.86, or 1.86-1.88, or 1.88-1.90, or 1.90-1.92, or 1.92-1.94, or 1.94- The refractive index may be from about 1.70 to about 2.10 at 635 nm, e.g., from 1.70 to 1.72, or from 1.72 to 1.74, or from 1.74 to 1.76, or from 1.76 to 1.78, or from 1.78 to 1.80, or from 1.80 to 1.82, or from 1.82 to 1.84, or from 1.84 to 1.85. The nanocomposite may have a refractive index of 1.86, or 1.86-1.88, or 1.88-1.90, or 1.90-1.92, or 1.92-1.94, or 1.94-1.96, or 1.96-1.98, or 1.98-2.00, or 2.00-2.02, or 2.02-2.04, or 2.04-2.06, or 2.06-2.08, or 2.08-2.10, and the haze of the nanocomposite is less than 0.1%, or less than 0.2%, or less than 0.3%, or less than 0.4%, or less than 0.The present invention provides a nanocomposite film having a capped nanocrystal content of less than 5%, or even less than 1%, and the capped nanocrystals are uniformly dispersed in the film without agglomeration to provide a uniform RI distribution as observed by TEM, SEM, or EDX imaging as a uniform particle distribution.

[0064] The method of the present disclosure includes capping the as-synthesized, purified and / or isolated nanocrystals with at least one capping agent to produce at least partially capped nanocrystals. The at least partially capped nanocrystals may be further purified and / or isolated according to the method of the present disclosure. The nanocrystals and capped nanocrystals may be dispersed in a material comprising a solvent, a polymer, or any combination thereof in the method of the present disclosure.

[0065] The surface of the titanium oxide nanocrystals of the present disclosure is optionally capped with at least one capping agent, including but not limited to a silane, an alcohol, or a carboxylic acid. Examples of silanes of the present disclosure include methyltrimethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, phenyltrimethoxysilane, dodecyltrimethoxysilane, m,p-ethylphenethyltrimethoxysilane, 2-[methoxy(polyethyleneoxy)propyl]trimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-isocyanatopropyltrimethoxysilane, and 3-glycidoxypropyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 1-hexenyltrimethoxysilane, 1-octenyltrimethoxysilane, phenylaminomethyl)methyldimethoxysilane, phenylamino ... methoxysilane, N-phenylaminopropyltrimethoxysilane, 3-(4-pyridylethyl)thiopropyltrimethoxysilane, N-(3-trimethoxysilylpropyl)pyrrole, 2-(3-trimethoxysilylpropylthio)thiophene, (3-trimethoxysilylpropyl)diethylenetriamine, 11-mercaptoundecyltrimethoxysilane, (2-diphenylphosphino)ethyldimethylethoxysilane, 2-(diphenylphosphino)ethyltriethoxysilane, 3-(diphenylphosphino)propyltriethoxysilane, or any combination thereof.

[0066] Examples of alcohols of the present disclosure include, but are not limited to, heptanol, hexanol, octanol, benzyl alcohol, phenol, ethanol, propanol, butanol, oleyl alcohol, dodecyl alcohol, octadecanol, triethylene glycol monomethyl ether, or any combination thereof.

[0067] Examples of carboxylic acids of the present disclosure include, but are not limited to, octanoic acid, acetic acid, propionic acid, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, benzoic acid, stearic acid, trifluoroacetic acid, biphenyl-4-carboxylic acid, 2-(2-methoxyethoxy)acetic acid, methacrylic acid, mono-2-(methacryloyloxy)ethyl succinate, or any combination thereof.

[0068] Examples of thiols and sulfonates of the present disclosure include, but are not limited to, 2-mercaptoethanol, 2-{2-[2-(2-mercaptoethoxy)ethoxy]ethoxy}ethanol, 2-(2-methoxyethoxy)ethanethiol, 1-octanethiol, sodium 2,3-dimercaptopropanesulfonate monohydrate, sodium dodecyl sulfate, or any combination thereof.

[0069] Examples of phosphonates and phosphates of the present disclosure include, but are not limited to, dodecylphosphonic acid, octylphosphonic acid, (11-mercaptoundecyl)phosphonic acid, (11-(acryloyloxy)undecyl)phosphonic acid, 11-methacryloyloxyundecylphosphonic acid, [2-[2-(2-methoxyethoxy)ethoxy]ethyl]phosphonic acid ethyl ester, or any combination thereof.

[0070] The capped titanium dioxide nanocrystals of the present disclosure may optionally be dissolved in solvents such as: benzyl alcohol, phenol, oleyl alcohol, butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, 2-(isopentyloxy)ethanol, 2-propoxypropanol (PnP), 2-(hexyloxy)ethanol; ethers and cyclic ethers such as: tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether; glycol and esters such as propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), methyl acetates, ethyl acetates, butyl carbitol acetate (BCA), butyl acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monoethyl ether acetate, butoxyethyl acetate, ethyl acetate, 2-(2-butoxyethoxy)ethyl acetate, and the like; aromatics such as benzene, toluene; and water, and any combination or mixture thereof, and therein. It will be redistributed.

[0071] The TiO 2The average particle size of the nanocrystals may be <50 nm as measured by TEM. Preferably, the particle size is between 1-4 nm, or 4-6 nm, or 6-8 nm, or 8-10 nm, or 10-12 nm, or 12-14 nm, or 14-16 nm, or 16-18 nm, or 18-20 nm, or 20-25 nm, or 25-30 nm, or 30-35 nm, or 35-40 nm, or 40-45 nm, or 45-50 nm as measured by TEM.

[0072] One common technique for evaluating the size and size distribution of nanocrystals in a dispersion is dynamic light scattering (DLS). DLS typically measures nanocrystals dispersed in a liquid that is transparent to the wavelength of measurement. In this technique, a laser beam is scattered from a liquid sample of appropriate concentration in a plastic, glass, or fused silica cuvette, and the size and size distribution of the nanocrystals can be calculated by measuring the time dependence of the scattered laser light due to the Brownian motion of the nanocrystals. The result is usually a size distribution of nanocrystals with the x-axis being the equivalent diameter, and the y-axis can represent the scattering intensity, the volume of the scattering nanocrystals, or the number of scattering nanocrystals. The measured size often includes not only the thin layer of solvent (solvent shell), but also the size of the nanocrystal and the size of the capping agent, and / or solvent groups, and / or precursor groups, and therefore the actual nanocrystal size is often smaller than that measured by DLS. In this disclosure, unless otherwise specified, all references to nanocrystal size and size distribution refer to the actual nanocrystal size and not to the nanocrystal size plus capping agent and / or solvent group and / or precursor group, or the nanocrystal plus capping agent and / or solvent group and / or precursor group plus solvent shell. D9999 is defined as 99.99% of the particles in a measured dispersion are less than the reported value (in nanometers), measured by volume. A variety of DLS spectrometers are available, but each vendor often develops proprietary methodologies and algorithms, and results may not be interchangeable, and the model specifically used to obtain the data in this disclosure is the Malvern Zetasizer Nano S DLS. In any embodiment described herein, unless specified, the average particle size and / or D9999 value determined / measured by DLS can be based on intensity, volume, or both.For example, unless otherwise specified, the average particle size of a sample of titanium dioxide nanocrystals is between 4 and 50 nm if the average particle size determined by DLS and based on either intensity or volume is within the range of 4 to 50 nm. References to D9999 values ​​should be understood in the same manner. Unless otherwise specified or clear from the context, in any of the embodiments described herein, the average particle size and / or D9999 values ​​determined / measured by DLS referred to herein can be based on volume. Unless otherwise specified or clear from the context, in any of the embodiments described herein, the average particle size and / or D9999 values ​​determined / measured by DLS referred to herein can be based on intensity.

[0073] The capped titanium dioxide nanocrystals dispersed at 5 wt.% in a solvent of the present disclosure may have an average particle size, as measured by intensity, of <130 nm, as measured by dynamic light scattering. Preferably, the particle size, as measured by DLS, is 1-4 nm, or 4-6 nm, or 6-8 nm, or 8-10 nm, or 10-12 nm, or 12-14 nm, or 14-16 nm, or 16-18 nm, or 18-20 nm, or 20-25 nm, or 25-30, or 30-35 nm, or 30-35 nm, or 35-40 nm, or 40-45 nm, or 45-50 nm, or 50-55 nm, or 55-60 nm, or 60-65 nm, or 65-70 nm, or 70-75 nm, or 75-80 nm, or 75-90 nm, or 75-100 nm, or 75-110 nm, or 75-120 nm, or 75-130 nm, or 75-140 nm, or 75-150 nm, or 75-160 nm, or 75-170 nm, or 75-180 nm, or 75-190 nm, or 75-200 nm, or 75-200 nm, or 75-200 nm, or 75-200 nm, or 75-300 nm, or 75-300 nm, or 75-400 nm, or 75-500 nm, or 75-600 nm, or 75-190 nm, or 75-200 nm, or 75-300 nm, or 75-400 nm, or 75-500 nm, or 75-600 nm, or 5 nm, or 75-80 nm, or 80-85 nm, or 85-90 nm, or 90-95 nm, or 95-100 nm, or 100-105, or 105-110, or 110-115, or 115-120, or 120-125, or 125-130.

[0074] The capped titanium dioxide nanocrystals dispersed at 5 wt. % in a solvent of the present disclosure may have an average particle size, measured by volume, of <130 nm as measured by dynamic light scattering. Preferably, the particle size, as measured by DLS, is between 1-4 nm, or 4-6 nm, or 6-8 nm, or 8-10 nm, or 10-12 nm, or 12-14 nm, or 14-16 nm, or 16-18 nm, or 18-20 nm, or 20-25 nm, or 25-30, or 30-35 nm, or 30-35 nm, or 35-40 nm, or 40-45 nm, or 45-50 nm, or 50-55 nm, or 55-60 nm, or 60-65 nm, or 65-70 nm, or 70-75 nm, or 75-80 nm, or 80-85 nm, or 85-90 nm, or 90-95 nm, or 95-100 nm, or 100-110 nm, or 110-120 nm, or 120-130 nm.

[0075] The capped titanium dioxide nanocrystals dispersed at 5 wt.% in the solvent of the present disclosure may have a D9999 measured by volume of <500 nm as measured by dynamic light scattering. Preferably, the D9999 is <20 nm, <30 nm, <40 nm, <50 nm, <60 nm, <70 nm, <80 nm, <90 nm, <100 nm, <110 nm, <120 nm, <130 nm, <140 nm, <150 nm, <170 nm, <190 nm, <200 nm as measured by DLS.

[0076] One common technique for evaluating the light transmittance and absorbance of nanocrystal dispersion formulations and films is UV-Vis spectrophotometer (UV-Vis). The UV-Vis method measures the transmitted light versus incident light of a sample in the wavelength range of 200nm to 900nm. The transmittance of a sample at a given wavelength is defined as:

number

number

[0077] The absorbance, or optical density (OD), of a sample at a given wavelength is defined as:

number

[0078] A reference sample is often used to eliminate effects from other materials in the sample. For samples, which often involve multiple reflections, modeling and algorithms may be applied to extract the actual transmittance, absorptance, and absorbance.

[0079] To measure nanocrystal dispersions or formulations, samples are typically placed in plastic, glass, or fused silica cuvettes with a 10 mm path length. Samples are measured against a reference, which contains the same solvent used in the dispersion in the same or same type of cuvette to eliminate effects from the cuvette and solvent. To measure nanocrystal polymer nanocomposites, the nanocomposite may be spin-cast onto a glass or fused silica wafer to form a uniform thin film, and the sample may be measured against a reference, which contains the same wafer and / or the same polymer spin-cast onto a wafer of the same thickness to eliminate effects from the wafer and polymer. Modeling and algorithms may be applied to extract the exact transmittance, absorptance, and absorbance of the nanocomposite.

[0080] A variety of UV-Vis spectrometers are available, but they are all based on the same principles and, when operated properly, the results are interchangeable. The particular model used to obtain the data in this disclosure is the Perkin Elmer Lambda 850.

[0081] One common technique for evaluating loading levels of nanocrystal dispersions and nanocomposites is thermogravimetric analysis (TGA). In this technique, the nanocrystal dispersion or nanocrystal polymer nanocomposite is placed in a crucible and heated from room temperature to about 800°C while monitoring the weight. The organic solvent, polymer, and capping agent will decompose at high and usually different temperatures, leaving only the inorganic nanocrystals. The relative weight percentages of the various components in the original sample can be obtained. The TGA results are usually plotted with temperature on the x-axis and relative weight percentage on the y-axis. There are various TGA instruments available, but they are all based on similar principles and, if operated properly, the results are interchangeable. The model specifically used to obtain the data in this disclosure is a TA Instrument TGA Q500.

[0082] Formulations of the present disclosure may be analyzed using a TA Instruments Q500 Thermogravimetric Analyzer (TGA) to determine the organic solids content of the capped titanium dioxide nanocrystals and subsequently the inorganic content of the final formulation. The percent mass at 200°C relative to the initial mass (M200C) is considered to be the capped nanocrystals, and the percent mass at 700°C relative to the initial mass (M700C) is considered to be the inorganic portion of the capped nanocrystals, i.e., the inorganic solids content. The organic content is defined as the difference between the percent mass at 200°C and 700°C divided by the percent mass at 200°C, i.e., % organics = (M200C - M700C) / M200C.

[0083] The refractive index is measured using a Metricon 2010 / M model prism coupler with 448 nm and 635 nm laser beams. The estimated refractive index of the same material at a third wavelength can be calculated. The calculation of the refractive index at 550 nm is based on the Cauchy equation of binomial type.

number

number

[0084] This disclosure relates to TiO 2 A method of making nanocrystals is provided, comprising dissolving a precursor of the nanocrystal in at least one solvent to produce a solution, optionally at least one of heating and increasing the pressure of the solution, and reacting the precursor with at least one solvent of the solution to form the nanocrystal.

[0085] The nanocrystals may be further capped with at least one capping agent to enhance the solubility or dispersibility of the nanocrystals in at least one solvent or other medium, or any combination of solvents and other media. In the method of the present disclosure, the nanocrystals may be capped with at least one agent that may include at least one silane, alcohol, or carboxylic acid. These capping agents can impart uniform dispersion of the nanocrystals in different media, such as hydrophobic or hydrophilic media, by creating an effective nanocrystal surface, which is formed by a complete or partial shell of the capping agent with its tail group having a polarity compatible with the medium.

[0086] The capping method of the present disclosure may include capping the nanocrystals with at least one capping agent in solution before, during, or after said reaction of the precursors. The capping method may include the addition of a small amount of water to facilitate the capping step. The method of the present disclosure may further include purifying and / or isolating the nanocrystals before or after the capping method of the present disclosure.

[0087] The functionalized capping agent, according to one aspect of the present disclosure, is TiO 2 The capping agent is covalently attached to the nanocrystal. Alternatively, the nanocrystal is functionalized with the capping agent without forming a covalent bond.

[0088] The present disclosure includes nanocrystals and at least partially capped nanocrystals made by the methods described herein.

[0089] The disclosed methods further include methods of making formulations by mixing the nanocrystals with monomers, oligomers, and / or polymers and other additives. The formulations can be used to form films or coatings, such as by applying the formulation to a surface. Application methods include spin coating, spraying, dipping, screen printing, rolling, painting, printing, inkjet printing, dispensing devices, roll-to-roll coating, deposition by evaporation and / or vapor deposition, and the like, followed by optional curing of the film or coating by treatment with light or heat. TiO 2 Synthesis of nanocrystals

[0090] In an exemplary method, titanium oxide nanocrystals are produced by a solvothermal process from a mixture of titanium(IV) butoxide, water, and benzyl alcohol in an inert atmosphere sealed in an autoclave. The molar ratio of titanium(IV) butoxide to water is about 1:0 to 1:0.1, 1:0.1 to 1:0.5, 1:0.5 to 1:1, 1:1 to 1:1.5, 1:1.5 to 1:2, 1:2 to 1:2.5, 1:2.5 to 1:3, 1:3 to 1:3. .5, 1:3.5-1:4, 1:4-1:4.5, 1:4.5-1:5, 1:5-1:5.5, 1:5.5-1:6, 1:6-1:6.5, 1:6.5-1:7, 1:7-1:7.5, 1:7.5-1:8, 1:8-1:8.5, 1:8.5-1:9, 1:9-1:9.5, 1:9.5-1:10. The molar ratio of titanium(IV) butoxide to benzyl alcohol ranges from 1:0.1 to 1:5, 1:5 to 1:10, 1:10 to 1:15, 1:15 to 1:20, 1:20 to 1:25, 1:25 to 1:30, 1:30 to 1:35, 1:35 to 1:40, 1:40 to 1:45, 1:45 to 1:50, 1:50 to 1:55, 1:55 to 1:60, 1:60 to 1:65, 1:65 to 1:70, 1:70 to 1:75, 1:75 to 1:80, 1:80 to 1:85, 1:85 to 1:90, 1:90 to 1:95, 1:95 to 1:100, 1:100-1:150. The reaction mixture was heated at rates of 0.1-0.5, 0.5-1, 1-1.5, 1.5-2, 2-2.5, 2.5-3, 3-3.5, 2.5-4, 4-4.5, 4.5-5 °C / min, and then heated at 140-150, 150-160, 160-170, 170-180, 180-190, 190-200, 200-210, 210-220, 220-240, 230-250, 240-260, 250-270, 260-280, 270-290, 280-300, 310-320, 320-330, 330-340, 340-350, 350-360, 360-370, 370-380, 380-390, 390-400, 400-410, 410-420, 420-430, 430-440, 440-450, 450-460, 460-470, 470-480, 480-490, 490-500, 500-510, 510-520, 520-530, 530-540, 540-550, 550-560, 560-570, 570-580, 580-590, 600-610, 610-620, 620-630, 630-640, It is heated to temperatures between 0, 220-230, 230-240, 240-250, 250-260, 260-270, 270-280, 280-290, 290-300°C, 300-310°C, 310-320°C, 320-330°C, 330-340°C, 340-350°C, 350-360°C, and 360-370°C. Once the reaction mixture reaches the desired temperature, the temperature is maintained for 1-10 min, 10-20 min, 20-30 min, 30-40 min, 40-50 min, 50-60 min, 60-70 min, 70-80 min, 80-90 min, 90-100 min, 100-120 min, 1-2 hr, 2-3 hr, 3-4 hr, 4-5 hr, 5-6 hr, 6-7 hr, 7-8 hr, 8-9 hr, 9-10 hr, 10-1 hr, 11-12 hr, 12-13 hr, 13-14 hr, 14-15 hr, 15-16 hr, 16-17 hr, 17-18 hr, 18-19 hr, 19-20 hr. The reactor pressure reaches 50-150 psi during the reaction. After cooling the reactor to room temperature, the as-synthesized TiO 2 A white milky solution of nanocrystals is recovered. TiO 2 Nanocrystal caps

[0091] Some embodiments of the present disclosure include TiO 2 In some embodiments, the method comprises capping a TiO nanocrystal. 2 The nanocrystals (e.g., any of those described herein) are reacted with a first capping agent in a first capping solvent to produce a first at least partially capped TiO 2 In some embodiments, reacting comprises: 1) producing TiO nanocrystals; 2 2) mixing the nanocrystals with a first capping agent in a first capping solvent to provide a first reaction mixture; and 3) heating the first reaction mixture, e.g., at the reflux temperature of the first capping solvent, for a period of time (e.g., about 10 minutes to about 120 minutes) to produce a first at least partially capped TiO. 2 In some embodiments, the method includes: 1) forming a first at least partially capped TiO nanocrystal; 2 2) mixing the nanocrystals with a second capping agent in a second capping solvent to provide a second reaction mixture; and 3) heating the second reaction mixture, for example, at the reflux temperature of the second capping solvent for a period of time (e.g., about 10 minutes to about 120 minutes) to produce a second at least partially capped TiO. 2 In some embodiments, the method further comprises: a) adding water to the first or second reaction mixture after each heating step 2) and b) heating the first or second reaction mixture for an additional period of time (e.g., from about 10 minutes to about 120 minutes). In some embodiments, the method further comprises: producing the first or second at least partially capped TiO nanocrystals, e.g., as described herein. 2 This can further include isolating, purifying, and / or drying the nanocrystals.

[0092] TiO suitable for the capping method herein 2The nanocrystals are not particularly limited. In some embodiments, the nanocrystals are TiO 2 Nanocrystals are those having a size of less than 50 nm (e.g., less than about 50 nm, less than about 40 nm, less than about 30 nm, less than about 20 nm, less than about 10 nm, or less than about 5 nm, e.g., about 1 nm, about 4 nm, about 5 nm, about 10 nm, about 15 nm, about 20 nm, about 35 nm, about 30 nm, about 40 nm, about 50 nm, or any range between the recited values, e.g., about 1 nm to about 5 nm, about 1 nm to about 10 nm, about 40 nm to about 50 nm, about 20 nm to about 30 nm, about 10 nm to about 20 nm, about 30 nm to about 40 nm, about 4 nm to about 50 nm, about 4 nm to about 20 nm, about 15 nm to about 20 nm, or about 10 nm to about 25 nm). 2 The nanocrystals can have a narrow particle size distribution. For example, in some embodiments, TiO 2 The nanocrystals can have a narrow particle size distribution characterized by: 1) a D90:D10 ratio of less than 5, preferably less than 3, or less than 2, e.g., from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.8, from about 1.2 to about 3, or from about 1.5 to about 3; 2) a D90:D50 ratio of less than 3, preferably less than 2, or less than 1.5, e.g., from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.5; and / or 3) a D50:D10 ratio of less than 3, preferably less than 2, or less than 1.5, e.g., from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.5. In some embodiments, TiO 2 The nanocrystals may also have a narrow particle size distribution characterized by a standard deviation (σ) of the particle size distribution of 15% or less (e.g., 10% or less, or 5% or less, e.g., about 1% to about 15%, about 5% to about 10%, or about 10% to about 15%) of the median particle size of the nanocrystals, as measured by TEM. In some embodiments, the TiO 2The nanocrystals may also have a narrow particle size distribution, as measured by TEM, characterized by a standard deviation (σ) of the particle size distribution of 5 nm or less (e.g., 3 nm or less, or about 1 nm or less, e.g., about 1 nm, about 3 nm, about 5 nm, or any range between the recited values, e.g., about 1-3 nm, about 1-5 nm, about 3-5 nm, etc.). In some embodiments, the TiO 2 The nanocrystals may also have a narrow particle size distribution characterized by greater than about 90% (e.g., greater than about 95%, or greater than about 99%, e.g., about 91%, about 95%, about 98%, about 99%, about 99.5%, or any range between the recited values, e.g., 90-99%, 90-95%, or 95-99%, etc.) of the nanocrystals having a particle size within 5 nm of the average particle size, as measured by TEM.

[0093] In some preferred embodiments, TiO 2The nanocrystals are prepared by any of the methods described herein. For example, typically, the milky white suspension is collected and transferred to a centrifuge bottle, such as a 250 mL centrifuge bottle. The suspension is centrifuged at 100-500, 500-1000, 100-1500, 1500-2000, 2000-2500, 2500-3000 rpm, 3000-3500, 3500-4000, 4000-4500, 4500-5000, 5000-5500, 5500-6000, 6000-650 Centrifuge at 0, 6500-7000, 7000-7500, 7500-8000, 8000-8500, 8500-9000 rpm for 0-5, 5-10, 10-15, 15-20, 30-25, 25-30, 30-35, 35-40, 40-45, 45-50, 50-55, 55-60 minutes. Decant the supernatant and settle the wet cake at the bottom of the centrifuge bottle. Wash the wet cake by adding a solvent if desired, then stir the wet cake in the solvent and then centrifuge. Then transfer the collected wet cake to a 250 ml round-bottom flask. A solvent such as PGMEA or toluene is added to the wet cake in a ratio of 0.1:1 to 1:1, 1:1 to 1.25:1, 1.25:1 to 1.5:1, 1.5:1 to 1.75:1, 1.75:1 to 2:1, 2:1 to 2.25:1, 2.25:1 to 2.5:1, 2.5:1 to 2.75:1, 2.75:1 to 3:1, 3:1 to 4:1, 4:1 to 5:1, 5:1 to 6:1, 6:1 to 7:1, 7:1 to 8:1, 8:1 to 9:1, 9:1 to 10:1 solvent by weight. The first capping agent is added to the reaction flask at 0.1-5%, 5-10%, 10-15%, 15-20%, 20-25%, 25-30%, 30-35% capping agent by weight based on the wet cake. The mixture is then heated at 50-60, 60-70, 70-80, 80-90, 90-100, 100-110, 110-120, 120-130°C for 1-10, 10-20, 20-30, 30-40, 40-50, ...80, 80-90, 90-100, 100-110, 110-120, 120-130°C for 1-10, 10-20, 20-30, 30-40, 40-50, 50-60, 60-80, 80-90, 90-100, 100-110, 110-120, 120-130°C for 1-10, 10-20, 20-30, 30-40, 40-50, 50-60, 60-80, 80-90, 90-100, 100-110, 120-130°C for 1- Reflux for ~70, 70~80, 80~90, 90~100, 100~120 minutes.

[0094] Optionally, a second capping agent is added to the reaction flask before or after the first heating step, and the second capping agent is added to the reaction flask in a ratio of 0.1-5%, 5-10%, 10-15%, 15-20%, 20-25%, 25%-30%, 30%-35%, 35%-40%, 40%-45%, 45%-50%, 50%-55%, 55%-60%, 60%-70%, 70%-80%, 80%-90%, 90%-100% of the capping agent by weight relative to the wet cake. The mixture is then refluxed for 1-10, 10-20, 20-30, 30-40, 40-50, 50-60, 60-70, 70-80, 80-90, 90-100, 100-120 minutes at 50-60, 60-70, 70-80, 80-90, 90-100, 100-120° C. Optionally, water is then added to the wet cake in a ratio of 0.1-5%, 5-10%, 10-15%, 15-20%, 20-25%, 25-30%, 30-35% water by weight after cooling the reaction mixture to 80° C. The mixture is refluxed at 80-90, 90-100, 100-110, 110-120, 120-130°C for an additional 1-10, 10-20, 20-30, 30-40, 40-50, 50-60, 60-70, 70-80, 80-90, 90-100, 100-120 minutes. The reaction mixture is then cooled to room temperature to obtain the capped nanocrystals. The capped nanocrystals in the dispersion are then filtered through a 0.45 micron, then a 0.2 micron PTFE filter, or optionally further purified by the following washing steps:

[0095] The capped nanocrystals are purified by washing to remove excess capping agent and other by-products. The reaction mixture is precipitated by mixing an anti-solvent, e.g., heptane for the PGMEA solution or acetone for the toluene solution, with the reaction mixture in a ratio of 0.1:1 to 1:1, 1:1 to 1.25:1, 1.25:1 to 1.5:1, 1.5:1 to 1.75:1, 1.75:1 to 2:1, 2:1 to 2.25:1, 2.25:1 to 2.5:1, 2.5:1 to 2.75:1, or 2.75:1 to 3:1 by weight of the anti-solvent. This precipitate is then separated into 100-500, 500-1000, 100-1500, 1500-2000, 2000-2500, 2500-3000 rpm, 3000-3500, 3500-4000, 4000-4500, 4500-5000, 5000-5500, 5500-6000, 6000-6500, 650 Centrifuge at 0-7000, 7000-7500, 7500-8000, 8000-8500, and 8500-9000 rpm for 0-5, 5-10, 10-15, 15-20, 30-25, 25-30, 30-35, 35-40, 40-45, 45-50, 50-55, and 55-60 minutes. Decant and discard the resulting supernatant. The solids are then separated into non-polar capped TiO 2 Toluene in the case of nanocrystals, polar capped TiO 2The nanocrystals are dispersed in a solvent such as THF, and the dispersed solids are then precipitated again using an anti-solvent, such as heptane for the THF solution or acetone for the toluene solution, in a ratio of 0.1:1 to 1:1, 1:1 to 1.25:1, 1.25:1 to 1.5:1, 1.5:1 to 1.75:1, 1.75:1 to 2:1, 2:1 to 2.25:1, 2.25:1 to 2.5:1, 2.5:1 to 2.75:1, or 2.75:1 to 3:1 by weight to the reaction mixture. This precipitate is then separated into 100-500, 500-1000, 100-1500, 1500-2000, 2000-2500, 2500-3000 rpm, 3000-3500, 3500-4000, 4000-4500, 4500-5000, 5000-5500, 5500-6000, 6000-6500, 650 Centrifuge at 0-7000, 7000-7500, 7500-8000, 8000-8500, and 8500-9000 rpm for 0-5, 5-10, 10-15, 15-20, 30-25, 25-30, 30-35, 35-40, 40-45, 45-50, 50-55, and 55-60 minutes. Decant and discard the resulting supernatant. Repeat this process as necessary. The solids are then dried overnight in a vacuum oven.

[0096] The dried solids are redispersed in PGMEA at a 1:1 ratio of solids to solvent to produce a dispersion at a loading of 50% by weight. The resulting dispersion is optionally filtered through a 0.45 micron followed by a 0.2 micron PTFE filter.

[0097] The first or second capping agent is typically independently selected from silanes, alcohols, carboxylic acids, thiols, sulfonates, phosphonates, phosphates, and combinations thereof. Examples of suitable silanes, alcohols, carboxylic acids, thiols, sulfonates, phosphonates, phosphates include those described herein. In some embodiments, the first or second capping agent is methyltrimethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, phenyltrimethoxysilane, dodecyltrimethoxysilane, m,p-Ethylphenethyltrimethoxysilane, 2-[methoxy(polyethyleneoxy)propyl]trimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-isocyanatopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 1-hexenyltrimethoxysilane, 1-octenyltrimethoxysilane, phenylaminomethyl)methyldimethoxysilane, N-phenylaminopropyltrimethoxysilane, 3-(4-pyridylethyl)thiopropyltrimethoxysilane, N-(3-trimethoxysilylpropyl)pyrrole, 2-(3-trimethoxysilylpropylthio)thiophene, (3-trimethoxysilylpropylthio)pyrrole, (2-(diphenylphosphino)ethyldimethylethoxysilane, 2-(diphenylphosphino)ethyltriethoxysilane, 3-(diphenylphosphino)propyltriethoxysilane, heptanol, hexanol, octanol, benzyl alcohol, phenol, ethanol, propanol, butanol, oleyl alcohol, dodecyl alcohol, octadecanol, triethylene glycol Monomethyl ether, octanoic acid, acetic acid, propionic acid, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, benzoic acid, stearic acid, trifluoroacetic acid, biphenyl-4-carboxylic acid, 2-(2-methoxyethoxy)acetic acid, methacrylic acid, mono-2-(methacryloyloxy)ethyl succinate, 2-mercaptoethanol, 2-{2-(2-mercaptoethoxy)ethoxy}ethanol, 2-(2-methoxyethoxy)ethanethiol, 1-octanethiol, 2,are independently selected from sodium 3-dimercaptopropanesulfonate monohydrate, sodium dodecyl sulfate, dodecylphosphonic acid, octylphosphonic acid, (11-mercaptoundecyl)phosphonic acid, (11-(acryloyloxy)undecyl)phosphonic acid, 11-methacryloyloxyundecylphosphonic acid, [2-[2-(2-methoxyethoxy)ethoxy]ethyl]phosphonic acid ethyl ester, and combinations thereof. In some embodiments, the first or second capping agent is independently selected from methyltrimethoxysilane, n-octyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, and combinations thereof; for example, in some embodiments, the first or second capping agent is independently selected from methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and combinations thereof.

[0098] The first or second capping solvent is typically independently selected from alcohol-based solvents, ether-based solvents, glycol-based solvents, ketone-based solvents, ester-based solvents, aromatic solvents, water, and combinations thereof. Examples of suitable alcohol-based solvents, ether-based solvents, glycol-based solvents, ketone-based solvents, ester-based solvents, and aromatic solvents include any of those described herein. In some embodiments, the first or second capping solvent is benzyl alcohol, phenol, oleyl alcohol, butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, 2-(isopentyloxy)ethanol, 2-propoxy-propanol (PnP), 2-(hexyloxy)ethanol, tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, Independently selected from diethylene glycol monoethyl ether, diethylene glycol, dipropylene glycol, acetone, propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), methyl acetates, ethyl acetates, butyl carbitol acetate (BCA), butyl acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, butoxyethyl acetate, ethyl acetate, 2-(2-butoxyethoxy)ethyl acetate, benzene, toluene, water, and combinations thereof.In some embodiments, the first or second capping solvent is independently selected from benzyl alcohol, butyl carbitol acetate (BCA), propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), ethyl acetate, toluene, and combinations thereof, e.g., the first or second capping solvent is independently selected from benzyl alcohol, butyl carbitol acetate (BCA), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl acetate, and combinations thereof.

[0099] At least partially capped TiO prepared by the method herein 2 Nanocrystals are also novel compositions of matter of the present disclosure.

[0100] In some embodiments, the present disclosure provides a TiO 2 composition as described herein that is at least partially capped with at least one capping agent selected from silanes, alcohols, carboxylic acids, thiols, sulfonates, phosphonates, phosphates, and combinations thereof. 2 At least partially capped TiO containing nanocrystals 2In some embodiments, the at least one capping agent is selected from the group consisting of methyltrimethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, phenyltrimethoxysilane, dodecyltrimethoxysilane, m,p-ethylphenethyltrimethoxysilane, 2-[methoxy(polyethyleneoxy)propyl]trimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-methyl ... propylcaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-isocyanatopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 1-hexenyltrimethoxysilane, 1-octenyltrimethoxysilane, phenylaminomethyl)methyldimethoxysilane, N-phenylaminopropyltrimethoxysilane, xysilane, 3-(4-pyridylethyl)thiopropyltrimethoxysilane, N-(3-trimethoxysilylpropyl)pyrrole, 2-(3-trimethoxysilylpropylthio)thiophene, (3-trimethoxysilylpropyl)diethylenetriamine, 11-mercaptoundecyltrimethoxysilane, (2-diphenylphosphino)ethyldimethylethoxysilane, 2-(diphenylphosphino)ethyltriethoxysilane, 3-(diphenylphosphino)propyltriethoxysilane, heptanol, hexanol, octanol, benzyl alcohol, phenol, ethanol, propanol, butanol, oleyl alcohol, dodecyl alcohol, octadecanol, triethylene glycol monomethyl ether, octanoic acid, acetic acid, propionic acid, 2-[2-(2-methoxyethoxy)ethoxy ]acetic acid, oleic acid, benzoic acid, stearic acid, trifluoroacetic acid, biphenyl-4-carboxylic acid, 2-(2-methoxyethoxy)acetic acid, methacrylic acid, mono-2-(methacryloyloxy)ethyl succinate, 2-mercaptoethanol, 2-{2-(2-mercaptoethoxy)ethoxy}ethanol, 2-(2-methoxyethoxy)ethanethiol, 1-octanethiol, sodium 2,3-dimercaptopropanesulfonate monohydrate, sodium dodecyl sulfate, dodecylphosphonic acid, octylphosphonic acid, (11-mercaptoundecyl)phosphonic acid, (11-(acryloyloxy)undecyl)phosphonic acid, 11-methacryloyloxyundecylphosphonic acid, [2-[2-(2-methoxyethoxy)ethoxy]ethyl]phosphonic acid ethyl ester, and combinations thereof.In some embodiments, the at least one capping agent is selected from methyltrimethoxysilane, n-octyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, and combinations thereof, for example, the at least one capping agent is selected from methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and combinations thereof.

[0101] The at least partially capped TiO 2 The nanocrystals are in dry and / or substantially pure form, e.g., in some embodiments, at least partially capped TiO 2 Nanocrystals are TiO 2 The capping agent used to cap the nanocrystals, and / or TiO 2 Free or substantially free of by-products resulting from capping the nanocrystals. In some preferred embodiments, the at least partially capped TiO 2 The nanocrystals can be dispersible. In some embodiments, the nanocrystals can be at least partially capped TiO. 2 The nanocrystals were isolated from the capping reaction, purified and dried, and the dried at least partially capped TiO 2 The nanocrystals can be redispersed in a capping solvent as described herein. The term "substantially free" is desirably understood to mean less than 10% by weight, e.g., less than 5% by weight, less than 3% by weight, less than 1% by weight.

[0102] In some embodiments, the at least partially capped TiO 2 The nanocrystals can typically have an organic content of about 5% to about 35%, preferably about 5% to about 15%, or about 10% to about 25%, or about 15% to about 30%, as measured by TGA.

[0103] In any of the embodiments described herein, the at least partially capped TiO 2 The nanocrystals also have an average particle size, measured by volume, of 130 nm for capped titanium dioxide nanocrystals dispersed at 5 wt. % in a solvent, as measured by dynamic light scattering (DLS). In some embodiments, the at least partially capped TiO may be characterized as being less than 120 nm, less than 100 nm, less than 80 nm, less than 50 nm, less than 20 nm, or less than 10 nm, e.g., about 10 nm, about 20 nm, about 50 nm, about 80 nm, about 100 nm, about 120 nm, or any range between the recited values, e.g., about 10 to about 50 nm, about 50 to about 100 nm, etc. 2 The nanocrystals may also be further characterized as having a D9999 of less than 500 nm (e.g., less than 200 nm, less than 100 nm, or less than 50 nm, e.g., about 10 nm, about 20 nm, about 50 nm, about 100 nm, about 200 nm, about 500 nm, or any range between the recited values, e.g., about 20 nm to about 50 nm, about 50 nm to about 100 nm, about 20 nm to about 200 nm, about 100 nm to about 200 nm, etc.) as measured by dynamic light scattering (DLS) on the volume of capped titanium dioxide nanocrystals dispersed in a solvent at 5 wt.%.

[0104] In some embodiments, the present disclosure also provides an at least partially capped TiO 2 Compositions, such as nanocrystal dispersions, that include nanocrystals are provided. TiO 2 Nanocrystal Dispersion

[0105] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO2 A nanocrystal dispersion comprising nanocrystals and a solvent, the nanocrystal dispersion comprising at least a partially capped TiO 2 The nanocrystal dispersion is provided in which the nanocrystals are present in an amount greater than 30%, e.g., greater than 40%, greater than 50%, greater than 60%, or greater than 70%, by weight of the dispersion, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, or any range between the recited values, e.g., about 40-70%, about 30-80%, about 50-80%, etc. At least partially capped TiO 2 The nanocrystals can be any of those described herein. For example, in some embodiments, the nanocrystal dispersion is at least partially capped with a capping agent selected from, for example, methyltrimethoxysilane, n-octyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, and combinations thereof. 2The nanocrystals may be included, and preferably, the capping agent is selected from methyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and combinations thereof, and more preferably, the capping agent is selected from methoxy(triethyleneoxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, and combinations thereof, for example, the capping agent is methoxy(triethyleneoxy)propyltrimethoxysilane. The solvent is not particularly limited. For example, the solvent can be selected from alcohol-based solvents, ether-based solvents, glycol-based solvents, ketone-based solvents, ester-based solvents, aromatic solvents, water, and combinations thereof. Examples of suitable alcohol-based solvents, ether-based solvents, glycol-based solvents, ketone-based solvents, ester-based solvents, and aromatic solvents include any of those described herein. In some embodiments, the solvent is benzyl alcohol, phenol, oleyl alcohol, butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, 2-(isopentyloxy)ethanol, 2-propoxy-propanol (PnP), 2-(hexyloxy)ethanol, tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, propylene glycol monomethyl ether (P GME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol, dipropylene glycol, acetone, propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), methyl acetates, ethyl acetates, butyl carbitol acetate (BCA), butyl acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, butoxyethyl acetate, ethyl acetate, 2-(2-butoxyethoxy)ethyl acetate, benzene, toluene, water, and combinations thereof, and are preferred. Alternatively, the solvent is selected from benzyl alcohol, butyl carbitol acetate (BCA), butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, tetrahydrofuran, diethyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol, dipropylene glycol, acetone, propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), ethyl acetate, butyl acetate, diethylene glycol monoethyl ether acetate, toluene, and combinations thereof. More preferably, the solvent is selected from benzyl alcohol, butyl carbitol acetate (BCA), isopropanol, tetrahydrofuran, propylene glycol monomethyl ether (PGME), dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), ethyl acetate, toluene, and combinations thereof.In some preferred embodiments, the solvent is selected from butyl carbitol acetate (BCA), propylene glycol monomethyl ether (PGME), dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl acetate, and combinations thereof, for example, the solvent is propylene glycol methyl ether acetate (PGMEA).

[0106] The present disclosure relates to a composition containing a dispersion of capped titanium dioxide nanocrystals and a solvent, where the capped titanium dioxide nanocrystals are present in the solvent in an amount of less than 10% by weight, or between 10% and 20% by weight, or between 20% and 30% by weight, or between 30% and 40% by weight, or between 40% and 50% by weight, or between 50% and 60% by weight, or between 60% and 70% by weight, or between 70% and 80% by weight, or between 80% and 90% by weight, or between 90% and 95% by weight, and the solvent is selected from the group consisting of alcohols, such as: benzyl alcohol, phenol, oleyl alcohol, butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, 2-(isopentyloxy)ethanol, 2-propoxypropanol (PnP), 2-(hexyloxy)ethanol; ethers and cyclic ethers, such as: tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether; glycols, such as diethylene glycol, dipropylene glycol; ketones and cyclic ketones, such as acetone; esters, such as propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), methyl acetates, ethyl acetates, butyl acetate, ethylene glycol monobutyl ether acetate, butyl carbitol acetate (BCA), diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, butoxyethyl acetate, ethyl acetate, 2-(2-butoxyethoxy)ethyl acetate; aromatics, such as benzene, toluene; and water. The present invention provides compositions which may include a number of, as well as any combination or mixture thereof.

[0107] In some embodiments, the nanocrystal dispersions described herein are also characterized by the size of the nanocrystals in the dispersion. 2 The average particle size of the nanocrystals ranges from 1 to 50 nm, e.g., from 4 to 20 nm, or from 15 to 20 nm. In some embodiments, the TiO 2 The D9999 of the nanocrystals is in the range of 20-500 nm, preferably less than 200 nm, as measured by DLS. 2 The nanocrystals are typically uniformly dispersed without any aggregation or settling of the nanocrystals as observed by TGA.

[0108] In a solvent such as PGMEA, TiO 2 The optical transmittance at 400 nm of a 50 wt % dispersion of the nanocrystals, measured using a 1 cm path length cuvette, may be 70%-65%, or 65%-60%, or 60%-55%, or 55%-50%, or 50%-45%, or 45%-40%, 40%-35%, 35%-30%, 30%-25%, 25%-20%, 20%-15%, 15%-10%, 10%-5%, 5%-3%, 3%-2%, or 2%-1%.

[0109] In a solvent such as PGMEA, TiO 2 The optical transmittance at 450 nm of a 50 wt % dispersion of the nanocrystals, measured using a 1 cm path length cuvette, may be 70%-65%, or 65%-60%, or 60%-55%, or 55%-50%, or 50%-45%, or 45%-40%, 40%-35%, 35%-30%, 30%-25%, 25%-20%, 20%-15%, 15%-10%, 10%-5%, 5%-3%, 3%-2%, or 2%-1%.

[0110] In a solvent such as PGMEA, TiO 2The optical transmittance at 500 nm of a 50 wt % dispersion of the nanocrystals, measured using a 1 cm path length cuvette, may be 70%-65%, or 65%-60%, or 60%-55%, or 55%-50%, or 50%-45%, or 45%-40%, 40%-35%, 35%-30%, 30%-25%, 25%-20%, 20%-15%, 15%-10%, 10%-5%, 5%-3%, 3%-2%, or 2%-1%.

[0111] In a solvent such as PGMEA, TiO 2 The optical transmittance at 650 nm of a 50 wt % dispersion of the nanocrystals, measured using a 1 cm path length cuvette, may be 70%-65%, or 65%-60%, or 60%-55%, or 55%-50%, or 50%-45%, or 45%-40%, 40%-35%, 35%-30%, 30%-25%, 25%-20%, 20%-15%, or 15%-10%.

[0112] The present disclosure provides a dispersion of capped titanium dioxide nanocrystals in a solvent as described herein, wherein when the dispersion is stored at a temperature in the range of 18-25° C. without any intentional shaking or mixing, the dispersion is storage stable for at least 1 week, or 2 weeks, or 3 weeks, or 4 weeks, or 3 months, or at least 5 months, or at least 6 months, or at least 7 months, or at least 8 months, or at least 9 months, or at least 10 months, or at least 11 months, or at least 1 year, or at least 2 years, or at least 3 years.

[0113] In some embodiments, the nanocrystal dispersion can be stable for more than 2 weeks, e.g., for 3 or 4 weeks, or for more than 3 weeks or more than 4 weeks, and has less than 5% (e.g., less than 3%, less than 2%, or less than 1%, e.g., about 0.1%, about 0.5%, about 1%, about 2%, about 3%, or between the recited values) of crystalline solids when stored in the dark at room temperature. The change in transmittance at 400 nm over any range, for example, about 0.01 to 1%, about 0.1 to 1%, about 0.1 to 5%, about 0.5 to 2%, about 0.5 to 3%, about 0.5 to 1%, etc., is shown.

[0114] The nanocrystal dispersions typically contain at least partially capped TiO 2 In some embodiments, the at least partially capped TiO nanocrystals can be prepared by a method comprising mixing the nanocrystals with a solvent to form a dispersion. 2 The nanocrystals are in substantially pure form, e.g., TiO 2 The capping agent used to cap the nanocrystals, and / or TiO 2 In some embodiments, the method is free of or substantially free of by-products resulting from capping the nanocrystals. 2 This involves mixing the nanocrystals with a solvent to form a dispersion. ZrO 2 -TiO 2 Nanocrystal Dispersion

[0115] Optionally, the present disclosure provides a method for preparing a capped titanium oxide nanocrystal described herein (e.g., an at least partially capped TiO nanocrystal described herein) in a solvent. 2 In one embodiment, the present invention provides a composition containing a dispersion of TiO nanocrystals, and capped zirconium oxide nanocrystals, such as those described in U.S. Pat. No. 8,592,511 B2, the entire contents of which are incorporated herein by reference, to optimize optical, physical, or chemical performance. 2 ZrO 2 The weight ratio of the nanocrystals is 100% TiO 2 and 0% ZrO 2 From 0% TiO 2 and 100% ZrO 2 The properties of the dispersion are listed in Table 3, where TiO 2 ZrO 2 The ratios are 0% and 100%, 10% and 90%, 20% and 80%, 30% and 70%, 40% and 60%, 50% and 50%, 60% and 40%, 70% and 30%, 80% and 20%, 90% and 10%, 100% and 0%, and the solvent content is 50% by weight.

[0116] 1. A dispersion comprising capped titanium oxide nanocrystals and capped zirconium oxide nanocrystals, wherein the total amount of nanocrystals is present in an amount of less than 10% by weight, or between 10% and 20% by weight, or between 20% and 30% by weight, or between 30% and 40% by weight, or between 40% and 50% by weight, or between 50% and 60% by weight, or between 60% and 70% by weight, or between 70% and 80% by weight, or between 80% and 90% by weight, or between 90% and 95% by weight, and the solvent is an alcohol, e.g. : benzyl alcohol, phenol, oleyl alcohol, butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, 2-(isopentyloxy)ethanol, 2-propoxypropanol (PnP), 2-(hexyloxy)ethanol; ethers and cyclic ethers, for example: tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, propylene glycol monomethyl ether (PGME), The dispersion may include one or more of diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether; glycols, such as diethylene glycol, dipropylene glycol; ketones and cyclic ketones, such as acetone; esters, such as propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), methyl acetates, ethyl acetates, butyl carbitol acetate (BCA), butyl acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, butoxyethyl acetate, ethyl acetate, 2-(2-butoxyethoxy)ethyl acetate, and the like; aromatics, such as benzene, toluene; and water, as well as any combination or mixture thereof.

[0117] ZrO at 50 wt% in a solvent such as PGMEA 2 and TiO 2The dispersion of the nanocrystal mixture was measured using a 1 cm path length cuvette and was found to be 65% - 60%, or 60% - It may have a light transmittance at 450 nm of 55%, or 55% to 50%, or 50% to 45%, or 45% to 40%, 40% to 35%, 35% to 30%, 30% to 25%, 25% to 20%, 20% to 15%, or 15% to 10%.

[0118] ZrO at 50 wt% in a solvent such as PGMEA 2 and TiO 2 A dispersion of the mixture of nanocrystals may have a light transmittance at 500 nm of 75%-70%, or 70%-65%, or 65%-60%, or 60%-55%, or 55%-50%, or 50%-45%, or 45%-40%, 40%-35%, 35%-30%, 30%-25%, 25%-20%, 20%-15%, or 15%-10%, as measured using a 1 cm path length cuvette.

[0119] The capped titanium dioxide nanocrystals dispersed at 5 wt.% in a solvent of the present disclosure may have an average particle size, as measured by intensity, of <130 nm, as measured by dynamic light scattering. Preferably, the particle size, as measured by DLS, is 1-4 nm, or 4-6 nm, or 6-8 nm, or 8-10 nm, or 10-12 nm, or 12-14 nm, or 14-16 nm, or 16-18 nm, or 18-20 nm, or 20-25 nm, or 25-30, or 30-35 nm, or 30-35 nm, or 35-40 nm, or 40-45 nm, or 45-50 nm, or 50-55 nm, or 55-60 nm, or 60-65 nm, or 65-70 nm, or 70-80 nm, or 80-90 nm, or 90-100 nm, or 100-120 nm, or 12-14 nm, or 14-16 nm, or 16-18 nm, or 18-20 nm, or 20-25 nm, or 25-30, or 30-35 nm, or 30-35 nm, or 35-40 nm, or 40-45 nm, or 45-50 nm, or 50-55 nm, or 55-60 nm, or 60-65 nm, or 65-70 nm, or 80-100 nm, or 100-120 nm, or 12-14 nm, or 14-16 nm, or 16-18 nm, or 18-20 nm, or 20-25 nm, or 25-30, or 30-35 nm, or 30-35 nm, or 35-40 nm, or 40 nm, or between 70 and 75 nm, or between 75 and 80 nm, or between 80 and 85 nm, or between 85 and 90 nm, or between 90 and 95 nm, or between 95 and 100 nm, or between 100 and 105, or between 105 and 110, or between 110 and 115, or between 115 and 120, or between 120 and 125, or between 125 and 130.

[0120] The capped titanium dioxide nanocrystals dispersed at 5 wt. % in a solvent of the present disclosure may have an average particle size, measured by volume, of <130 nm as measured by dynamic light scattering. Preferably, the particle size, as measured by DLS, is between 1-4 nm, or 4-6 nm, or 6-8 nm, or 8-10 nm, or 10-12 nm, or 12-14 nm, or 14-16 nm, or 16-18 nm, or 18-20 nm, or 20-25 nm, or 25-30, or 30-35 nm, or 30-35 nm, or 35-40 nm, or 40-45 nm, or 45-50 nm, or 50-55 nm, or 55-60 nm, or 60-65 nm, or 65-70 nm, or 70-75 nm, or 75-80 nm, or 80-85 nm, or 85-90 nm, or 90-95 nm, or 95-100 nm, or 100-110 nm, or 110-120 nm, or 120-130 nm.

[0121] The capped titanium dioxide nanocrystals dispersed at 5 wt.% in a solvent of the present disclosure may have a D9999 measured by volume of <200 nm as measured by dynamic light scattering. Preferably, the D9999 is <20, <30, <40, <50, <60, <70, <80, <90, <100, <110, <120, <130, <140, <150, <160, <170, <180, <190 nm as measured by DLS. formulation

[0122] The present disclosure provides formulations that include a mixture of capped nanocrystals and an organic coating material, and optionally a solvent.

[0123] The organic coating materials may include any one or any combination of two or more of monomers, oligomers, and / or polymers, curing agents, adhesion promoters, wetting agents, leveling agents, dispersants, viscosity modifiers, and optionally antioxidants. These and other ingredients may be present in amounts known to those of skill in the art, so long as they do not significantly interfere with the optical applications of the formulations described herein. It can be adopted in.

[0124] The formulations disclosed in this disclosure are flowable liquids that may be used to create films or coatings, or layers or lenses, or self-supporting structures.

[0125] The formulations of the present disclosure may include nanocrystals of metal oxides, such as titanium oxide, or mixtures of zirconium oxide and titanium oxide, which have a high bulk refractive index, typically greater than 2, and exceptional transparency in the visible spectrum.

[0126] The organic coating materials of the present disclosure, in combination with metal oxide nanocrystals as described herein, allow for the production of easily processable thin coatings with high refractive index and high optical transparency. These films may be flexible.

[0127] In some embodiments, the capping agent of the capped nanocrystals in the formulation of the present disclosure is methyltrimethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, phenyltrimethoxysilane, dodecyltrimethoxysilane, m,p-Ethylphenethyltrimethoxysilane, 2-[methoxy(polyethyleneoxy)propyl]trimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-isocyanatopropyltrimethoxysilane, and 3-glycidoxypropyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 1-hexenyltrimethoxysilane, 1-octenyltrimethoxysilane, phenylaminomethyl)methyldimethoxysilane, N-phenylaminopropyltrimethoxysilane, 3-(4-pyridylethyl)thiopropyltrimethoxysilane, N-(3-trimethoxysilylpropyl)pyrrole, 2-(3-trimethoxysilylpropylthio)thiophene, (3-trimethoxypropyl)propyltrimethoxysilane, (Diphenylphosphino)propyltriethoxysilane, 11-mercaptoundecyltrimethoxysilane, (2-diphenylphosphino)ethyldimethylethoxysilane, 2-(diphenylphosphino)ethyltriethoxysilane, 3-(diphenylphosphino)propyltriethoxysilane, heptanol, hexanol, octanol, benzyl alcohol, phenol, ethanol, propanol, butanol, oleyl alcohol, dodecyl alcohol, octadecanol, triethylene glycol Cholesterol monomethyl ether, octanoic acid, acetic acid, propionic acid, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, benzoic acid, stearic acid, trifluoroacetic acid, biphenyl-4-carboxylic acid, 2-(2-methoxyethoxy)acetic acid, methacrylic acid, succinic acid mono-2-(methacryloyloxy)ethyl, 2-mercaptoethanol, 2-{2-(2-mercaptoethoxy)ethoxy}ethanol, 2-(2-methoxyethoxy)ethanethiol, 1-octanethiol, 2,3-dimercaptopropanesulfonate sodium monohydrate, sodium dodecyl sulfate, dodecylphosphonic acid, octylphosphonic acid, (11-mercaptoundecyl)phosphonic acid, (11-(acryloyloxy)undecyl)phosphonic acid, 11-methacryloyloxyundecylphosphonic acid, [2-[2-(2-methoxyethoxy)ethoxy]ethyl]phosphonic acid ethyl ester, and any combination thereof.

[0128] Solvents for the formulations of the present disclosure include alcohols, such as: benzyl alcohol, phenol, oleyl alcohol, butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, 2-(isopentyloxy)ethanol, 2-propoxypropanol (PnP), 2-(hexyloxy)ethanol; ethers and cyclic ethers, such as tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether; glycols, such as diethylene glycol, dipropylene glycol; ketones and cyclic ketones, such as acetone; esters, such as propylene glycol methyl ether. acetate (PGMEA), ethyl lactate (EL), methyl acetates, ethyl acetates, butyl carbitol acetate (BCA), butyl acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, butoxyethyl acetate, ethyl acetate, 2-(2-butoxyethoxy)ethyl acetate; aromatics, such as: benzene, toluene; and water, as well as any combination or mixture thereof.

[0129] The solvent in the formulation of the present disclosure may constitute less than 10% by weight of the total formulation, or 10% to 20% by weight of the total formulation, or 20% to 30% by weight of the total formulation, or 30% to 40% by weight of the total formulation, or 40% to 50% by weight of the total formulation, or 50% to 60% by weight of the total formulation, or 60% to 70% by weight of the total formulation, or 70% to 80% by weight of the total formulation, or 80% to 90% by weight of the total formulation.

[0130] The formulations of the present disclosure may be analyzed using a TA Instruments Q500 Thermogravimetric Analyzer (TGA) to determine the inorganic solids content. The procedure is the same as described above. The percent mass at 200°C relative to the initial mass is considered as the total mass of the formulation minus the solvent content, and the percent mass at 700°C relative to the initial mass is considered as the inorganic portion of the formulation, i.e., the solids content.

[0131] The inorganic solids content of the formulation of the present disclosure may be 0-10% as measured by TGA, or 10-20% as measured by TGA, or 20-30% as measured by TGA, or 30-40% as measured by TGA, or 40-50% as measured by TGA, or 50-60% as measured by TGA, or 60-70% as measured by TGA, or 70-80% as measured by TGA, or 80-90% as measured by TGA, or 90-93% as measured by TGA. The organic coating material of the formulation of the present disclosure may include monomers, oligomers, and / or polymers. The monomers, oligomers, and / or polymers of the formulation of the present disclosure may include acrylics. The monomers, oligomers, and / or polymers of the formulations of the present disclosure include bisphenol A glycerolate dimethacrylate, biphenyl-2-ol ethoxylate esters with acrylic acid (OPPEOA), bisphenol A ethoxylate diacrylates, bisphenol A propoxylate diacrylate, bisphenol F ethoxylate (2 EO / phenol) diacrylate, bisphenol A glycerolate diacrylates, bisphenol A ethoxylate dimethacrylate, ethoxylated (4) bisphenol A diacrylate. (SR-601), Biphenol A ethoxylate diacrylate (SR-349), Tris(2-acryloyloxy)ethyl}isocyanurate, Tricyclodecane dimethanol diacrylate, Tris(2-hydroxyethyl)isocyanurate triacrylate, Cresol novolac epoxy acrylate (CN112C60), Benzyl methacrylate (BMA), Benzyl acrylate, Trimethylolpropane triacrylate (TMPTA), Trimethylolpropane ethoxylate (1 EO / OH) methyl ether diacrylate, 1,6-Hexanediol diacrylate (HDDA, SR238B), Tri(ethylene glycol) diacrylate, Ethylene glycol diacrylate, Poly(ethylene glycol) diacrylate, Glycerol 1,3-diglycerolate diacrylate, Di(ethylene glycol) diacrylate, Tetra(ethylene glycol) diacrylate, Poly(propionyl

[0043] The copolymers may include tri(ethylene glycol) diacrylate, tri(propylene glycol) diacrylate (SR306F), 1,6-hexanediol ethoxylate diacrylate, ethylene glycol phenyl ether acrylate, biphenyl methyl acrylate (Miramer M1192), tricyclodecane dimethanol diacrylate (SR833S), polyester acrylate (CN2283, CN2281).

[0132] Aliphatic urethane acrylate oligomer (CN2920), epoxy acrylate oligomer (CN2003B), tris(2-hydroxyethyl)isocyanurate triacrylate (THEICTA - Miramer M370), 1,1'-thiobis(2,3-epithiopropane), 2,2'-thiobis-ethanethiol, or any combination thereof.

[0133] The capped nanocrystals of the formulations of the present disclosure may comprise less than 10% by weight of monomers, oligomers, and / or polymers, plus at least partially capped nanocrystals, or 10% to 20% by weight of monomers, oligomers, and / or polymers, plus at least partially capped nanocrystals, or 20% to 30% by weight of monomers, oligomers, and / or polymers, plus at least partially capped nanocrystals, or 30% to 40% by weight of monomers, oligomers, and / or polymers, plus at least partially capped nanocrystals, or 40% to 50% by weight of monomers, oligomers, and The nanocrystals may comprise 50% to 60% by weight of monomers, oligomers, and / or polymers, plus at least partially capped nanocrystals, or 60% to 70% by weight of monomers, oligomers, and / or polymers, plus at least partially capped nanocrystals, or 70% to 80% by weight of monomers, oligomers, and / or polymers, plus at least partially capped nanocrystals, or 80% to 90% by weight of monomers, oligomers, and / or polymers, plus at least partially capped nanocrystals.

[0134] The curing agent of the formulation of the present disclosure may include a photoinitiator. Any photoinitiator can be used as long as it can generate active species such as radicals using light (UV) energy. The curing agent of the photoinitiator may be amines such as Ebecryl® Pl 15, benzophenone and its derivatives such as Ebecryl® P39, Speedcure BEM (Lambson USA Ltd, Rutherford, CT, USA), 4,4'-bis(diethylamino)benzophenone, or organic phosphines such as diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide, or Irgacure® 184 (BASF USA, Florham Park, NJ, USA). Park, NJ, USA), or 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), or ethyl (2,4,6-trimethylbenzoyl)phenylphosphinate, 4-(dimethylamino)benzophenone, or others such as 2-isopropylthoxanthone, Darocur 4265, Speedcure Xkm, methylbenzoyl formate, thioxanthen-9-one, etc. The formulation may include a single photoinitiator, or any combination thereof.

[0135] The curing agent of the formulation of the present disclosure may include a thermal free radical initiator. Suitable thermal free radical initiators include, but are not limited to, peroxide compounds and azo compounds. Peroxide curing agents include commonly used organic peroxy curing agents such as dicumyl peroxide, t-butyl perbenzoate, benzoyl peroxide, t-butyl perbenzoate ... The initiator may be selected from ethyl peracetate, 1,1-di(t-butylperoxy)3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne, and n-butyl-4,4-bis(t-butylperoxyvalerate). The azo initiator may be selected from 2,2'-azobisisobutyronitrile (AIBN), V-40, V-59, and VA-061 (Wako Chemicals USA, North Chesterfield, VA, USA). The combination of multiple curing agents may be advantageous in certain circumstances as known to those skilled in the art.

[0136] The amount of curing agent in the formulation of the present disclosure may be present in an amount of less than 0.5% by weight of the monomer, oligomer, and / or polymer, or from 0.5% to 1% by weight of the monomer, oligomer, and / or polymer, or from 1% to 2% by weight of the monomer, oligomer, and / or polymer, or from 2% to 3% by weight of the monomer, oligomer, and / or polymer, or from 3% to 4% by weight of the monomer, oligomer, and / or polymer, or from 4% to 5% by weight of the monomer, oligomer, and / or polymer, or from 5% to 6% by weight of the monomer, oligomer, and / or polymer, or from 6% to 7% by weight of the monomer, oligomer, and / or polymer, or from 7% to 8% by weight of the monomer, oligomer, and / or polymer, or from 8% to 15% by weight of the monomer, oligomer, and / or polymer.

[0137] When present, the adhesion promoter may be selected from organometallic compounds, such as functional silanes, or from functionalized monomers and oligomers. Some suitable functional silane adhesion promoters contain amino or methacryloxy groups. Exemplary silane adhesion promoters include, but are not limited to, 3-aminopropyltriethoxysilane, 3-[(methacryloyloxy)propyl]trimethoxysilane, ureidopropyltrimethoxysilane, and trimethoxy[3-(methylamino)propyl]silane. Functionalized monomeric and oligomeric adhesion promoters include, but are not limited to, CN820, CN146 (Sartomer Americas, Exton, PA, USA), SR9051, SR9053 (Sartomer Americas, Exton, PA, USA), and Ebecryl 171 (Allnex USA Inc., Wallingford, CT, USA).

[0138] The adhesion promoter of the formulation of the present disclosure may be present in an amount of less than 0.5% by weight of the monomer, oligomer, and / or polymer, or 0.5-1% by weight of the monomer, oligomer, and / or polymer, or 1-5% by weight of the monomer, oligomer, and / or polymer, or 5-10% by weight of the monomer, oligomer, and / or polymer, or 10-15% by weight of the monomer, oligomer, and / or polymer, or 15-30% by weight of the monomer, oligomer, and / or polymer.

[0139] Wetting agents may be present to reduce the surface tension of the formulation, thereby improving the wetting of the coating on the substrate and the underlayer.Representative examples of suitable wetting agents include, but are not limited to, siloxane surfactants such as BYK-307, BYK-330, (BYK Chemie, GMBH), fluorosurfactants such as Novec 4430, Novec 4432, and Novec 4434 (3M, St.Paul, MN, USA).

[0140] The amount of wetting agent in the formulations of the present disclosure is less than 0.05% by weight of the total formulation, or less than 0.05% by weight of the total formulation. It may be present in an amount of from 0.1% by weight, or from 0.1 to 0.5% by weight of the total formulation, or from 0.5 to 1% by weight of the total formulation, or from 1 to 2% by weight of the total formulation, or from 2 to 5% by weight of the total formulation.

[0141] Leveling agents may be used to improve the flowability of the formulation and produce a more uniform surface of the dried coating. When present, the leveling agent may be a polyacrylate compound such as BYK-352, BYK-353, BYK-356, and BYK-361N, and an aralkyl-modified polymethylalkylsiloxane such as BYK-322, BYK-323, and BYK-350 (BYK Chemie, LLC).

[0142] The amount of leveling agent in the formulation of the present disclosure may be present in an amount less than 0.05% by weight of the total formulation, or between 0.05 and 0.1% by weight of the total formulation, or between 0.1 and 0.5% by weight of the total formulation, or between 0.5 and 1% by weight of the total formulation, or between 1 and 2% by weight of the total formulation, or between 2 and 5% by weight of the total formulation.

[0143] The dispersant may be a nonionic dispersant, an anionic dispersant, or a combination thereof. Examples of dispersants may include, without limitation, polyalkylene glycols and their esters, polyoxyalkylenes, polyhydric alcohol ester alkylene oxide adducts, alcohol alkylene oxide adducts, sulfonic acid esters, sulfonic acid salts, carboxylic acid esters, carboxylic acid salts, alkylamide alkylene oxide adducts, alkylamines, and the like, which may be used alone or in a mixture of two or more.

[0144] Commercially available examples of dispersants include, without limitation, Disper BYK-101, Disper BYK-130, Disper BYK-140, Disper BYK-160, Disper BYK-161, Disper BYK-162, Disper BYK-163, Disper BYK-164, Disper BYK-165, Disper BYK-166, Disper BYK-170, Disper BYK-171, Disper BYK-182, Disper BYK-2000, Disper BYK-2001 (BYK Chemie, LLC), Solsperse 32000, Solsperse 36000, Solsperse 28000, Solsperse 20000, Solsperse 41000, and Solsperse 45000 (Lubrizol, Wickliffe, Ohio, USA), fluorosurfactants such as FC-4430, FC-4432, FC-4434 (3M), Capstone FS-3100, and the like may be mentioned.

[0145] The amount of dispersant in the formulations of the present disclosure may vary depending on the material being dispersed. The amount of dispersant may be less than 3% by weight of the material being dispersed, or 3-5% by weight of the material being dispersed, or 5-10% by weight of the material being dispersed, or 10-20% by weight of the material being dispersed, or 20-40% by weight of the material being dispersed, or 40-60% by weight of the material being dispersed, or 60-80% by weight of the material being dispersed, or 80-100% by weight of the material being dispersed, or 100-150% by weight of the material being dispersed.

[0146] The formulations of the present disclosure can have tunable viscosity and / or viscosity that can be controlled by one or more of the organic coating materials or solvents.

[0147] The formulations of the present disclosure may have a viscosity of about 1 cP to about 1,000 cP. The formulations of the present disclosure may have an adjustable viscosity of, for example, about 1 cP to 2 cP, about 2 cP to 5 cP, about 5 cP to 10 cP, about 10 cP to 15 cP, about 15 cP to 20 cP, about 20 cP to 25 cP, about 25 cP to about 30 cP, about 30 cP to about 40 cP, about 40 cP to about 50 cP, about 50 cP to about 60 cP, about 60 cP to about 75 cP, about 75 cP to about 100 cP, about 100 cP to about 200 cP, about 200 cP to about 500 cP, or about 500 cP to about 1,000 cP when measured at 25° C. using a Brookfield RVDV II+ cone-and-plate viscometer. This is also fine.

[0148] The viscosity of the formulations of the present disclosure may be controlled. Parameters that can control the viscosity of the formulation include, but are not limited to, the average length and molecular weight of the monomers, oligomers, and / or polymers; the presence and concentration of solvents; the presence and concentration of thickeners (i.e., viscosity modifying components); particle size of the components present in the formulation; and combinations thereof.

[0149] The antioxidant of the formulation of the present disclosure may include at least one primary antioxidant, which may be selected from sterically hindered phenols such as Irganox 1010, Irganox 1076, Songnox® 1076, Songnox® 2450, or phenol phosphites such as Songnox® 1680, or phosphines such as Irgafos 168 (BASF USA, Florham Park, NJ, USA), or aromatic secondary amines or sterically hindered amines such as Songlite® 6220 (Songwon Americas, Friendwood, TX, USA).

[0150] The formulation of the present disclosure may contain at least one secondary antioxidant. The secondary antioxidant is preferably selected from compounds containing at least one unit formed from a sulfur atom bonded to two carbon atoms. Representative examples of secondary antioxidants are di(t-butyl)hydroxyphenylaminobisoctylthiotriazine and Irganox PS800 (BASF USA, Florham Park, NJ, USA).

[0151] The amount of antioxidant in the formulation of the present disclosure may be less than 0.5% by weight of the total formulation, or between 0.5% and 1% by weight of the total formulation, or between 1% and 2% by weight of the total formulation, or between 2% and 3% by weight of the total formulation, or between 3% and 4% by weight of the total formulation, or between 4% and 5% by weight of the total formulation, or between 5% and 6% by weight of the total formulation, or between 6% and 7% by weight of the total formulation, or between 7% and 8% by weight of the total formulation.

[0152] The optical transmittance at 400 nm of a formulation of the present disclosure using 50% PGMEA by weight of the total formulation as a solvent may be 99%-95%, or 95%-90%, or 90%-85%, or 85%-80%, or 80%-75%, or 75%-70%, or 70%-65%, or 65%-60%, or 60%-55%, or 55%-50%, or 50%-45%, or 45%-40%, or 40%-35%, or 35%-30%, or 30%-25%, or 25%-20%, or 20%-15%, or 15%-10%, when measured in a cuvette having a 1 cm path length using a PerkinElmer Lambda 850 spectrophotometer.

[0153] The optical transmittance at 450 nm of a formulation of the present disclosure using 50% PGMEA by weight of the total formulation as a solvent may be 99%-95%, or 95%-90%, or 90%-85%, or 85%-80%, or 80%-75%, or 75%-70%, or 70%-65%, or 65%-60%, or 60%-55%, or 55%-50%, or 50%-45%, or 45%-40%, or 40%-35%, or 35%-30%, or 30%-25%, or 25%-20%, or 20%-15%, or 15%-10%, when measured in a cuvette having a 1 cm path length using a PerkinElmer Lambda 850 spectrophotometer.

[0154] The optical transmittance at 500 nm of the formulations of the present disclosure using 50% by weight of all formulations as a solvent was measured using a PerkinElmer Lambda 850 spectrophotometer with a 1 cm path length. When measured in a cuvette, it may be 99% to 95%, or 95% to 90%, or 90% to 85%, or 85% to 80%, or 80% to 75%, or 75% to 70%, or 70% to 65%, or 65% to 60%, or 60% to 55%, or 55% to 50%, or 50% to 45%, or 45% to 40%, or 40% to 35%, or 35% to 30%, or 30% to 25%, or 25% to 20%, or 20% to 15%, or 15% to 10%.

[0155] The optical transmittance at 650 nm of a formulation of the present disclosure using 50% PGMEA by weight of the total formulation as a solvent may be 99%-95%, or 95%-90%, or 90%-85%, or 85%-80%, or 80%-75%, or 75%-70%, or 70%-65%, or 65%-60%, or 60%-55%, or 55%-50%, or 50%-45%, or 45%-40%, or 40%-35%, or 35%-30%, or 30%-25%, or 25%-20%, or 20%-15%, or 15%-10%, when measured in a cuvette having a 1 cm path length using a PerkinElmer Lambda 850 spectrophotometer.

[0156] In some embodiments, the present disclosure provides a nanocomposite formulation comprising a nanocrystal dispersion as described herein and a monomer, oligomer, and / or polymer. In some embodiments, the present disclosure provides a nanocomposite formulation prepared by a method comprising mixing a nanocrystal dispersion as described herein with a monomer, oligomer, and / or polymer. In some embodiments, the present disclosure provides a nanocomposite formulation comprising: 1) an at least partially capped TiO 2 In some embodiments, the present disclosure provides a nanocomposite formulation comprising: 1) at least partially capped TiO nanocrystals; and 2) a monomer, oligomer, and / or polymer. 2 In some embodiments, the present disclosure provides a nanocomposite formulation comprising: 1) at least partially capped TiO nanocrystals; 2) monomers, oligomers, and / or polymers; and 3) a solvent. 2 A nanocomposite formulation is provided, comprising: 1) a nanocrystal; 2) a monomer, oligomer, and / or polymer; 3) a solvent; and 4) a curing agent. In some embodiments, the nanocomposite formulation further comprises one or more components selected from a curing agent, an adhesion promoter, a wetting agent, a leveling agent, a dispersant, a viscosity modifier, and an antioxidant. Suitable at least partially capped TiO 2 Nanocrystals, monomers, oligomers, and / or polymers, solvents, curing agents, adhesion promoters, wetting agents, leveling agents, dispersants, viscosity modifiers, and antioxidants may include any of those described herein.

[0157] At least partially capped TiO in nanocomposite formulations 2The nanocrystals may be at least partially capped with a capping agent selected from any of those described herein, such as methyltrimethoxysilane, n-octyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, and combinations thereof. 2 The nanocrystals may include, preferably, the capping agent is selected from methyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and combinations thereof, more preferably, the capping agent is selected from methoxy(triethyleneoxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, and combinations thereof, e.g., the capping agent is methoxy(triethyleneoxy)propyltrimethoxysilane. In some embodiments, the at least partially capped TiO 2 The nanocrystals are in substantially pure form, e.g., TiO 2 The capping agent used to cap the nanocrystals, and / or TiO 2 Free or substantially free of by-products resulting from capping the nanocrystals. In some embodiments, the at least partially capped TiO 2The nanocrystals are present in an amount greater than 30% by weight relative to the monomer, oligomer, and / or polymer, e.g., greater than 40%, greater than 50%, greater than 60%, greater than 70%, greater than 80%, or greater than 90%, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, about 90%, or any range between the recited values, e.g., about 50-90%, about 40-80%, about 60-90%, etc.

[0158] Monomers, oligomers, and / or polymers for nanocomposite formulations can include any of those described herein. In some embodiments, the monomers, oligomers, and / or polymers are acrylate, epoxy, or isocyanurate compounds. For example, in some embodiments, the monomers, oligomers, and / or polymers are bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), bisphenol A ethoxylate diacrylates, bisphenol A propoxylate diacrylate, bisphenol F ethoxylate (2 EO / phenol) diacrylate, bisphenol A glycerolate diacrylates, bisphenol A ethoxylate dimethacrylate, ethoxylated (4) bisphenol A diacrylate (SR-601), bisphenol A ethoxylate diacrylate (SR-349), tris(2-acryloyloxy)ethyl}isocyanurate, tricyclodecane dimethanol diacrylate, tris(2-hydroxyethyl)isocyanurate triacrylate, cresol novolac epoxy acrylate (CN112C60), benzyl methacrylate (BMA), benzyl acrylate, trimethylolpropane triacrylate (TMPTA), trimethylolpropane ethoxylate (1 EO / OH) methyl ether diacrylate, 1,6-hexanediol diacrylate (HDDA, SR238B), tri(ethylene glycol) diacrylate, ethylene glycol diacrylate, poly(ethylene glycol) diacrylate, glycerol 1,3-diglycerolate diacrylate, di(ethylene glycol) diacrylate, and combinations thereof.In some preferred embodiments, the monomers, oligomers, and / or polymers are selected from the group consisting of bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), bisphenol A ethoxylate diacrylates, bisphenol A propoxylate diacrylate, bisphenol F ethoxylate (2 EO / phenol) diacrylate, bisphenol A glycerolate diacrylates, bisphenol A ethoxylate dimethacrylate, ethoxylated (4) bisphenol A diacrylate. (SR-601), biphenol A ethoxylate diacrylate (SR-349), cresol novolac epoxy acrylate (CN112C60), and combinations thereof, preferably the monomer, oligomer, and / or polymer is selected from bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), ethoxylated (4) bisphenol A diacrylate (SR-601), biphenol A ethoxylate diacrylate (SR-349), cresol novolac epoxy acrylate (CN112C60), and combinations thereof.

[0159] Solvents for the nanocomposite formulations herein include any of those described herein. For example, in some embodiments, the solvent is benzyl alcohol, butyl carbitol acetate (BCA), butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, tetrahydrofuran, diethyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol The solvent may be selected from butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol, dipropylene glycol, acetone, propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), ethyl acetate, butyl acetate, diethylene glycol monoethyl ether acetate, toluene, and combinations thereof, preferably, the solvent is selected from benzyl alcohol, butyl carbitol acetate (BCA), propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol, dipropylene glycol, acetone, propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), ethyl acetate, butyl acetate, diethylene glycol monoethyl ether acetate, toluene, and combinations thereof. More preferably, the solvent is selected from benzyl alcohol, butyl carbitol acetate (BCA), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), ethyl acetate, and combinations thereof, for example, the solvent is dipropylene glycol methyl ether (DPGME), propylene glycol methyl ether acetate (PGMEA), or combinations thereof.

[0160] Curing agents for the nanocomposite formulations herein, when present, are typically photoinitiators and / or thermal free radical initiators. Suitable curing agents include those described herein. In some embodiments, the curing agent is Ebecryl® Pl 15, Ebecryl® P39, benzophenone, Speedcure BEM, 4,4'-bis(diethylamino)benzophenone, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, Irgacure® 184, 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), ethyl(2,4,6-trimethylbenzoyl)phenylphosphinate, 4-(dimethylamino)benzophenone, 2-isopropyl toxanthone, Daro More preferably, the curing agent comprises one or more agents selected from Ebecryl® Pl 15, Ebecryl® P39, benzophenone, diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide, Irgacure® 184, benzoyl peroxoside, and 2,2'-azobisisobutyronitrile. In some embodiments, the nanocomposite formulation may further comprise at least one adhesion promoter as described herein, preferably selected from 3-aminopropyltriethoxysilane, 3-[(methacryloyloxy)propyl]trimethoxysilane, ureidopropyltrimethoxysilane, trimethoxy[3-(methylamino)propyl]silane, CN820, CN146, and combinations thereof.In some embodiments, the nanocomposite formulation may further comprise at least one wetting agent as described herein, preferably selected from BYK-307, BYK-330, Novec 4430, Novec 4432, Novec 4434, and combinations thereof. In some embodiments, the nanocomposite formulation may further comprise at least one leveling agent as described herein, preferably selected from BYK-352, BYK-353, BYK-356, BYK-361N, BYK-322, BYK-323, BYK-350, and combinations thereof. In some embodiments, the nanocomposite formulation may further comprise at least one dispersing agent as described herein, preferably selected from Disper BYK-101, Disper BYK-130, Disper BYK-140, Disper BYK-160, Disper BYK-161, Disper BYK-. 162, Disper BYK-163, Disper BYK-164, Disper BYK-165, Disper BYK-166, Disper BYK-170, Disper BYK-171, Disper BYK-182, Disper BYK-2000, Disper BYK-2001, Solsperse 32000, Solsperse 36000, Solsperse 28000, Solsperse 20000, Solsperse 41000, and Solsperse 45000, FC-4430, FC-4432, FC-4434 (3M), Capstone FS-3100, and combinations thereof. In some embodiments, the nanocomposite formulation may further comprise at least one antioxidant as described herein, preferably at least one antioxidant selected from Irganox 1010, Irganox 1076, Songnox (registered trademark) 1076, Songnox (registered trademark) 2450, Songnox (registered trademark) 1680, Irgafos 168, Songlite (registered trademark) 6220, and combinations thereof.

[0161] The nanocomposite formulations described herein typically have TiO in the formulation in the range of 1-50 nm, e.g., 4-20 nm, or 10-20 nm. 2 In some embodiments, the TiO 2 in the formulation has an average particle size of nanocrystals. 2 The D9999 of the nanocrystals is in the range of 20-500 nm, preferably less than 200 nm, as measured by DLS. 2 The nanocrystals are typically uniformly dispersed without nanocrystal aggregation or settling as observed by TGA. The formulations are also typically stable for greater than 2 weeks, e.g., for 3 or 4 weeks, or for greater than 3 weeks or greater than 4 weeks, and exhibit a change in transmittance at 400 nm of less than 5% (e.g., less than 3%, less than 2%, or less than 1%, e.g., about 0.1%, about 0.5%, about 1%, about 2%, about 3%, or any range between the recited values, e.g., about 0.01-1%, about 0.1-1%, about 0.1-5%, about 0.5-2%, about 0.5-3%, about 0.5-1%, etc.) when stored in the dark at room temperature.

[0162] In some embodiments, the nanocomposite formulations described herein can also have a tunable viscosity ranging from about 1 cP to about 1000 cP, e.g., from about 1 cP to 2 cP, from about 2 cP to 5 cP, from about 5 cP to 10 cP, from about 10 cP to 15 cP, from about 15 cP to 20 cP, from about 20 cP to 25 cP, from about 25 cP to about 30 cP, from about 30 cP to about 40 cP, from about 40 cP to about 50 cP, from about 50 cP to about 60 cP, from about 60 cP to about 75 cP, from about 75 cP to about 100 cP, from about 100 cP to about 200 cP, from about 200 cP to about 500 cP, or from about 500 cP to about 1,000 cP, as measured at 25° C. using a Brookfield RVDV II+ cone and plate viscometer. Scattering agent-containing formulation

[0163] The formulations described herein (e.g., any of the nanocomposite formulations described herein) may include scatterer particles, which may include titania particles, polymeric fillers or beads, or silica particles, or ZrO 2These may include particles of several hundred nanometers, such as controlled aggregates of nanocrystals.

[0164] The scatterers in the formulations described herein may have an average size ranging from 50-100 nm, or 100-200 nm, or 200-300 nm, or 300-400 nm, or 400-500 nm, or 500-600 nm, or 600-700 nm, or 700-800 nm, or 800-900 nm, or 900 nm to 1 μm, or 1-1.5 μm, or 1.5-2 μm.

[0165] The scatterers in the formulations described herein may be in an amount of 0.1-40% by weight, based on the total weight of the formulation.

[0166] The scatterers in the formulations described herein may have a refractive index higher than the refractive index of the binder formulation.

[0167] The scatterers in the formulations described herein may have a refractive index lower than the refractive index of the binder formulation.

[0168] Formulations described herein containing scatterer particles may have a viscosity of less than 5 cPs, or between 5 cPs and 50 cPs, or between 50 cPs and 200 cPs, or between 200 cPs and 400 cPs, or between 400 cPs and 650 cPs, or between 650 cPs and 1000 cPs, when measured at 25° C. using a Brookfield RVDV II+ cone and plate viscometer.

[0169] The formulations described herein that contain scatterer particles are storage stable for at least 1 week, or 2 weeks, or 3 weeks, or 4 weeks, or 3 months, or at least 5 months, or at least 6 months, or at least 7 months, or at least 8 months, or at least 9 months, or at least 10 months, or at least 11 months, or at least 1 year, or at least 2 years, or at least 3 years, when the scattering formulation is stored at a temperature in the range of 18-25°C without any intentional shaking or mixing.

[0170] The formulations described herein containing scatterer particles may be storage stable, where the weight percentage of scatterer particles in a sample taken from the top third of a stored sample of the scattering formulation changes by less than 1% over the storage time, or 1-2%, or 2-3%, or 3-4%, or 4-5%, or 5-7%, or 7-10%, or 10-15%, or 15-20%, or 20-25%, or 25-30%, or 30-35%. How the film is made

[0171] The present disclosure provides methods for making nanocomposites, which may be films or coatings, or layers or lenses, or free-standing structures, obtained by curing the liquid formulations described herein by heat or UV exposure.

[0172] The nanocomposite coating or film described herein, wherein the at least partially capped nanocrystals are made by a process comprising mixing the nanocrystals with at least one capping agent in a capping solvent; the at least partially capped nanocrystals may be separated from the capping solvent; the nanocrystals may be titanium oxide, or a mixture of zirconium oxide and titanium oxide nanocrystals; the partially capped nanocrystals are mixed with a solvent, a monomer, an oligomer, a polymer, or a combination thereof, and the formulation may further comprise a curing agent, an antioxidant, a crosslinking agent, a thickener, an adhesion promoter, a wetting agent, a leveling agent, a dispersant, a plasticizer, or a softener.

[0173] The disclosed methods of making nanocomposite coatings or films using the disclosed formulations may be deposited on substrates that include or contain glass, SiC, poly(3,4-ethylenedioxythiophene) (PEDOT), PEDOT doped with poly(styrenesulfonate) (PSS), polyethylene terephthalate (PET), polyethylene naphthalene (PEN), or doped poly(4,4-dioctylcyclopentadithiophene), or polyimide.

[0174] The disclosed methods of making nanocomposite coatings or films using the disclosed formulations include spin coating, slot-die coating, slit coating, screen printing, inkjet printing, dip coating, draw-bar coating, roll-to-roll printing, nano-coating, and nano-coating. The methods may include photoimprinting, photopatterning, spray coating, imprint lithography, and any combination thereof.

[0175] The disclosed method of making a nanocomposite coating or film using the disclosed formulation may be to adhere to a substrate and heat cure the coating or film on a hot plate at 50° C.-100° C., or 100° C.-150° C., or 150° C.-200° C. for 5-10 minutes, or 10-20 minutes, or 20-30 minutes, or 30-40 minutes, or 40-50 minutes, or 50-60 minutes, or 60-70 minutes, or 70-80 minutes, or 80-90 minutes, or 90-100 minutes, or 100-120 minutes.

[0176] The disclosed method of making a nanocomposite coating or film using the disclosed formulation comprises depositing on a substrate a UV having a wavelength between 220-230 nm, 230-240 nm, 240-250 nm, 250-260 nm, 260-270 nm, 270-280 nm, 280-290 nm, 290-300 nm, 300-310 nm, 310-320 nm, or 320-330 nm, or 330-340 nm, or 340-350 nm, or 350-360 nm, or 360-370 nm, or 370-380 nm, or 380-390 nm, or 390-400 nm, or 400-410 nm, or 410-420 nm, at a dose of 1 J / cm. 2 Less than 1~2J / cm 2 Less than 2~3J / cm 2 Less than 3~4J / cm 2 Less than 4~5J / cm 2 Less than 5~6J / cm 2 Less than 6~7J / cm 2 Less than 7~8J / cm 2 Less than 8~9J / cm2 Less than 9~10J / cm 2 It may be cured by irradiation with a dose of less than 1000 nm.

[0177] In some embodiments, the present disclosure provides a method of coating a substrate comprising depositing the nanocomposite formulation described herein on a surface of the substrate. In some embodiments, the substrate is a glass substrate, a ceramic substrate, a metal substrate, and / or a plastic substrate. In some embodiments, the substrate can comprise glass, SiC, poly(3,4-ethylenedioxythiophene) (PEDOT), PEDOT doped with poly(styrenesulfonate) (PSS), polyethylene terephthalate (PET), polyethylene naphthalene (PEN), doped poly(4,4-dioctylcyclopentadithiophene), or polyimide, or a combination thereof. In some embodiments, the nanocomposite formulation is deposited on the surface by spin coating, spraying, dipping, screen printing, rolling, painting, printing, inkjet printing, dispensing, roll-to-roll coating, deposition by evaporation and / or vapor deposition, preferably by spin coating, inkjet printing, imprinting, nanoimprinting, photopatterning, roll-to-roll coating, slot-die coating, and / or screen printing. In some embodiments, the method further comprises curing the nanocomposite formulation, for example, by light, such as UV light, or by heat treatment as described herein.

[0178] The coated substrate prepared by the methods described herein is also a novel composition of the present disclosure. In some embodiments, the present disclosure also provides a device comprising a coated substrate prepared by the methods described herein. In some embodiments, the device is an LED, mini LED, micro LED, organic LED (OLED), quantum LED (QLED), touch screen, display, sensor, CMOS sensor, flexible electronics, printed electronics, augmented reality, virtual reality, mixed reality, waveguide, diffraction grating, or solar cell device. In some embodiments, the device is a device that includes a lens structure as an internal light extraction layer, e.g., a light emitting diode device, and the internal light extraction layer comprises a coated substrate prepared by the methods described herein. Film or coating

[0179] The present disclosure relates to methods of making nanocomposites using the formulations described herein. The present invention provides a nanocomposite coating or film made using the method, the nanocomposite coating or film comprising a mixture of a polymer matrix, a curing agent, and capped nanocrystals, the capped nanocrystals being present in the coating or film in an amount greater than 5% by weight of the coating or film.

[0180] Nanocomposite coatings or films in the present disclosure may include nanocrystals of metal oxides such as titanium oxide, or a mixture of zirconium oxide and titanium oxide.

[0181] The film thickness of the nanocomposite coatings or films of the present disclosure made using the disclosed methods of making nanocomposites using the formulations described herein may range from 40 nanometers to 100 micrometers.

[0182] Nanocomposite coatings or films of the present disclosure made using the disclosed methods of making nanocomposites using the formulations described herein have a CdI of 1.60-1.62, or 1.62-1.64, or 1.64-1.66, or 1.66-1.68, or 1.68-1.70, 1.70-1.72, or 1.72-1.76 at 448 nm when measured using a prism coupler for films having a thickness of <5 um. .74, or 1.76 to 1.78, or 1.78 to 1.80, or 1.80 to 1.82, or 1.82 to 1.84, or 1.84 to 1.86, or 1.86 to 1.88, or 1.88 to 1.90, or 1.90 to 1.92, or 1.92 to 1.94, or 1.94 to 1.96, or 1.96 to 1.98, or 1.98 to 2.00, or 2.00 to 2.02, or 2.02 to 2.04, or may have a refractive index of 2.04 to 2.06, or 2.06 to 2.08, or 2.08 to 2.10, and at 635 nm may be 1.60 to 1.62, or 1.62 to 1.64, or 1.64 to 1.66, or 1.66 to 1.68, or 1.68 to 1.70, or 1.70 to 1.72, or 1.72 to 1.74, or 1.76 to 1.78, or 1.78 to 1.80, or 1.80 to 1.82, or 1. It may have a refractive index of 82 to 1.84, or 1.84 to 1.86, or 1.86 to 1.88, or 1.88 to 1.90, or 1.90 to 1.92, or 1.92 to 1.94, or 1.94 to 1.96, or 1.96 to 1.98, or 1.98 to 2.00, or 2.00 to 2.02, or 2.02 to 2.04, or 2.04 to 2.06, or 2.06 to 2.08, or 2.08 to 2.10.

[0183] Nanocomposite coatings or films of the present disclosure made using the disclosed methods of making nanocomposites with the formulations described herein may have a root mean square (RMS) surface roughness of 3 nm to 10 nm, or 2 nm to 3 nm, or 1 nm to 2 nm, or 0.6 nm to 1 nm, or 0.1 nm to 0.6 nm. The RMS surface roughness may be measured over a 5 micron by 5 micron square using an atomic force microscope (AFM).

[0184] Nanocomposite coatings or films of the present disclosure made using the disclosed methods of making nanocomposites with the formulations described herein may have high visible light (400-800 nm) transmittance of 99.9%-99%, or 99%-98%, or 98%-97%, or 97%-96%, or 96%-95%, or 95%-90%, or 90%-85%, or 85%-80%, or 80%-75%, or 75%-70%, or 70%-65%, or 65%-60%, 60%-55%, 55%-50%, 50%-45%, 45%-40%, 40%-35%, 35%-30%, 30%-25%, 25%-20%, 20%-15%, or 15%-10% for films less than 5 microns.

[0185] The transmittance of a film according to the present disclosure may be the normal transmittance measured using a Perkin Elmer UV-Vis Lambda 850 spectrophotometer, where the film is optically transparent. It is coated onto a clear substrate, such as a fused silica or glass substrate, and a blank substrate of the same type and thickness is used as a reference. The ripples in the spectrum are the result of interference between the incident and reflected light and usually indicate that the film is of high quality, i.e., high smoothness, high uniformity, and high transmittance.

[0186] Nanocomposite coatings or films of the present disclosure made using the disclosed methods of making nanocomposites with the formulations described herein may have a percent haze of less than 0.5% or between 0.5 and 1.0% for films less than 5 microns. The percent haze of films according to the present disclosure is measured using a HunterLab Vista Hazemeter, where the films are applied onto optically clear substrates such as fused silica or glass substrates.

[0187] Nanocomposite coatings or films of the present disclosure made using the disclosed methods of making nanocomposites with the formulations described herein may further exhibit thermal stability at temperatures below 150° C. Thermal stability may be measured by subjecting the nanocomposite coating or film to a specified temperature in air, nitrogen, or under vacuum for 5 minutes or more, or 10 minutes or more, or 30 minutes or more, or 60 minutes or more, or 120 minutes or more without visible discoloration, cracking, or delamination.

[0188] Thermal stability may be measured by placing the coating or film at 150°C in vacuum or nitrogen for 120 minutes, and the average change in light transmittance from 400 nm to 800 nm, when normalized to a 1 μm film, is 5% to 10%, or 2% to 5%, or 1% to 2%, or 0.1% to 1%, or 0.001% to 0.1%. Normalization may be performed by converting the transmittance to absorptance, dividing the absorptance by the film thickness in micrometers, and then converting the result back to transmittance for a 1 μm film.

[0189] A film that is a coating or film of a nanocomposite of the present disclosure made using a method of making a nanocomposite using a formulation described herein, wherein the amount of at least partially capped nanocrystals in the film is 10%-20%, or 20%-30%, or 30%-40%, or 40%-50%, or 50%-60%, or 60%-70%, or 70%-75%, or 75%-80%, or 80%-85%, or 85%-90%, or 90%-93% by weight of the nanocomposite film.

[0190] A film that is a coating or film of a nanocomposite of the present disclosure made using a method of making a nanocomposite using a formulation described herein, wherein the amount of at least partially capped nanocrystals in the film is 10%-20%, or 20%-30%, or 30%-40%, or 40%-50%, or 50%-60%, or 60%-70%, or 70%-75%, or 75%-80%, or 80%-85%, or 85%-90%, or 90%-93% by weight of the nanocomposite binder.

[0191] In some embodiments, the present disclosure provides a method for producing at least partially capped TiO 2 Provided is a nanocomposite film comprising nanocrystals and at least one monomer, oligomer, and / or polymer, wherein the at least partially capped nanocrystals are present in an amount greater than 50%, e.g., greater than 60%, greater than 70%, greater than 80%, or greater than 90%, by weight of the nanocomposite, e.g., about 55%, about 60%, about 70%, about 80%, about 90%, or any range between the recited values, e.g., about 55-90%, about 60-90%, about 70-90%, etc. At least partially capped TiO 2 The nanocrystals can be any of those described herein. For example, in some embodiments, the film is made of methyltrimethoxysilane, n-octyltrimethoxysilane, methoxy(triethyleneoxy)propyl 1. The TiO described herein, at least partially capped with a capping agent selected from trimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, and combinations thereof. 2Nanocrystals may be included, preferably the capping agent is selected from methyltrimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and combinations thereof, more preferably the capping agent is selected from methoxy(triethyleneoxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, and combinations thereof, for example the capping agent is methoxy(triethyleneoxy)propyltrimethoxysilane. In some embodiments, the at least partially capped TiO 2 The nanocrystals are in substantially pure form, e.g., TiO 2 The capping agent used to cap the nanocrystals, and TiO 2The monomers, oligomers, and / or polymers are free or substantially free of by-products resulting from capping the nanocrystals. The monomers, oligomers, and / or polymers can also be any of those described herein, such as acrylate, epoxy, or isocyanurate compounds. In some preferred embodiments, the monomers, oligomers, and / or polymers are, for example, bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), bisphenol A ethoxylate diacrylates, bisphenol A propoxylate diacrylate, bisphenol F ethoxylate (2 EO / phenol) diacrylate, bisphenol A glycerolate diacrylates, bisphenol A ethoxylate dimethacrylate, ethoxylated (4) bisphenol A diacrylate (SR-601), bisphenol A ethoxylate diacrylate (SR-349), tris(2-acryloyloxy)ethyl}isocyanurate, tricyclodecane dimethanol diacrylate, tris(2-hydroxyethyl)isocyanurate triacrylate, cresol novolac epoxy acrylate (CN112C60), benzyl methacrylate (BMA), benzyl acrylate, trimethylolpropane triacrylate (TMPTA), trimethylolpropane ethoxylate (1 EO / OH) methyl ether diacrylate, 1,6-hexanediol diacrylate (HDDA, SR238B), tri(ethylene glycol) diacrylate, ethylene glycol diacrylate, poly(ethylene glycol) diacrylate, glycerol 1,3-diglycerolate diacrylate, di(ethylene glycol) diacrylate, and combinations thereof.In some embodiments, the monomers, oligomers, and / or polymers are selected from the group consisting of bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), bisphenol A ethoxylate diacrylates, bisphenol A propoxylate diacrylate, bisphenol F ethoxylate (2 EO / phenol) diacrylate, bisphenol A glycerolate diacrylates, bisphenol A ethoxylate dimethacrylate, ethoxylated (4) bisphenol A diacrylate. (SR-601), biphenol A ethoxylate diacrylate (SR-349), cresol novolac epoxy acrylate (CN112C60), and combinations thereof, preferably the monomer, oligomer, and / or polymer is selected from bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), ethoxylated (4) bisphenol A diacrylate (SR-601), biphenol A ethoxylate diacrylate (SR-349), cresol novolac epoxy acrylate (CN112C60), and combinations thereof, for example, the monomer, oligomer, and / or polymer is bisphenol A glycerolate dimethacrylate.

[0192] The nanocomposite films herein typically contain TiO as measured by DLS as a 5% nanocrystal dispersion in PGMEA. 2 The average particle size of the nanocrystals is in the range of 1-5 nm, 5-10 nm, 10-15 nm, 15-20 nm, 20-30 nm, 30-40 nm, or 40-50 nm, and D9999 is less than 100 nm.

[0193] In some embodiments, the nanocomposite films herein have a % transmission of a 1 micron thick film at a wavelength of 400 nm that is greater than 80%, e.g., greater than 85%, greater than 90%, greater than 95%, greater than 97%, greater than 98%, greater than 99%, e.g., about 85%, about 90%, about 95%, about 97%, about 98%, about 99%, about 99.5%, or any range between the recited values, e.g., about 90-99%, and at a wavelength of 500 nm that is greater than 80%, e.g., greater than 85%, greater than 90%, greater than 95%, greater than 97%, greater than 98%, greater than 99%, e.g., about 85%, about 90%, about 95%, about 97%, about 98%, about 99%, about 99.5%, or any range between the recited values. and at a wavelength of 600 nm, greater than 80%, for example, greater than 85%, greater than 90%, greater than 95%, greater than 97%, greater than 98%, greater than 99%, for example, about 85%, about 90%, about 95%, about 97%, about 98%, about 99%, about 99.5%, or any range between the values ​​recited, for example, about 90-99%; and at a wavelength of 800 nm, greater than 80%, for example, greater than 85%, greater than 90%, greater than 95%, greater than 97%, greater than 98%, greater than 99%, for example, about 85%, about 90%, about 95%, about 97%, about 98%, about 99%, about 99.5%, or any range between the values ​​recited, for example, about 90-99%.In some embodiments, the nanocomposite films herein also have a .DELTA. of about 1.70 to about 2.10, e.g., 1.70 to 1.70, or 1.70 to 1.72, or 1.72 to 1.74, or 1.76 to 1.78, or 1.78 to 1.80, or 1.80 to 1.82, or 1.82 to 1.86, at 448 nm, when measured using a prism coupler for films having a thickness of <5 um. 1.84, or 1.84-1.86, or 1.86-1.88, or 1.88-1.90, or 1.90-1.92, or 1.92-1.94, or 1.94-1.96, or 1.96-1.98, or 1.98-2.00, or 2.00-2.02, or 2.02-2.04, or 2.04-2.06, or 2.06-2.08, or 2.08-2. 10, and at 635 nm, it can have a refractive index of 1.60 to 1.62, or 1.62 to 1.64, or 1.64 to 1.66, or 1.66 to 1.68, or 1.68 to 1.70, or 1.70 to 1.72, or 1.72 to 1.74, or 1.76 to 1.78, or 1.78 to 1.80, or 1.80 to 1.82, or 1.82 to 1.84, or 1.84 to It may have a refractive index of 1.86, or 1.86 to 1.88, or 1.88 to 1.90, or 1.90 to 1.92, or 1.92 to 1.94, or 1.94 to 1.96, or 1.96 to 1.98, or 1.98 to 2.00, or 2.00 to 2.02, or 2.02 to 2.04, or 2.04 to 2.06, or 2.06 to 2.08, or 2.08 to 2.10. In some embodiments, the nanocomposite films herein can also have a hardness, as measured by nanoindentation, of greater than 50 MPa, greater than 100 MPa, or greater than 200 MPa, or greater than 300 MPa, or greater than 400 MPa, e.g., about 55 MPa, about 100 MPa, about 200 MPa, about 300 MPa, about 400 MPa, about 500 MPa, or any range between the recited values, e.g., about 50-500 MPa, or about 100-400 MPa.In some embodiments, the nanocomposite films herein may also be characterized as having a percent absorption of less than 0.1%, less than 0.05%, or less than 0.01% at a wavelength of 450 nm as measured by an integrating sphere for a film having a thickness of 1 micron. In some embodiments, the nanocomposite films herein may also be characterized as having a percent absorption of less than 0.1%, less than 0.05%, or less than 0.01% at a wavelength of 450 nm as measured by an AFM for an area of ​​5 microns by 5 microns. In some embodiments, the nanocomposite films herein can have a surface roughness of Ra less than 1 nm. In some embodiments, the nanocomposite films herein can also be characterized in that the haze of the nanocomposite film is less than 0.1%, or less than 0.2%, or less than 0.3%, or less than 0.4%, or less than 0.5%, or less than 1% (e.g., from about 0.01% to about 0.1%, from about 0.1% to about 0.2%, from about 0.1% to about 0.5%, from about 0.2% to about 0.5%, or from about 0.1% to about 1%) as measured by a haze meter, and b* is less than 1, or less than 0.5, or less than 0.1 (e.g., from about 0.01 to about 0.1, from about 0.1 to about 0.5, from about 0.1 to about 0.2, or from about 0.1 to about 1). In some embodiments, the nanocomposite films herein can also be characterized in that the haze of the nanocomposite film is less than 0.1%, or less than 0.2%, or less than 0.3%, or less than 0.4%, or less than 0.5%, or less than 1%, and the at least partially capped nanocrystals are uniformly dispersed throughout the film without agglomeration, as observed by uniform particle distribution in TEM, SEM, or EDX images, providing a uniform RI distribution.

[0194] The nanocomposite films herein can typically be prepared by a method that includes mixing the respective components of the nanocomposite formulation and, optionally, curing the nanocomposite formulation. In some embodiments, the method includes preparing at least a partially capped TiO 2The method includes mixing the nanocrystals with at least one monomer, oligomer, and / or polymer to provide a nanocomposite formulation, and optionally curing the nanocomposite formulation to provide a nanocomposite film. In some embodiments, the method includes forming an at least partially capped TiO film in a solvent. 2 The method includes mixing the nanocrystals with at least one monomer, oligomer, and / or polymer to provide a nanocomposite formulation, and optionally curing the nanocomposite formulation to provide a nanocomposite film. In some embodiments, the method includes forming an at least partially capped TiO 2 The method includes mixing the nanocrystals, a curing agent, and at least one monomer, oligomer, and / or polymer to provide a nanocomposite formulation, and optionally curing the nanocomposite formulation to provide a nanocomposite film. In some embodiments, the method includes forming an at least partially capped TiO film in a solvent. 2 The method includes mixing the nanocrystals, a curing agent, and at least one monomer, oligomer, and / or polymer to provide a nanocomposite formulation, and optionally curing the nanocomposite formulation to provide a nanocomposite film. 2 The nanocrystals can typically be prepared according to any one of the methods described herein. In some embodiments, the at least partially capped TiO 2 The TiO nanocrystals are prepared by any of the methods described herein. 2 It can be prepared from nanocrystals.

[0195] The nanocomposite film herein can be used in various devices. In some embodiments, the present disclosure can include any of the nanocomposite films herein. In some embodiments, the device is an optoelectronic device, a photovoltaic device, a catalytic device, a fuel cell, a battery, a smart window, a sensor, a CMOS sensor, an LED, a mini LED, a micro LED, an organic LED (OLED), a quantum LED (QLED), a touch screen, a display, a flexible electronics device, a printed electronics device, an augmented reality, a virtual reality, a mixed reality, a waveguide, a grating, or a solar cell device. In some embodiments, the device is a light emitting diode device, for example, having a lens structure as an internal light extraction layer, and the internal light extraction layer comprises the nanocomposite film herein. Scattering Composite

[0196] The disclosed method of making nanocomposites using the formulations described herein that contain scatterers The film thickness of the nanocomposite coatings or films of the present disclosure made with may range from 50 nanometers to 100 micrometers.

[0197] Nanocomposite coatings or films of the present disclosure made using the disclosed methods of making nanocomposites using formulations described herein that include scatterers have a refractive index of 1.60-1.62, or 1.62-1.64, or 1.64-1.66, or 1.66-1.68, or 1.68-1.70, or 1.70-1.72, or at 448 nm, when measured using a prism coupler for films having a thickness of <5 um. 1.72 to 1.74, or 1.76 to 1.78, or 1.78 to 1.80, or 1.80 to 1.82, or 1.82 to 1.84, or 1.84 to 1.86, or 1.86 to 1.88, or 1.88 to 1.90, or 1.90 to 1.92, or 1.92 to 1.94, or 1.94 to 1.96, or 1.96 to 1.98, or 1.98 to 2.00, or 2.00 to 2.02, or 2.02 to 2 It may have a refractive index of 1.60 to 1.62, or 1.62 to 1.64, or 1.64 to 1.66, or 1.66 to 1.68, or 1.68 to 1.70, or 1.70 to 1.72, or 1.72 to 1.74, or 1.76 to 1.78, or 1.78 to 1.80, or 1.80 to 1.82, or 1. It may have a refractive index of 82 to 1.84, or 1.84 to 1.86, or 1.86 to 1.88, or 1.88 to 1.90, or 1.90 to 1.92, or 1.92 to 1.94, or 1.94 to 1.96, or 1.96 to 1.98, or 1.98 to 2.00, or 2.00 to 2.02, or 2.02 to 2.04, or 2.04 to 2.06, or 2.06 to 2.08, or 2.08 to 2.10.

[0198] A coating or film of a nanocomposite of the present disclosure made using the disclosed method of making a nanocomposite using a formulation described herein containing scatterers, wherein the film is at least 1-2 micrometers thick and contains scatterers having a surface roughness of 5-4 nm, or 4-3 nm, or 3-2 nm, or 2-1 nm, or 1-0.5 nm.

[0199] Nanocomposite coatings or films of the present disclosure made using the disclosed methods of making nanocomposites using the formulations described herein that contain scatterers have a percent solubility of 99.99%-99%, or 99%-98%, or 98%-97%, or 97%-96%, or 96%-95%, or 95%-96% for films less than 5 microns, as measured at a wavelength of 400 nm. The film may have a vertical transmittance of 90% to 85%, 85% to 80%, 80% to 75%, 75% to 70%, 70% to 65%, 65% to 60%, 60% to 55%, 55% to 50%, 50% to 45%, 45% to 40%, 40% to 35%, 35% to 30%, 30% to 25%, 25% to 20%, 20% to 15%, or 15% to 10%.

[0200] Nanocomposite coatings or films of the present disclosure made using the disclosed methods of making nanocomposites with the formulations described herein that contain scatterers have a percent solubility of 99.99%-99%, or 99%-98%, or 98%-97%, or 97%-96%, or 96%-95%, or 95%-96% for films less than 5 microns, as measured at a wavelength of 500 nm. The film may have a vertical transmittance of 90% to 85%, 85% to 80%, 80% to 75%, 75% to 70%, 70% to 65%, 65% to 60%, 60% to 55%, 55% to 50%, 50% to 45%, 45% to 40%, 40% to 35%, 35% to 30%, 30% to 25%, 25% to 20%, 20% to 15%, or 15% to 10%.

[0201] Nanocomposite coatings or films of the present disclosure made using the disclosed method of making nanocomposites using the formulations described herein that contain scatterers have wavelengths of 600 nm. For films less than 5 microns, as measured at length, the film may have a vertical transmittance of 99.99%-99%, or 99%-98%, or 98%-97%, or 97%-96%, or 96%-95%, or 95%-90%, or 90%-85%, or 85%-80%, or 80%-75%, or 75%-70%, or 70%-65%, or 65%-60%, 60%-55%, 55%-50%, 50%-45%, 45%-40%, 40%-35%, 35%-30%, 30%-25%, 25%-20%, 20%-15%, or 15%-10%.

[0202] Nanocomposite coatings or films of the present disclosure made using the disclosed methods of making nanocomposites with the formulations described herein containing scatterers may have a percent haze of less than 0.5%, or 0.5-1.0%, or 1.0-10.0%, or 10-20%, or 20-30%, or 30-40%, or 40-50%, or 50-60%, or 60-70%, or 70-80%, or 80-90%, or 90-100% for films less than 5 microns. The percent haze of films according to the present disclosure is measured using a Hunter Lab Vista Haze Meter.

[0203] The disclosed nanocomposite coatings or films made using the disclosed methods of making nanocomposites with the formulations described herein that contain scatterers may further exhibit thermal stability at temperatures below 150° C. Thermal stability may be measured by subjecting the nanocomposite coatings or films to a specified temperature in air, nitrogen, or under vacuum for 5 minutes or more, or 10 minutes or more, or 30 minutes or more, or 60 minutes or more, or 120 minutes or more without visible discoloration, cracking, or delamination.

[0204] Thermal stability may be measured by placing the coating or film at 150°C in air, nitrogen or vacuum for 120 minutes or more and measuring the average change in light transmittance from 400 nm to 800 nm, when normalized to a 1 μm film, of 5% to 10%, or 2% to 5%, or 1% to 2%, or 0.1% to 1%, or 0.001% to 0.1%. Normalization may be performed by converting the transmittance to absorptance, dividing the absorptance by the film thickness in micrometers, and then converting the result back to transmittance for a 1 μm film.

[0205] A coating or film of a nanocomposite of the present disclosure made using a method of making a nanocomposite using a formulation described herein containing scatterers, wherein the amount of at least partially capped nanocrystals in the film is 10%-20%, or 20%-30%, or 30%-40%, or 40%-50%, or 50%-60%, or 60%-70%, or 70%-75%, or 75%-80%, or 80%-85%, or 85%-90%, or 90%-93% by weight of the nanocomposite film.

[0206] A coating or film of a nanocomposite of the present disclosure made using a method of making a nanocomposite using a formulation described herein containing scatterers, wherein the amount of at least partially capped nanocrystals in the film is 10%-20%, or 20%-30%, or 30%-40%, or 40%-50%, or 50%-60%, or 60%-70%, or 70%-75%, or 75%-80%, or 80%-85%, or 85%-90%, or 90%-93% by weight of the nanocomposite binder. Device

[0207] The present disclosure provides a light emitting diode device including an internal light extraction layer, the internal light extraction layer comprising a high refractive index nanocomposite with or without scatterers of the present disclosure.

[0208] The present disclosure further provides methods for producing optoelectronic devices, photovoltaic devices, catalysts, and the like, comprising the active component. A device, fuel cell, battery, smart window, sensor, CMOS sensor, LED, mini LED, micro LED, organic LED (OLED), quantum LED (QLED), touch screen, display, flexible electronics device, printed electronics device, augmented reality, virtual reality, mixed reality, waveguide, diffraction grating, or solar cell device is provided, wherein the active component comprises or contains the nanocomposite of the present disclosure.

[0209] The present disclosure provides a light emitting diode device including a lens structure as an internal light extraction layer, the internal light extraction layer including a coating or film of a high refractive index nanocomposite of the present disclosure, and the refractive index of the lens structure may be stepped or have a gradient refractive index profile.

[0210] The following are non-limiting examples of embodiments of the present disclosure. EXAMPLES

[0211] Example 1 Titanium dioxide (TiO 2 ) Synthesis of nanocrystals: Titanium oxide nanocrystals with sizes ranging from 1 to 1500 nm can be prepared from precursors such as titanium(IV) methoxide, titanium(IV) ethoxide, titanium(IV) propoxide, titanium(IV) isopropoxide, titanium(IV) butoxide, or titanium(IV) oxyacetylacetonate. Titanium n-butoxide, chlorotriisopropoxytitanium(IV), titanium n-propoxide, titanium(IV) chloride, titanium chloride tri-n-butoxide, or titanium dichloride diethoxide may be advantageously used as precursors, depending on the desired end product.

[0212] In an exemplary method, a titanium alkoxide precursor, such as titanium n-butoxide, titanium n-propoxide, titanium isopropoxide, or titanium ethoxide, is mixed with water, which acts as a reagent, and a solvent or mixture of solvents, such as benzyl alcohol, phenol, oleyl alcohol, butanol, propanol, isopropanol, tetrahydrofuran, ethanol, methanol, acetonitrile, toluene, PGMEA, propylene glycol propyl ether (PGPE), PGME, 2-methyl-1-propanol, or triethylene glycol monomethyl ether, and sealed in an autoclave. The reaction mixture is heated to a temperature between 140 and 300°C. Once the reaction mixture reaches the set temperature, the temperature is maintained for a period ranging from 20 minutes to 24 hours, depending on the solvent or solvent mixture and / or the temperature of the reaction. The as-synthesized titanium oxide nanocrystals are collected as a white milky suspension.

[0213] The milky white suspension was then collected and transferred to a centrifuge bottle. The suspension was then centrifuged at 1500 rpm for 5 minutes. The supernatant was then decanted, forming a wet cake at the bottom of the centrifuge bottle. The wet cake was washed with PGMEA at a weight ratio of 2.75:1 solvent to wet cake and vigorously stirred. The suspension was then centrifuged again at 1500 rpm for 5 minutes, and the resulting supernatant was decanted from the top. The wet cake was then transferred to a 250 ml round bottom flask. PGMEA was added at a weight ratio of 1.857:1 solvent to wet cake. Then, a capping agent, for example, methyltrimethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, phenyltrimethoxysilane, dodecyltrimethoxysilane, m,p-ethylphenethyltrimethoxysilane, 2-[methoxy(polyethyleneoxy)propyl]trimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 3-(meth ... Silane, 3-isocyanatopropyltriethoxysilane, 3-isocyanatopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 1-hexenyltrimethoxysilane, 1-octenyltrimethoxysilane, phenylaminomethyl)methyldimethoxysilane, N-phenylaminopropyltrimethoxysilane, 3-(4-pyridylethyl)thiopropyltrimethoxysilane, N-(3-trimethoxysilylpropyl)pyrrole, 2- (3-trimethoxysilylpropylthio)thiophene, (3-trimethoxysilylpropyl)diethylenetriamine, 11-mercaptoundecyltrimethoxysilane, (2-diphenylphosphino)ethyldimethylethoxysilane, 2-(diphenylphosphino)ethyltriethoxysilane, 3-(diphenylphosphino)propyltriethoxysilane, heptanol, hexanol, octanol, benzyl alcohol, phenol, ethanol, propanol, butanol, oleyl alcohol, dodecyl alcohol alcohol, octadecanol, triethylene glycol monomethyl ether, octanoic acid, acetic acid, propionic acid, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, benzoic acid, stearic acid, trifluoroacetic acid, biphenyl-4-carboxylic acid, 2-(2-methoxyethoxy)acetic acid, methacrylic acid, mono-2-(methacryloyloxy)ethyl succinate, 2-mercaptoethanol, 2-{2-(2-mercaptoethoxy)ethoxy}ethanol, 2-(2-methoxyethoxy)ethanethiol, 1-octanoic acid, A mixture of 11-mercaptoundecyl, 2,3-dimercaptopropanesulfonate sodium monohydrate, sodium dodecyl sulfate, dodecylphosphonic acid, octylphosphonic acid, (11-mercaptoundecyl)phosphonic acid, (11-(acryloyloxy)undecyl)phosphonic acid, 11-methacryloyloxyundecylphosphonic acid, [2-[2-(2-methoxyethoxy)ethoxy]ethyl]phosphonic acid ethyl ester, and any combination thereof, was added to the reaction flask in a ratio of 1:5 capping agent to wet cake by weight. The mixture was then heated to 120° C. for 1 hour.The reaction was cooled and all the wet cake was dispersed in the solution, which took on a salmon colored appearance.

[0214] The reaction mixture was then washed to remove excess capping agent and impurities. The reaction mixture was then precipitated in an anti-solvent, e.g., heptane, at a weight ratio of 2:1 heptane to the reaction mixture. The precipitate was centrifuged at 4500 rpm for 10 minutes. The resulting supernatant was decanted and discarded. The solids were then dispersed in THF. The dispersed solids were then precipitated again in an anti-solvent, e.g., heptane, at a weight ratio of 2:1 heptane to the reaction mixture. The precipitate was centrifuged at 4500 rpm for 10 minutes. The resulting supernatant was decanted and discarded. The solids were then dispersed in THF. The dispersed solids were then precipitated a third time in an anti-solvent, e.g., heptane, at a weight ratio of 2:1 heptane to the reaction mixture. The precipitate was centrifuged at 4500 rpm for 10 minutes. The resulting supernatant was decanted and discarded. The solids were then dried in a vacuum oven overnight.

[0215] The dried solids were redispersed in PGMEA at a 1:1 ratio of solids to solvent to create a dispersion at 50 wt% loading. The resulting dispersion was filtered through a 0.45 micron and then a 0.2 micron PTFE filter. Example 2

[0216] In one example, titanium oxide nanocrystals were prepared from a mixture of 100 mmol of titanium(IV) butoxide, 500 mmol of water, and 418 mL of benzyl alcohol in an inert atmosphere sealed in an autoclave. The reaction mixture was heated to 200 °C at a heating rate of 2 °C / min. Once the reaction mixture reached 200 °C, the temperature was maintained for 20-60 minutes. After cooling the autoclave to room temperature, the as-synthesized TiO 2 A white milky solution of nanocrystals was recovered.

[0217] The milky white suspension was then collected and transferred to a centrifuge bottle. The suspension was then centrifuged at 1500 rpm for 5 minutes. The supernatant was then decanted, leaving a wet cake at the bottom of the centrifuge bottle. The wet cake was washed with PGMEA in a ratio of 2.75:1 solvent by weight to the wet cake and vigorously stirred. The suspension was then centrifuged again at 1500 rpm for 5 minutes, and the resulting supernatant was decanted off. The collected wet cake was then transferred to a 250 ml round bottom flask. PGMEA was added in a ratio of 0.3:1 solvent by weight to the wet cake. Methoxy(triethyleneoxy)propyltrimethoxysilane was then added to the reaction flask in a ratio of 1:10 capping agent by weight to the wet cake. The mixture was then refluxed at 120° C. for 1 hour, at which point it became a clear dispersion. The reaction mixture was then cooled to room temperature for further processing.

[0218] The solution was filtered through 0.45 micron and then 0.2 micron PTFE filters to give a dispersion at 50% weight loading. Example 3

[0219] In one example, titanium oxide nanocrystals were prepared from a mixture of 100 mmol of titanium(IV) butoxide, 500 mmol of water, and 418 mL of benzyl alcohol in an inert atmosphere sealed in an autoclave. The reaction mixture was heated to 225 °C at a heating rate of 2 °C / min. Once the reaction mixture reached 225 °C, the temperature was maintained for 20-60 minutes. After cooling the autoclave to room temperature, the as-synthesized TiO 2 A white milky solution of nanocrystals was recovered.

[0220] The milky white suspension was then transferred to a centrifuge bottle and centrifuged at 1500 rpm for 5 minutes. The supernatant was then decanted, leaving a wet cake at the bottom of the centrifuge bottle. The wet cake was washed with PGMEA in a solvent ratio of 2.75:1 by weight to the wet cake and vigorously stirred. The suspension was then centrifuged again at 1500 rpm for 5 minutes and the resulting supernatant was decanted off, leaving a wet cake. The wet cake was then transferred to a 250 ml round bottom flask. PGMEA was added in a solvent ratio of 0.3:1 by weight to the wet cake. 2-[2-(2-methoxyethoxy)ethoxy]acetic acid was then added to the reaction flask in a capping agent ratio of 1:10 by weight to the wet cake. The mixture was then heated to 60° C. for 1 hour, at which point it became a clear dispersion. The reaction mixture was then cooled to room temperature for further processing.

[0221] The solution was filtered through 0.45 micron and then 0.2 micron PTFE filters to give a dispersion at 50% weight loading. Example 4

[0222] In one example, titanium dioxide nanocrystals were prepared from 2583 mmol of titanium(IV) butoxide, 6457 mmol of water, and 3400 mL of benzyl alcohol in an inert atmosphere and transferred to a 2 gallon Parr reactor. The reaction mixture was heated to 200-225°C at a heating rate of 2°C / min for 1-2 hours. The reaction pressure reached 50-150 psi. Upon completion of the reaction and allowing the reactor to return to room temperature, a white milky solution of as-synthesized titanium dioxide nanocrystals was collected.

[0223] The milky white suspension was then transferred to a centrifuge bottle and centrifuged at 1500 rpm for 5 minutes. The supernatant was then decanted, leaving a wet cake at the bottom of the centrifuge bottle. The wet cake was washed with PGMEA at a solvent ratio of 2.75 to 1 by weight relative to the wet cake and vigorously stirred. The suspension was then centrifuged at 1500 rpm for 5 minutes. The resulting supernatant liquid was decanted off, leaving a wet cake. The wet cake was then transferred to a 3000 ml round bottom flask. PGMEA was added to the reaction flask at a ratio of 1.857:1 solvent by weight to the wet cake. Methoxy(triethyleneoxy)propyltrimethoxysilane was then added to the reaction flask at a ratio of 1:5 capping agent by weight to the wet cake. Also, 3-(acryloyloxy)propyltrimethoxysilane was added to the reaction flask at a ratio of 1:50 capping agent by weight to the wet cake. The mixture was then heated to 120° C. for 1 hour, at which point it became a clear dispersion. The reaction mixture was then cooled to room temperature for further processing.

[0224] The capped nanocrystals were purified by washing to remove excess capping agent and other by-products. The capped nanocrystals were precipitated from the reaction mixture using an anti-solvent, e.g., heptane, in a ratio of 2:1 heptane by weight to the reaction mixture. The precipitate was collected by centrifugation at 4500 rpm for 10 minutes. The resulting supernatant was decanted and discarded. The collected solids were then dispersed in THF. The dispersed solids were again precipitated in an anti-solvent, e.g., heptane, in a ratio of 2:1 heptane by weight to the reaction mixture. The precipitate was collected by centrifugation at 4500 rpm for 10 minutes. The resulting supernatant was decanted and discarded. The collected solids were then dispersed in THF. The dispersed solids were precipitated a third time in an anti-solvent, e.g., heptane, in a ratio of 2:1 heptane by weight to the reaction mixture. The precipitate was collected by centrifugation at 4500 rpm for 10 minutes and dried in a vacuum oven overnight.

[0225] The dried solids were redispersed in PGMEA at a 1:1 ratio of solids to solvent by weight to create a dispersion at 50 wt% loading. The resulting dispersion was filtered through a 0.45 micron and then a 0.2 micron PTFE filter. Example 5

[0226] In one example, titanium dioxide nanocrystals were prepared from 2583 mmol of titanium(IV) butoxide, 6457 mmol of water, and 3400 mL of benzyl alcohol in an inert atmosphere and transferred to a 2 gallon Parr reactor. The reaction mixture was heated to 200-225°C at a heating rate of 2°C / min for 1-2 hours. The reaction pressure reached 50-150 psi. Upon completion of the reaction and allowing the reactor to return to room temperature, a white milky solution of as-synthesized titanium dioxide nanocrystals was collected.

[0227] The milky white suspension was then transferred to a centrifuge bottle and centrifuged at 1500 rpm for 5 minutes. The supernatant was then decanted, leaving a wet cake at the bottom of the centrifuge bottle. The wet cake was washed with PGMEA at a solvent ratio of 2.75:1 by weight to the wet cake and vigorously stirred. The suspension was then centrifuged again at 1500 rpm for 5 minutes and the resulting supernatant was decanted off the top, leaving a wet cake. The wet cake was then transferred to a 3000 ml round bottom flask. PGMEA was added at a solvent ratio of 1.857:1 by weight to the wet cake. Methoxy(triethyleneoxy)propyltrimethoxysilane was then added to the reaction flask at a capping agent ratio of 1:5 by weight to the wet cake. 3-(acryloyloxy)propyltrimethoxysilane was also added to the reaction flask at a capping agent ratio of 1:50 by weight to the wet cake. The mixture was then heated to 120° C. for 1 hour, at which point it became a clear dispersion. The reaction mixture was then cooled to room temperature for further processing.

[0228] The capped nanocrystals were purified by washing to remove excess capping agent and other by-products. The capped nanocrystals were precipitated from the reaction mixture using an anti-solvent, e.g., heptane, in a ratio of 2:1 heptane to reaction mixture by weight. The precipitate was collected for 4 h. The solids were collected by centrifugation at 500 rpm for 10 minutes. The resulting supernatant was decanted and discarded. The collected solids were then dispersed in THF and precipitated again from the reaction mixture using an anti-solvent, e.g., heptane, in a weight ratio of 2:1 heptane to the reaction mixture. The precipitate was collected by centrifugation at 4500 rpm for 10 minutes. The resulting supernatant was decanted and discarded. The solids were then dispersed in THF. The dispersed solids were then precipitated a third time from the reaction mixture using an anti-solvent, e.g., heptane, in a weight ratio of 2:1 heptane to the reaction mixture. The precipitate was collected by centrifugation at 4500 rpm for 10 minutes and dried in a vacuum oven overnight.

[0229] The dried solids were redispersed in PGMEA at a ratio of 1:0.43 solids to solvent by weight to create a dispersion at 65 wt% loading. The resulting dispersion was filtered through a 0.45 micron and then a 0.2 micron PTFE filter. Example 6

[0230] In another example, 879 g of 100% (w / w) titanium(IV) n-butoxide was mixed with 3550 g of benzyl alcohol and 116.3 g of water in an inerted 2 gallon Parr reactor. The setup was sealed under inert conditions, e.g., nitrogen atmosphere, to prevent oxygen contamination. The Parr reactor was then heated to 200° C. with stirring at 600 rpm and maintained at this temperature for 1 hour. After the reaction, the reactor was cooled to room temperature and a white milky solution of as-synthesized titanium oxide nanocrystals was collected.

[0231] The milky white suspension was then transferred to a centrifuge bottle and centrifuged at 1500 rpm for 5 minutes. The supernatant was then decanted, leaving a wet cake at the bottom of the centrifuge bottle. The wet cake was washed with PGMEA in a solvent ratio of 2.75:1 by weight to the wet cake and vigorously stirred. The suspension was then centrifuged again at 1500 rpm for 5 minutes, the resulting supernatant was decanted off the top, and the wet cake was allowed to settle. The wet cake was then transferred to a 3000 ml round bottom flask. PGMEA was added in a solvent ratio of 1.857:1 by weight to the wet cake. Methoxy(triethyleneoxy)propyltrimethoxysilane was then added to the reaction flask in a capping agent ratio of 1:5 by weight to the wet cake. This mixture was then heated to 120° C. for 40 minutes. Methacryloxypropyltrimethoxysilane was then added to the reaction flask in a capping agent ratio of 1:3 by weight to the wet cake. The mixture was heated at 120° C. for an additional 30 minutes at which point it became a clear dispersion. The reaction mixture was then cooled to room temperature for further processing.

[0232] The capped nanocrystals were purified by washing to remove excess capping agent and other by-products. The capped nanocrystals were precipitated from the reaction mixture using an anti-solvent, e.g., heptane, in a ratio of 2:1 heptane by weight to the reaction mixture. The precipitate was collected by centrifugation at 4500 rpm for 10 minutes. The resulting supernatant was decanted and discarded. The solids were then dispersed in THF. The dispersed solids were again precipitated using an anti-solvent, e.g., heptane, in a ratio of 2:1 heptane by weight to the reaction mixture. The precipitate was collected by centrifugation at 4500 rpm for 10 minutes. The resulting supernatant was decanted and discarded. The solids were again dispersed in THF. The dispersed solids were precipitated a third time using an anti-solvent, e.g., heptane, in a ratio of 2:1 heptane by weight to the reaction mixture. The precipitate was collected by centrifugation at 4500 rpm for 10 minutes and dried in a vacuum oven overnight.

[0233] The dried solids were redispersed in PGMEA at a 1:1 ratio of solids to solvent by weight to create a dispersion with a 50 wt% loading. and then filtered through a 0.2 micron PTFE filter. Example 7

[0234] In another example, 879 g of 100% (w / w) titanium(IV) n-butoxide was mixed with 3550 g of benzyl alcohol and 116.3 g of water in an inerted 2 gallon Parr reactor. The setup was sealed under inert conditions, e.g., nitrogen atmosphere, to prevent oxygen contamination. The Parr reactor was then heated to 250° C. with stirring at 500 rpm and maintained at this temperature for 90 minutes. After the reaction, the reactor was cooled to room temperature. A white milky solution of as-synthesized titanium oxide nanocrystals was collected.

[0235] The milky white suspension was then transferred to a centrifuge bottle and centrifuged at 1500 rpm for 5 minutes. The supernatant was then decanted, leaving a wet cake at the bottom of the centrifuge bottle. The wet cake was washed with PGMEA in a solvent ratio of 2.75:1 by weight to the wet cake and vigorously stirred. The suspension was then centrifuged again at 1500 rpm for 5 minutes, the resulting supernatant was decanted off, and the wet cake was allowed to settle. The wet cake was then transferred to a 3000 ml round bottom flask. PGMEA was added in a solvent ratio of 1.857:1 by weight to the wet cake. Methoxy(triethyleneoxy)propyltrimethoxysilane was then added to the reaction flask in a capping agent ratio of 1:5 by weight to the wet cake. This mixture was then heated to 120° C. for 30 minutes. Methacryloxypropyltrimethoxysilane was then added to the reaction flask in a capping agent ratio of 4:5 by weight to the wet cake. The mixture was then heated at 120° C. for 30 minutes. Water was then added to the reaction mixture at a ratio of 1:20 capping agent to wet cake by weight. The mixture was heated at 100° C. for an additional 20 minutes at which point a clear dispersion was obtained. The reaction mixture was then cooled to room temperature for further processing.

[0236] The capped nanocrystals were purified by washing to remove excess capping agent and other by-products. The capped nanocrystals wer...

Claims

1. Titanium dioxide precursor is dissolved in a solvent to form TiO 2 including converting TiO to nanocrystals. 2 A method of preparing nanocrystals, the solvent being mostly other than water, the converting comprising: 1) mixing a titanium dioxide precursor in a solvent to provide a reaction mixture; and 2) heating the reaction mixture at a reaction temperature, e.g., from about 180° C. to about 250° C., from about 200° C. to about 210° C., for a period of time to form TiO. 2 A method for providing nanocrystals.

2. The conversion may include 1) mixing a precursor of titanium dioxide in a solvent, optionally with water, to provide a reaction mixture; and 2) heating the reaction mixture at a reaction temperature, e.g., from about 180° C. to about 250° C., from about 200° C. to about 210° C., for a period of time to form TiO. 2 The method of claim 1 comprising providing a nanocrystal.

3. The conversion may include 1) adding a titanium dioxide precursor and, optionally, water to a solvent to provide a reaction mixture; and 2) heating the reaction mixture at a reaction temperature of about 180° C. to about 250° C. (e.g., about 200° C. to about 210° C., or about 203° C. to about 207° C.) for about 10 minutes to 5 hours (e.g., 20 minutes to 1 hour, or 1-5 hours) to produce TiO. 2 and obtaining the nanocrystals.

4. The precursor of titanium dioxide is titanium alkoxide, for example, Ti(OR). 4 Titanium alkoxides having the formula Ti(OR) x G y or a combination thereof, wherein each R group can independently be an alkyl group (e.g., a C1-C6 alkyl group), or a substituted alkyl group; each occurrence of G group is independently a halogen (e.g., Cl); x is an integer from 0 to 4; and y is an integer from 0 to 4, with the proviso that x+y is 4.

5. The solvent may be benzyl alcohol, phenol, oleyl alcohol, butanol, propanol, isopropanol, ethanol, butoxyethanol, butoxypropanol, methanol, 2-(isopentyloxy)ethanol, 2-propoxy-propanol (PnP), 2-(hexyloxy)ethanol, tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, propylene glycol monomethyl ether (PGME), diethylene glycol butyl ether, dipropylene glycol methyl ether (DPGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ...

5. The method of any one of claims 1 to 4, comprising one or more solvents selected from ethyl ether, diethylene glycol, dipropylene glycol, acetone, propylene glycol methyl ether acetate (PGMEA), ethyl lactate (EL), methyl acetates, ethyl acetates, butyl acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, butoxyethyl acetate, ethyl acetate, 2-(2-butoxyethoxy)ethyl acetate, benzene, toluene, and water.

6. The method according to any one of claims 1 to 5, wherein the TiO prepared according to said method 2 The nanocrystals may be less than 50 nm (e.g., less than about 50 nm, less than about 40 nm, less than about 30 nm, less than about 20 nm, less than about 10 nm, or less than about 5 nm, e.g., about 1 nm, about 4 nm, about 5 nm, about 10 nm, about 15 nm, about 20 nm, about 35 nm, about 30 nm, about 40 nm, about 50 nm, or any range between the recited values, e.g., about 1 nm to about 5 nm, about 1 nm to about 10 nm, about 40 nm to about 50 nm, about 20 nm to about 30 nm, about 10 nm to about 20 nm, about 30 nm to about 40 nm, about 4 nm to about 50 nm, about 4 nm to about 20 nm, about 15 nm to about 20 nm, or about The method of claim 1, wherein the crystalline cellulose has an average particle size of about 10 nm to about 25 nm.

7. TiO having an average particle size of greater than 4 nm but less than 50 nm (e.g., from about 10 nm to about 25 nm, or from about 4 nm to about 20 nm) as measured by TEM. 2 A method of preparing nanocrystals includes: 1) adding a titanium dioxide precursor and water to a solvent to provide a reaction mixture; and 2) heating the reaction mixture at a reaction temperature of about 180° C. to about 250° C. (e.g., about 200° C. to about 210° C.) for about 10 minutes to 5 hours (e.g., about 20 minutes to 1 hour, or 1-5 hours) to form TiO 2 providing nanocrystals, wherein the molar ratio of titanium dioxide precursor to water is in the range of about 1:0.3 to about 1:3, e.g., about 1:0.5 to about 1:2.5, about 1:0.5 to about 1:1, about 1:1 to about 1:1.5, about 1:1.5 to about 1:2, about 1:2 to about 1:2.

5.

8. 8. The process of claim 7, wherein heating the reaction mixture at the reaction temperature is carried out under a pressure ranging from about 40 psi to about 500 psi, for example from about 40 psi to about 150 psi.

9. The precursor of titanium dioxide is titanium alkoxide, for example, Ti(OR). 4 Titanium alkoxides having the formula Ti(OR) x G y or a combination thereof, wherein each R group can independently be an alkyl group (e.g., a C1-C6 alkyl group), or a substituted alkyl group; each occurrence of G group is independently a halogen (e.g., Cl); x is an integer from 0 to 4; and y is an integer from 0 to 4, with the proviso that x+y is 4.

10. The method according to any one of claims 7 to 9, wherein the TiO prepared according to said method 2 The nanocrystals have a narrow particle size distribution, and the particle size distribution has a D of less than 5, preferably less than 3, or less than 2, for example, from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.8, from about 1.2 to about 3, or from about 1.5 to about 3. 90 :D 10 2) a ratio of D less than 3, preferably less than 2, or less than 1.5, for example from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.5 90 :D 50 and / or 3) a ratio of D less than 3, preferably less than 2, or less than 1.5, for example from about 1.1 to about 2, from about 1.5 to about 2, from about 1.2 to about 1.5 50 :D 10 The method is characterized by the ratio of

11. TiO prepared by the method according to any one of claims 1 to 10. 2 Nanocrystals.

12. The TiO according to any one of claims 1 to 10. 2 The nanocrystals are reacted with a first capping agent in a first capping solvent to form a first at least partially capped TiO 2 The present invention relates to a method for producing nanocrystals of TiO. 2 Methods for capping nanocrystals.

13. The TiO according to any one of claims 1 to 10. 2 2) mixing the nanocrystals with a first capping agent in a first capping solvent to provide a first reaction mixture; and 3) heating the first reaction mixture, for example at the reflux temperature of the first capping solvent, for a period of time (e.g., from about 10 minutes to about 120 minutes) to form a first at least partially capped TiO. 2 The method of claim 11 , further comprising: producing the nanocrystals.

14. 1) A first at least partially capped TiO 2 2) mixing the nanocrystals with a second capping agent in a second capping solvent to provide a second reaction mixture; and 2) heating the second reaction mixture, for example at the reflux temperature of the second capping solvent, for a period of time (e.g., from about 10 minutes to about 120 minutes) to form a second at least partially capped TiO. 2 The method of claim 12 or 13, further comprising producing the nanocrystals.

15. a) adding water to the first or second reaction mixture after each heating step 2); and b) heating the first or second reaction mixture for an additional period of time (e.g., from about 10 minutes to about 120 minutes).

16. The first or second capping agent may be methyltrimethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, phenyltrimethoxysilane, dodecyltrimethoxysilane, m,p-ethylphenethyltrimethoxysilane, 2-[methoxy(polyethyleneoxy)propyl]trimethoxysilane, methoxy(triethyleneoxy)propyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 4-amino ... (acryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-isocyanatopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 1-hexenyltrimethoxysilane, 1-octenyltrimethoxysilane, phenylaminomethyl)methyldimethoxysilane, N-phenylaminopropyltrimethoxysilane, 3-(4-pyridylethyl)thiopropyltrimethoxysilane , N-(3-trimethoxysilylpropyl)pyrrole, 2-(3-trimethoxysilylpropylthio)thiophene, (3-trimethoxysilylpropyl)diethylenetriamine, 11-mercaptoundecyltrimethoxysilane, (2-diphenylphosphino)ethyldimethylethoxysilane, 2-(diphenylphosphino)ethyltriethoxysilane, 3-(diphenylphosphino)propyltriethoxysilane, heptanol, hexanol, octanol, benzyl alcohol, phenol, ethanol, propanol, butanol, oleyl alcohol alcohol, dodecyl alcohol, octadecanol, triethylene glycol monomethyl ether, octanoic acid, acetic acid, propionic acid, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, oleic acid, benzoic acid, stearic acid, trifluoroacetic acid, biphenyl-4-carboxylic acid, 2-(2-methoxyethoxy)acetic acid, methacrylic acid, mono-2-(methacryloyloxy)ethyl succinate, 2-mercaptoethanol, 2-{2-(2-mercaptoethoxy)ethoxy}ethanol, 2-(2-methoxyethoxy)ethanethiol, 1-octanethiol, 2,The method according to any one of claims 11 to 15, wherein the phosphonic acid is independently selected from sodium 3-dimercaptopropanesulfonate monohydrate, sodium dodecyl sulfate, dodecylphosphonic acid, octylphosphonic acid, (11-mercaptoundecyl)phosphonic acid, (11-(acryloyloxy)undecyl)phosphonic acid, 11-methacryloyloxyundecylphosphonic acid, [2-[2-(2-methoxyethoxy)ethoxy]ethyl]phosphonic acid ethyl ester, and combinations thereof.

17. An at least partially capped TiO prepared by the method of any one of claims 12 to 16. 2 Nanocrystals.

18. 18. The at least partially capped TiO nanoparticle of claim 17, further characterized in that the D9999 is less than 500 nm (e.g., less than 200 nm, less than 100 nm, or less than 50 nm, e.g., about 10 nm, about 20 nm, about 50 nm, about 100 nm, about 200 nm, about 500 nm, or any range between the recited values, e.g., about 20 nm to about 50 nm, about 50 nm to about 100 nm, about 20 nm to about 200 nm, about 100 nm to about 200 nm, etc.) as measured by Dynamic Light Scattering (DLS) on a volume of the capped titanium dioxide nanocrystals dispersed in a solvent at 5 wt.%. 2 Nanocrystals.

19. 1. The composition of claim 1, characterized by an organic content of about 5% to about 35%, preferably about 5% to about 15%, about 10% to about 25%, or about 15% to about 30%, as measured by TGA. 7 to 18. At least partially capped TiO 2 Nanocrystals.

20. At least partially capped TiO 2 At least partially capped TiO nanocrystals are present in an amount greater than 30%, e.g., greater than 40%, greater than 50%, greater than 60%, or greater than 70%, by weight of the dispersion, e.g., about 40%, about 50%, about 60%, about 70%, about 80%, or any range between the recited values, e.g., about 40-70%, about 30-80%, about 50-80%, etc. 2 A nanocrystal dispersion comprising nanocrystals and a solvent.

21. TiO in the dispersion 2 The average particle size of the nanocrystals is in the range of 1 to 50 nm, e.g., 4 to 20 nm, or 15 to 20 nm, as measured by TEM, and the TiO 2 21. The nanocrystal dispersion of any one of claims 20, wherein the D9999 of the nanocrystals is in the range of 20 to 500 nm, preferably less than 200 nm, as measured by DLS.

22. A nanocomposite formulation comprising a nanocrystal dispersion according to any one of claims 20 to 21 and a monomer, oligomer and / or polymer.

23. 1) At least partially capped TiO 2 A nanocomposite formulation comprising: nanocrystals; 2) monomers, oligomers, and / or polymers; 3) a solvent; and 4) a curing agent.

24. At least partially capped TiO 2 24. The nanocomposite formulation of any one of claims 22-23, wherein the nanocrystals are present in an amount of greater than 30% by weight relative to the monomer, oligomer and / or polymer, such as greater than 40%, greater than 50%, greater than 60%, greater than 70%, greater than 80%, or greater than 90%, such as about 40%, about 50%, about 60%, about 70%, about 80%, about 90%, or any range between the recited values, such as about 50-90%, about 40-80%, about 60-90%, etc.

25. The monomers, oligomers and / or polymers may be, for example, bisphenol A glycerolate dimethacrylate, esters with acrylic acid (OPPEOA), bisphenol A ethoxylate diacrylates, bisphenol A propoxylate diacrylate, bisphenol F ethoxylate (2 EO / phenol) diacrylate, bisphenol A glycerolate diacrylates, bisphenol A ethoxylate dimethacrylate, ethoxylated (4) bisphenol A diacrylate (SR-601), bisphenol A ethoxylate diacrylate (SR-349), tris(2-acryloyloxy)ethyl} isocyanurate, tricyclodecane dimethanol diacrylate, tris(2-hydroxyethyl) isocyanurate triacrylate, cresol novolac epoxy acrylate (CN112C60), benzyl methacrylate (BMA), benzyl acrylate, trimethylolpropane triacrylate (TMPTA), trimethylolpropane ethoxylate (1 25. The nanocomposite formulation of any one of claims 22 to 24, wherein the compound is an acrylate, epoxy, or isocyanurate selected from dimethylformamide (DMSO / EO / OH) methyl ether diacrylate, 1,6-hexanediol diacrylate (HDDA, SR238B), tri(ethylene glycol) diacrylate, ethylene glycol diacrylate, poly(ethylene glycol) diacrylate, glycerol 1,3-diglycerolate diacrylate, di(ethylene glycol) diacrylate, and combinations thereof.

26. TiO as measured by DLS as a 5% nanocrystal dispersion in PGMEA 2 The average particle size of the nanocrystals is 1-5 nm, 5-10 nm, 10-15 nm, 15-20 nm, 20 30 nm, 30-40 nm, or 40-50 nm, with D9999 less than 100 nm, and TiO 2 A nanocomposite formulation according to any one of claims 22 to 25, wherein the D9999 of the nanocrystals is in the range of 20 to 500 nm, preferably less than 200 nm, as measured by DLS;

27. At least partially capped TiO nanocrystals are present in an amount greater than 50%, e.g., greater than 60%, greater than 70%, greater than 80%, or greater than 90%, by weight of the nanocomposite, e.g., about 55%, about 60%, about 70%, about 80%, about 90%, or any range between the recited values, e.g., about 55-90%, about 60-90%, about 70-90%, by weight of the nanocomposite. 2 A nanocomposite film comprising nanocrystals and at least one monomer, oligomer, and / or polymer.

28. 28. The nanocomposite film of claim 27, wherein the % transmittance of the film having a thickness of 1 micron is greater than 80%, e.g., greater than 85%, greater than 90%, greater than 95%, greater than 97%, greater than 98%, greater than 99%, e.g., about 85%, about 90%, about 95%, about 97%, about 98%, about 99%, about 99.5%, or any range between the recited values, e.g., about 90-99%, at a wavelength of 400 nm.

29. When measured with a Prism Coupler for films having a thickness of <5 um, at 448 nm, the optical transmittance is from about 1.70 to about 2.10, e.g., 1.70-1.72, or 1.72-1.74, or 1.74-1.76, or 1.76-1.78, or 1.78-1.80, or 1.80-1.82, or 1.82-1.84, or 1.84-1.86, or 1.86-1.88, or a refractive index of 1.88 to 1.90, or 1.90 to 1.92, or 1.92 to 1.94, or 1.94 to 1.96, or 1.96 to 1.98, or 1.98 to 2.00, or 2.00 to 2.02, or 2.02 to 2.04, or 2.04 to 2.06, or 2.06 to 2.08, or 2.08 to 2.10; and / or from about 1.70 to about 2.10, for example, from 1.70 to 1.72, or from 1.72 to 1.74, or from 1.74 to 1.76, or from 1.76 to 1.78, or from 1.78 to 1.80, or from 1.80 to 1.82, or from 1.82 to 1.84, or from 1.84 to 1.86, or from 1.86 to 1.88, or from 1.88 to 1.90, or from 1.90 to 1.92 29. The nanocomposite film of any one of claims 27 to 28, having a refractive index of 1.92 to 1.94, or 1.94 to 1.96, or 1.96 to 1.98, or 1.98 to 2.00, or 2.00 to 2.02, or 2.02 to 2.04, or 2.04 to 2.06, or 2.06 to 2.08, or 2.08 to 2.

10.

30. 30. The nanocomposite film of any one of claims 27 to 29, having a hardness as measured by nanoindentation of greater than 50 MPa, greater than 100 MPa, or greater than 200 MPa, or greater than 300 MPa, or greater than 400 MPa, e.g., about 55 MPa, about 100 MPa, about 200 MPa, about 300 MPa, about 400 MPa, about 500 MPa, or any range between the recited values, e.g., about 50-500 MPa, or about 100-400 MPa.

31. The haze of the nanocomposite film is less than 0.1%, or less than 0.2%, or less than 0.3%, or less than 0.4%, or less than 0.5%, or less than 1% (e.g., about 0.01% to about 0.1%, about 0.1% to about 0.2%, about 0.1% to about 0.5%, about 0.2% to about 0.5%, or about 0.1% to about 1%), and the at least partially capped nanocrystals are uniformly dispersed in the film without agglomeration, as observed by uniform particle distribution in TEM, SEM, or EDX images, to achieve a uniform RI distribution. The nanocomposite film according to any one of claims 27 to 30.

32. A device comprising the nanocomposite film of any one of claims 27 to 31.

33. 33. The device of claim 32 which is an optoelectronic device, a photovoltaic device, a catalytic device, a fuel cell, a battery, a smart window, a sensor, a CMOS sensor, an LED, a mini LED, a micro LED, an organic LED (OLED), a quantum LED (QLED), a touch screen, a display, a flexible electronics device, a printed electronics device, augmented reality, virtual reality, mixed reality, a waveguide, a diffraction grating, or a solar cell device.

Citation Information

Patent Citations

  • Titania coating liquid and its production method, and titania film and its formation method

    JP2001262008A

  • Synthesis, cap formation, and dispersion of nanocrystals

    JP2014503446A

  • Organic solvent dispersion of titanium oxide particles and method for producing the same

    JP6011749B1

  • Method for producing organic solvent dispersion of titanium oxide particles

    JP6028958B1

  • Method for preparing organic ligand-capped titanium dioxide nanocrystals

    US20060188431A1